The role of solvent in lignin hydrothermal liquefaction: its influence on conversion and phenolic monomer selectivity - Dong-Can Lv; Meng-Ru Chen; Yue-Yuan Ye; Duo Wang; Zhi-Min Wang; Yun-Quan Liu (Fuel, 2026)

Structure and characteristics of quercetin-loaded starch nanoparticles and their surface charges for protein corona formation with gastrointestinal digestive enzymes - Yu-Ru Wu; Zhi-Yuan Yang; Shan-Dan Zhao; Dan-Yang Shen; Ya-Jun Lin; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2026)

Paternal vitamin D deficiency is associated with offspring testicular developmental abnormalities, fibrosis, and altered sperm miRNA profiles - Yu-Ming Chen; Zhi-Hong Tian; Shi-Yuan Li; Juan Dai; Xing-Ru Wang; Guo-Ying Sun; Min Liu; Berthold Hocher; Mei Tian (Molecular Biology Reports, 2026)

MiR-324-5p mitigates experimental acute pancreatitis by suppressing Rock2 expression - Qian Chen; Zhao Shen; Qingmei Wang; Ru Jiao; Yehong Liu; Tingting Meng; Yunhui Fei; Caixia Liu (Mammalian Genome, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Origin of fast backward steps and detachment of kinesin motor under backward load - Jie Wang; Xiao-Xuan Shi; Yu-Ru Liu; Peng-Ye Wang; Ping Xie (Journal of Theoretical Biology, 2026)

Characterization of hygroscopicity-based mixing state at four sites in China - Jingye Ren; Fang Zhang; Lu Chen; Jieyao Liu; Wei Xu; Honghao Xu; Zhe Wang; Ru-Jin Huang (Journal of Aerosol Science, 2026)

Polymer-specific oxidative biotransformation of polyethylene and polypropylene microplastics by the stored-grain pest Tribolium castaneum - Sakhawat Shah; Jin-Ru Zhao; Ze-Yu Liu; Yi-Jia Chen; Jie Tang; Karam Khamis Elgizawy; Qiu-Ying Huang; Elvis Genbo Xu; Feng-Lian Yang (Chemical Engineering Journal, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Metagenomics-guided targeted isolation and mechanistic elucidation of haloalkaliphilic bisphenol A-degrading microorganisms - Sai Yang; Kai-yan Xing; Yue-fei Tao; Jia-yu Wang; Ke-hang Liu; Meng Zhang; Xiang-ru Xu; Lin Zhu; Wei Wei (Bioresource Technology, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Copper and zinc isotopes reveal redox-driven nutrient cycles in the Mesoproterozoic ocean - Kexin Song; Dandan Li; Chengshuai Yuan; Yang Liu; Yuan-Ru Qu; Sheng-Ao Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mechanisms of typical antibiotic degradation and suppression of resistance gene propagation in a biological manganese oxidation reactor - Huaqing Liu; Xin-Ru Jia; Chong-Yang Ren; Xiaoqiang Cao; He-Ping Zhao; Jian Zhang (Journal of Water Process Engineering, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Colloidal biochar promotes microbial carbon dioxide fixation and enhances net soil organic carbon gain - Jia Bing Liu; Jia Wang; Wang Kai Tong; Han Tang; Mei Ru Yue; Piao Yi Jiang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Chemical Engineering, 2026)

The co-ecotoxicity of microplastics and associated contaminants (PFOA) on soil ecosystems - Si-Yu Liu; Feng Han; Li-Qi Ma; Zheng Li; Chun-Ru Qin; Ikram Yaqine; Yi-kai Wang; Jian Su; Jie Chen (Journal of Environmental Chemical Engineering, 2026)

Mixed-gas nanobubble and colloidization stacked modification: Enhancing porous/chemical properties and endowing rapid adsorption function of biochar - Mei Ru Yue; Han Tang; Wang Kai Tong; Jia Bing Liu; Piao Yi Jiang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Chemical Engineering, 2026)

Modification of shrimp tropomyosin properties for improved functional performance: TGase modification and polyphenol-beta-glucan modification - Shiqi Liu; Ru Meng; Kexin Jiang; Yinuo Bai; Zhenxing Li; Lingyi Liu; Jin Wang; Lianliang Liu (Food Chemistry, 2026)

Incorporation of nanoscale fishbone enhances frozen snakehead fish slice quality via synergistic mechanisms: Pickering emulsion oxygen barrier and TGase-mediated protein crosslinking - Ziaur Rahman; Liangzi Zhang; Yajin Zhang; Arsalan Khan; Junaid Khan; Soottawat Benjakul; Qilin Huang; Shanbai Xiong; Juan You; Ru Liu; Dan Jia; Tao Yin (Food Chemistry, 2026)

Pectin-induced quality improvement of pea protein emulsion template oleogels and their application as fat replacers in sponge cakes - Ru Zhao; Xinxin Yin; Meijun Liu; Guanxin Xie; Yijian Li; Min Zhang; Tiehua Zhang; Haiqing Ye; Cuina Wang (Food Chemistry, 2026)

Pickering emulsion stabilized by whey protein isolate and psyllium husk powder: Interface properties and stabilization mechanism - Huifang Liu; Ru Tian; Yinshi Sun; Shuang Jiang; Di Qu (Food Chemistry, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Amine-functionalized oyster shell waste for hexavalent chromium removal and phosphate recovery - Kamonchanok Huangmee; Liang-Ching Hsu; Guan-Ru Liu; Pei-Chieh Tseng; Heng Yi Teah; Yu-Min Tzou; Nhu Anh Thi Than; Han-Yu Hsueh; Yu-Ting Liu (Bioresource Technology, 2026)

Differential host choices of Helicoverpa armigera and H. assulta to tomato - Jie-Wen Mao; Qian-Wen Luo; Shao-Ting Duan; Meng-Hao Zhang; Xiao-Guang Liu; Xian-Ru Guo; Yan-Min Liu; Wei-Zheng Li (Arthropod-Plant Interactions, 2026)

Analyzing phosphorus flow in crop production via interpretable machine learning: Insights from a typical agricultural region of Jiangxi Province, China - Yuejin Chen; Wending Huang; Lele Ru; Shuhui Peng; Wuhu Guo; Evgeny Abakumov; Ekaterina Chebykina; Yalan Zhang; Zanxu Chen; Dan Wang; Shijie Dai; Yanqi Liu; et al. (Applied Geochemistry, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

Disentangling species-specific controls on urban tree transpiration: A Bayesian framework - Xiang Zhang; Xue Zhong; Jun-Ru Yan; Qi Li; Ling-Ye Yao; Kai-Xin Liu; Astrid Moser-Reischl; Thomas Rötzer; Stephan Pauleit; Mohammad A. Rahman (Agricultural and Forest Meteorology, 2026)

Electroacupuncture-induced gut microbiota alterations correlate with FXR/FGF15 activation and metabolic improvement in hyperlipidemic rats - Huan Wu; Li Zhou; Wei Lin; Hong-xing Zhang; Zhao-qing Zhang; Xiao-fei Wang; Shi-ru Ju; Zhi-gang Liu; Fei Hu (Advances in Traditional Medicine, 2026)

Integration of niche evolution and pre-adaptation shaped the diversity of Cypripedium (Orchidaceae) in subtropical and temperate regions since mid-Miocene times - Liu-Qiong Wei; Peng Zhou; Pei-Yang Zhang; Si-Xian Li; Bo-Ni Lai; Ru-Yang Ye; Ji-Hong Li; Yan Luo; Xiao-Hong Zeng; Yi-Zhen Liu; Xiao-Guo Xiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Corrigendum to “Hydrological seasonality mediates scale-dependent land use effects on riverine microplastic pollution” [Water Research 301 (2026) 126043] - Qinwei Chen; Peng Wang; Ru Liu; Wang Shu; Guangpeng Liu; Lixin Zhu (Water Research, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

A hybrid deep learning framework for estimating urban tree transpiration - Xiang Zhang; Xue Zhong; Jun-Ru Yan; Qi Li; Kai-Xin Liu; Ling-Ye Yao; Long-Hao Zhang; Astrid Moser-Reischl; Thomas Rötzer; Stephan Pauleit; Mohammad A. Rahman (Journal of Environmental Management, 2026)

Prior-guided multi-domain mixture-of-experts for multimodal Earth observation data gaps - Chuang Liu; Jianhua Guo; Yingdong Pi; Xiao Wu; Zhiqi Zhang; Ru Chen; Xinyi Wang; Mi Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Optimized green extraction of flavonoids from Lycium barbarum leaves using betaine-ethylene glycol NADES: Mechanisms, identification, and bioactivity - Ya-Jie Yuan; Zhen Liu; Yu-Ru Wang; Xin-Yue Zhang; Qian Ma; Cen Xiang; Jun-Wei Yu; Yu-Ou Teng (Food Chemistry, 2026)

Mechanisms and effects of ozone-pullulanase treatment on multiscale structures and in vitro digestibility of rice starch - Zixuan Liu; Chunfan Guo; Mingyue Chen; Yaping Xu; Jingxuan Ma; Ru Wang; Zhaoxia Wu (Food Chemistry, 2026)

Microbial and metabolomic analyses elucidate the Debaryomyces hansenii-mediated flavor enhancement in dry-aged black pig pork - Ruo-Chun Kao; Meng-Ru Lee; Rung-Jen Tu; Wen-Shyan Chen; Hsiao-Mei Liang; Hsiu-Ming Liu; Hsin-Hui Su; Yen-Po Chen; Yung-Tsung Chen (Food Microbiology, 2026)

A core innate immune gene panel derived from germ-free larval zebrafish transcriptomics resolves strain-specific induction by Aeromonas veronii and Lacticaseibacillus rhamnosus GG - Xiang-Ru Liu; Ying Liu; Chen-Cong Zhang; Zi-Shu Huang; Feng-Yi Guo; De-Sheng Pei (Fish & Shellfish Immunology, 2026)

Diniconazole leads to neurotoxicity in zebrafish via triggering TLR4/MyD88-mediated immune-inflammatory responses - Hongying Zhang; Ru Guo; Youjuan Wu; Jiajun Huang; Zijia Yin; Kaiwen Zhao; Xuefeng Liu; Meifeng Li; Zeyin Jiang; Shanghong Wang; Lihua Fan; Chengyu Hu; et al. (Fish & Shellfish Immunology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Rational design of covalent-noncovalent coupled interface structures via vacuum-assisted self-assembly/ice-templating dual processes for high thermal conductive composites - Yuqin Liu; Xu Li; Ru Xia; Jiasheng Qian; Bin Wu (Chemical Engineering Journal, 2026)

Shape-memory effect in a flexible hydrogen-bonded organic framework for efficient C2H2/CO2 separation - Chunchen Gao; He Zheng; Wenjie Chen; Yiting Guo; Ru Xu; Ziyi Luo; Qifeng Luo; Xingliang Nie; Xin Lian; Xiongli Liu; Yabing He; Lin Li; et al. (Chemical Engineering Journal, 2026)

A gully catchment-scale model for predicting loess cave density: a case study from the Loess Plateau - Xiaolei Gao; Haopeng Geng; Meiqin Han; Wanying Xu; Ru Liu; Weiming Cheng; Baotian Pan (CATENA, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Role of pickering emulsions in enhancing the preservability and functionality of protein gel systems: a structured review with bibliometric analysis - Ramy M. Khoder; Arsalan Khan; Ziaur Rahman; Nayyar Iqbal; Qilin Huang; Juan You; Mahmoud Salah; Ibrahim Khalifa; Tao Yin; Ru Liu (Critical Reviews in Food Science and Nutrition, 2026)

Cross-frequency SAR indices for rice mapping using multi-frequency and full-polarization data - Qihao Chen; Shuxin Liu; Guangchao Li; Ru Li; Yuanye Cao; Ge Su; Xiuguo Liu (International Journal of Remote Sensing, 2026)

Hydrological seasonality mediates scale-dependent land use effects on riverine microplastic pollution - Qinwei Chen; Peng Wang; Ru Liu; Wang Shu; Guangpeng Liu; Lixin Zhu (Water Research, 2026)

Comparative study on combustion characteristics of dual-fire sources in naturally ventilated tunnels: Effects of fuel type and spacing - Wenhao Xue; Yuan Wang; Yang Lou; Xinlei Liu; Ru Zhou; Min Hao; Juncheng Jiang (Tunnelling and Underground Space Technology, 2026)

Paedocin A: An undescribed iridoid with a C1-C4 ether linkage from Paederia foetida with hepatoprotective effects - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry Letters, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Cadmium disrupts the immune antibacterial function of the freshwater crab Sinopotamon henanense via the Toll/proPO-AS pathway - Yue Liang; Duwen Pei; Cheng Liu; Fenjun Yan; Minnan Bao; Na Liu; Qian Wang; Caiping Feng; Ru Jia; Lan Wang (Journal of Hazardous Materials, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Two stages of Sn enrichment in granitic magmatism: insights from Sn isotopes of cogenetic minerals - Jia-Xin She; Weiqiang Li; Ru-Cheng Wang; Lei Xie; Chen Liu; Zhihao Xu; Shichao An; Cheng Xu (Geochimica et Cosmochimica Acta, 2026)

Bioactivity assay coupled with molecular networking for the discovery of antioxidants from purslane - Yan-Xi Li; Mei-Ru Wang; Long-Gao Xiao; Huan Yan; Shan-Shan Ling; Hui Liu; Tao-Bin He; Wei Ni; Xin Fang; Hai-Yang Liu (Food Research International, 2026)

LncRNA WFDC21P mediates the tobacco carcinogen induced malignant transformation of human normal lung epithelial cells by regulating tumor stemness - Shengsheng Li; Ru Liu; Shiyao Ye; Yitong Li; Linhan Huang; Qiuxian Wan; Zhuolin Liu; Yibo Wu; Nuoyan Wang; Minmin Huang; Jianjun Wu (Food and Chemical Toxicology, 2026)

Health Benefit Assessment of Continuous Improvement of Air Quality Action Plan in China - Weiming An; Hongtao Mao; Xiaoda Xue; Xiaoqian Cai; Xin Song; Pengbo Wang; Yongle Liu; Hongyu Ji; Jianbo Ru; Lei Zhang (Environmental Pollution, 2026)

PdPI, a PISTILLATA ortholog from Populus davidiana, enhances drought tolerance by regulating stomatal aperture and antioxidant defense - Siyuan Li; Meiqi Lu; Ling Jin; Zhanchen Ren; Xinyu Wang; Song Chen; Yunxia Wei; Jiaxin Liu; Yuanfu Liu; Haoran Bao; Yue Zhang; Tingyu Cao; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

TRMT10A maintains lipid homeostasis independently of its tRNA m1G9 methyltransferase activity - Huihui Sun; Yu Wang; Shanpeng Liu; Yan Jin; Jianyang Ge; Bowen Zhang; Yongteng Wang; Weifeng Sun; Yun Bai; Yuyong Tao; Yi Lu; Ru-Juan Liu; et al. (Science China Life Sciences, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

FOXG1 Transcriptionally Orchestrates Parvalbumin+ Interneuron Function Contributing to Schizophrenia Pathology - Pengfei Jiang; Mingzhao Su; Xue Zhou; Baoshen Zhang; Jie Sun; Ru Ba; Junhua Liu; Chunjie Zhao (Neuroscience Bulletin, 2026)
Schizophrenia (SCZ) is characterized by heterogeneous symptoms including abnormal perception, social withdrawal, and cognitive deficits. Parvalbumin-positive (PV + ) interneurons are particularly vulnerable in SCZ; however, the underlying cellular basis remains unclear. In this study, we found that selective deletion of the SCZ risk gene Foxg1 in PV + interneurons of mice recapitulated aspects of the disease phenotype, including impaired sensorimotor gating, anxiety-like behavior, social deficits, and cognitive impairments. Foxg1 deficiency caused dendritic simplification, reduced spine density, and impaired synaptic transmission in PV + interneurons of the prelimbic cortex. Our findings indicate that FOXG1 directly drives a set of SCZ risk genes that encode synaptic receptors, adhesion molecules, scaffolding proteins, transporters, ion channels, and vesicle-trafficking proteins, thereby orchestrating PV + interneuron synaptic function. Notably, FOXG1 activates the transcription of metabotropic glutamate receptor 3 (mGluR3), and pharmacological potentiation of mGluR3 activity alleviates behavioral deficits in Foxg1 conditional knockout mice. In conclusion, our findings identify a novel role for Foxg1 in PV + interneurons, providing new mechanistic insights into their vulnerability to SCZ.

Microplastics Inhibit Microbial Abundance and Enzyme Activities in Pb/Cd Co-contaminated Soil: The Alleviating Role of Biochar - Si-Yu Liu; Feng Han; Li-Qi Ma; Zheng Li; Chun-Ru Qin; Ikram Yaqine (Journal of Soil Science and Plant Nutrition, 2026)

Precision droplet deposition control in helicopter spraying: a novel valve-switch timing method accounting for headwind effects - Shuping Fang; Yu Ru; Ningning Wang; Xiaojun Jin; Chunxia Jiang; Yangyang Liu; Chao Zhang (Computers and Electronics in Agriculture, 2026)

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

Regionally specific dysregulation of gut microbiota and host–metabolite interface in podophyllotoxin-induced enterotoxicity based on the toxicological evidence chain concept - Tao Jiang; Jiaxing Sun; Chuanxin Liu; Yuhan Sun; Hetao Chen; Dongxia Liu; Ruyan Chen; Yanqiu Wang; Yi Ru; Jiajia Duan (Toxicology and Applied Pharmacology, 2026)

Deep carbon cycling in continental subduction zones - Sheng-Ao Liu; Wan-Yu Sun; Yuan-Ru Qu; Hong-Li Yang (Lithos, 2026)

Dual-engineered defect-rich molecularly imprinted zirconium metal organic framework platform for selective adsorption and ultrasensitive analysis of alternariol - Shi-Rong Sun; Lu Liu; Xia Wang; Yan Dong; Yan Li; Qianyun Sun; Yanfang Zhao; Xiangfeng Chen; Yong-Ning Wu; Rabah Boukherroub; Ru-Song Zhao (Journal of Hazardous Materials, 2026)

Enhanced photocatalytic fuel cell performance via C/WO3/ZnFe2O4 ternary photoanode for simultaneous wastewater degradation and energy harvesting - Yi Xiao; Ru Zhang; Qi Feng; Hailong Gao; Jiawei Ma; Ting Wu; Yongkui Huang; Longjun Xu; Chenglun Liu (Journal of Environmental Management, 2026)

Ozone-mediated microbial succession and kinetic for refrigerated grass carp (Ctenopharyngodon idella) fillets - Cheng Guo; Guodong Xu; Shanbai Xiong; Tao Yin; Ru Liu; Juan You (International Journal of Food Microbiology, 2026)

Numerical and experimental study on the soot formation in methane multi-jet flames under microgravity - Wen-Jiao Wang; Kai-Ru Jin; Zhi-Hao Zheng; Hong-Qing Shi; Du Wang; Ling-Nan Wu; Ya-Wen Liu; Longfei Li; Jiayu Sun; Yu Cheng Liu; Zhen-Yu Tian (Fuel, 2026)

Calcium-promoting peptide IWGR and EIY: Targeted screening based on the calcium-sensing receptor (CaSR), validation through in situ single-pass intestinal perfusion (SPIP), and analysis of calcium-promoting characteristics - Hongli Zhi; Xiaomin Liu; Xinmiao Sun; Jingjing Ru; Shan Gao; Huiping Liu; Xiaowei Zhang (Food Chemistry, 2026)

Low kinetic perturbation by the rapidly advancing ice-water interface suppresses Na+/Cl− induced myofibrillar protein network assembly - Yajin Zhang; Ziaur Rahman; Hongwei Song; Shanbai Xiong; Tao Yin; Ru Liu; Juan You (Food Chemistry, 2026)

Green and efficient extraction of polyphenols from Lycium barbarum leaves using a betaine-based natural deep eutectic solvent: Process optimization, mechanistic elucidation, and bioactivity evaluation - Ya-Jie Yuan; Zhen Liu; Yu-Ru Wang; Jing-Yi Wang; Qian Ma; Cen Xiang; Jun-Wei Yu; Yu-Ou Teng (Food Chemistry, 2026)

Shifting carbon emission dominance across subway lifecycle phases: A refined subsystem-interaction assessment - Jing Pu; Chen Cai; Shijun Chen; Ru Guo; Ruimin Lin; Xingyu Ding; Jia Liu; Kaiming Peng; Xiangfeng Huang (Environmental Impact Assessment Review, 2026)

Constructing compatible LLZTO/PEO interfaces with fast Li+ transport channels for high-performance composite polymer electrolytes - Yimei Jin; Yiting Lin; Zekai Zhang; Bing Li; Ru Wang; Cheng Lian; Xia Han; Honglai Liu; Haiping Su; Jingkun Li (Chemical Engineering Journal, 2026)

Capacity prediction of cobalt nickel phosphide supercapacitors based on machine learning - Qiang Shen; Licheng Zhu; Zhibo Shen; Tianzeng Ru; Minghui Guo; Jun Ren; Tao Wu; Zhanqiang Liu (Chemical Engineering Journal, 2026)

Knowledge-infused hierarchical causal inference framework for decoding sludge settleability to quantitatively regulate multi-process wastewater treatment - Yucheng Li; Chen Cai; Feiyun Sun; Xiangfeng Huang; Kaiming Peng; Ru Guo; Jia Liu (Bioresource Technology, 2026)

Study on the Diversity of the CXCL8 Family in Carassius auratus : Homologue Characteristics and Tissue‐Specific Immune Responses Under H. doneci Infection - Jin‐ye Zhang; Hong‐yan Liu; Yue‐ru Wang; Yuan‐jun Zhao (Journal of Fish Diseases, 2026)
Chemokines are essential for vertebrate immune regulation, and teleosts possess diverse CXCL8 lineages. However, studies on CXCL8 in C. auratus remain limited. In the present study, four CXCL8 homologues ( CaCXCL8‐1 to ‐4 ) were successfully cloned and identified from C. auratus , and their expression patterns were analysed in the tissues of healthy and those naturally infected with H. doneci . Bioinformatic analyses revealed that all homologues possess the conserved structural features of CXC chemokines. However, the divergence was observed in the N‐terminal ELR motif: CaCXCL8‐1 and CaCXCL8‐2 harboured a QLR motif, whereas CaCXCL8‐3 and CaCXCL8‐4 possessed a DPR motif. Phylogenetic analysis classified CaCXCL8‐1 and CaCXCL8‐2 into the CXCL8_L2 lineage, and CaCXCL8‐3 and CaCXCL8‐4 into the teleost‐specific CXCL8_L1b lineage. Tertiary structure predictions indicated that CaCXCL8‐1, −3, and −4 conserve key receptor‐binding sites, whereas CaCXCL8‐2 retained only GAG‐binding sites, suggesting potential functional divergence. Under healthy conditions, the four homologues were all constitutively expressed but displayed divergent basal profiles. Following H. doneci infection, they exhibited distinct tissue‐specific expression patterns: CaCXCL8‐1 was significantly upregulated in the gills; CaCXCL8‐2 was specifically induced in the spleen; CaCXCL8‐3 was markedly upregulated in both the gills and head kidney; and CaCXCL8‐4 was upregulated in the liver and head kidney but downregulated in the spleen. These divergent expression patterns suggest functional specialisation among the CaCXCL8 homologues, with different paralogs potentially coordinating localised versus systemic immune responses. Our findings provide evidence for the functional diversification of the CXCL8 chemokine in teleosts and contribute to understanding the evolution of complex immune systems in vertebrates.

Integrative analysis of lncRNAs associated with disulfidptosis-related genes for prognostic risk evaluation and tumor immune microenvironment assessment in laryngeal squamous cell carcinoma - Qinghua Liu; Zesheng Zhang; Yingli Xie; Ru Tang; Ge Gao; Zhe Yang; Duanshali Liu; Yilun Zou; Yongxia Zhang; Mingbo Liu (Human Cell, 2026)

Cross-feeding supports the growth of ammonia-oxidizing bacteria with reduced genomes during evolution - Yiming Feng; Ru Zheng; Lingrui Kong; Zhang Zhang; Baiyizhuo Chen; Sitong Liu (Water Research, 2026)

Mobility heterogeneity influences the relationship between built environment and metro travel emissions - Jing Pu; Chen Cai; Wei Zhu; Quan Yuan; Ru Guo; Xingyu Ding; Jia Liu; Kaiming Peng; Yanei Xue; Xiangfeng Huang (Transportation Research Part D: Transport and Environment, 2026)

Danaeopsis Heer ex Schimper (Marattialean fern) from the upper Middle Triassic of Ordos Basin, North China and a review of the genus - Yanqi Sun; Shenghui Deng; Yuanzheng Lu; Ru Fan; Dan Lyu; Songyan Liu (Review of Palaeobotany and Palynology, 2026)

Three undescribed terpenoids from the aerial parts of Alstonia scholaris - Bing-ru Liu; Chun-xiang Xu; Dan Liu; Yue Feng; Rong-tao Li; Jin-dong Zhong (Phytochemistry Letters, 2026)

Liquid-phase hydrogenation of benzaldehyde to benzyl alcohol over NiCoAl‑R catalysts: Synergistic metal–metal oxide interfaces for enhanced catalytic performance - Lingmei Yang; An Wei; Ru kuan Liu; Guo ling Zhang; Bing Han; Baining Lin; Lianhua Li (Journal of Environmental Chemical Engineering, 2026)

Superoxide dismutase/peroxidase-like MoS2 quantum dots enhance ammonia synthesis by Klebsiella pasteurii - Meng-Xin Zhao; Si-Ru Chen; Shan-Shan Hu; Ting-Ting Liu; Jia-Le Teng; Ya-Wen Yu; Jia-Long Zhang; Xue-Ru Zhou; Qun-Feng Ye; Su-Fang Qin; Le-Xing You (Journal of Environmental Chemical Engineering, 2026)

Flos Trollii polyphenol-fortified noodles: Dual enhancement of textural properties and reduction of in vitro starch digestibility - Kebing Yan; Xianqing Ye; Xiaoai Zhu; Yuan Ru; Yage Liu; Yiying Niu; Jun Xi; Kunlun Liu (Journal of Cereal Science, 2026)

New strategy for high-value utilization of silver carp skin/bone mixture: Steam explosion combined with stepwise enzymatic hydrolysis to produce endogenous calcium-bound ACE inhibitory peptides - Zijuan Li; Qingxiang Feng; Yanlei Gao; Tao Yin; Juan You; Shanbai Xiong; Ru Liu (Innovative Food Science & Emerging Technologies, 2026)

Carboxymethylated PGA/ASK composite: Synergistic mechanism for stabilizing protein network and improving freeze resistance of shrimp gel - Kaina Duan; Zijing Liu; Luhan You; Jie-ting Geng; Wenge Yang; Huamao Wei; Tao Huang; Ru Jia (Innovative Food Science & Emerging Technologies, 2026)

Ratio limitation of burnt-bitter-aroma compounds in strong-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Zheng-Juan Zhu; Jing Luo; Ling Xiang; Yan-Hong Xiang; Song-Tao Wang; Wen-Wen Zhang; Qing-Qing Liu; Ting Huang; Zheng-Hong Xu; Yong-Jun Yuan (Food Chemistry, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Iron and zinc isotopic insights into the formation of Archean continental crust - Jianfeng Ma; Hamed Gamaleldien; Robert H. Smithies; Tim Johnson; Yuan-Ru Qu; Sheng-Ao Liu; Christopher L. Kirkland (Earth and Planetary Science Letters, 2026)

Constructing an in-situ Fenton reaction using iron-air fuel cells with a graphite cathode for landfill leachate treatment - Sizhuo Wan; Cong Ding; Bingyin Liu; Mahmood Qaisar; Bibi Saima Zeb; Ru Wang; Linjiang Yuan (ENGINEERING Environment, 2026)

Investigation on Ionospheric TEC disturbances During the Geomagnetic Storms Resulted from ICME Events - Chao Niu; Xiang-yu Li; Xiao-niu Zeng; Hong-ru Li; Ji-hao Liu; Ai-min Du (Applied Geophysics, 2026)

Functional homogenization of terrestrial mammals outside protected areas in the Hengduan Mountains, China - Xueyou Li; Wenqiang Hu; Kenneth Otieno Onditi; Quan Li; Zhechang Hu; Ru Bai; Yang Liu; Hongjiao Wang; Xuelong Jiang (Conservation Biology, 2026)
Despite the crucial role of human impacts on biodiversity loss, many assessments of this loss focus on single metrics, such as species richness, and overlook the multidimensional effects of human activities. Because of its importance to ecosystem functioning, we investigated the functional diversity of medium‐ and large‐sized mammal assemblages in protected and unprotected mountain forests in the Hengduan Mountains of southwest China. We hypothesized that anthropogenic pressures outside protected areas (PAs) favor generalist species and lead to functionally homogenized assemblages compared with assemblages inside PAs. Using generalized dissimilarity models, we also examined the key drivers shaping patterns of functional β diversity in these landscapes. Outside PAs, functional richness was markedly lower, trait space was significantly more homogeneous, and nestedness β diversity was more prevalent (57.6%) than inside PAs, clear indications of functional homogenization. Anthropogenic variables consistently outweighed environmental gradients and spatial distance in explaining variation in functional β diversity. Our results demonstrate that anthropogenic pressure affects trait composition in ways that species counts alone do not fully capture, emphasizing the importance of conservation strategies that protect both functional integrity and taxonomic diversity.

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Emulsion-template oleogels: Formation mechanisms, structural regulation, and potential as solid fat substitutes - Ru Zhao; Min Zhang; Meijun Liu; Xinxin Yin; Guanxin Xie; Haiqing Ye; Tiehua Zhang; Cuina Wang (Food Research International, 2026)

Synergistic flavor enhancement and polycyclic aromatic hydrocarbons inhibition in roasted fish by Perilla-clam/yeast composite extracts: Regulation of Maillard reaction and lipid oxidation pathways - Yiling Tian; Tong Li; Yunyue Shan; Shanbai Xiong; Ru Liu; Yueqi An (Food Chemistry, 2026)

Green manure co-application boosts arid agroecosystem sustainability: Mixed sowing of feed rape and hairy vetch modulates N input and enzymes for optimized wheat production - Ru Yu; Jie Zhou; Fangdi Chang; Jiashen Song; Jing Wang; Xiaobin Li; Hua Zhang; Jufeng Cao; Xiaohong Li; Hanjiang Liu; Hongyuan Zhang; Yuyi Li (Field Crops Research, 2026)

A novel dual-function biosensor based on polarity reversal of MFC for bioelectricity generation and detecting trimethylamine-N-oxide - Sheng-chao Gao; Yu-xuan Wang; Yong-dong Li; Ru-meng Zhang; Ya-nan Zhang; Jin-song Dong; Hong-xia Ni; Yi Chen; Xi-hui Shen; Ying Liu (Chemical Engineering Journal, 2026)

Multifunctional carboxymethyl cellulose/polydopamine dual-network conductive hydrogels for motion detection and photothermal therapy - Yiying Wei; Bo Cong; Xiaopu Ji; Dangyang Wang; Jinghui Hu; Zonglei Mou; Haiqing Song; Yue Zhi; Yushu Liu; Guofeng Zhang; Wan Ru Sun; Pingyu Wang; et al. (Carbohydrate Polymers, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

Rethinking crustacean shell waste valorization: from environmental burden to microbial platform for sustainable bioproducts - Ru-Li He; Dong-Feng Liu (ENGINEERING Environment, 2026)

Study of enhancing analgesic potential of μ-conotoxins from the computational and pharmacological insights - Fan Zhao; Yunxia Liu; Ying Cui; Yushan Ding; Liu Ru; Ting Meng; Hongtao Yang; Yongbo Song (Molecular Diversity, 2026)

Mechanochemistry synthesis of Al-fumarate MOF towards high-performance in solar-driven interfacial water evaporation and electricity generation - Jun Liu; Ruiqi Li; Guixin Hu; Nan Yao; Juan He; Ru Tao; Tingting Jia; Li Lu; Liping Zhao; Jiang Gong (Journal of Environmental Chemical Engineering, 2026)

Insights into frozen quality preservation and energy conservation of salted swamp eel (Monopterus albus) fillets - Hongwei Song; Yajin Zhang; Hong Yang; Ru Liu; Tao Yin; Liu Shi; Juan You (International Journal of Refrigeration, 2026)

From biomass to supercapacitor electrode materials: bamboo derived carbon decorated with MnO2 used in flexible energy storage device - Pengfei Jia; Binyang Liu; Shenao Li; Yizhan Sun; Shuwen Lv; Ru Liu; Yuandong Xu; Xia Zhang; Wei Kong Pang; Peng Li (Fuel, 2026)

Distinguishing the contributions of organic matter and iron (oxyhydr)oxides to zinc availability in paddy soils surrounding lead-zinc mines - Yecheng Li; Zebin Hong; Yan Ru; Guojun Chen; Xiaomin Li; Shiwen Hu; Yang Yang; Chao Guo; Shan Wang; Pengfei Cheng; Qi Wang; Tongxu Liu (Environmental Pollution, 2026)

Drivers of urban street blocks thermal pleasure: SHAP interpretation of psychological, environmental perception, and microclimate factors - Xiaodong Xuan; Ru Liu; Zixu Zhang; Leiming Yang; Yihe Zheng; Yongjian Liu (Energy and Buildings, 2026)

Assessing synergy of CO2 and pollutant reductions in industrial parks from the industrial chain perspective - Shenghua Yan; Chen Cai; Jia Liu; Kaiming Peng; Ru Guo; Xiangfeng Huang (Environmental Impact Assessment Review, 2026)

Multi-channel carbon nanofibers with enhanced ion diffusion and ultra-stability for flexible supercapacitors at commercial-scale mass loading - Guangjie Yang; Yulong Yang; Jian Song; Zhenye Yin; Qian Zhang; Zhenlu Liu; Haoqi Yang; Min Ru; Shaochun Tang; Shuijian He (Chemical Engineering Journal, 2026)

Novel Lactobacillus Strains Alleviate E. coli-induced Inflammation in a Urinary Tract Infection Rat Model - Sini Kang; Zhihua Peng; Ru Wei; Jiaxin Liu; Hee-Jun Kim; Yongjun Lee; Moonjin Ra; Eun Ji Kim; Heo Keon; Jong Ik Jeon; Min Ji Jang; Myeong Soo Park; et al. (Probiotics and Antimicrobial Proteins, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Uncertainty quantification of the hardening soil model - Bangxiang Li; Youliang Zhang; Zhongliang Ru; Hao Liu; Zhiqing Wang; Hongbo Zhao (Bulletin of Engineering Geology and the Environment, 2026)

Protist‐Bacteria Trophic Interactions Contribute to Higher Community Stability in Subsoils Than Topsoils - Suo Liu; Jingyi Ru; Sihang Deng; Jiesi Lei; Zhencheng Ye; Yu Tang; Changchun Zhai; Shiqiang Wan; Yunfeng Yang (Global Change Biology, 2026)
Climate change is reshaping ecosystem components and functions across soil profiles. In this study, we examined the effects of altered precipitation and nighttime warming on soil microbial communities in both topsoils (0–20 cm in depth) and subsoils (20–50 cm in depth) in a long‐term field experiment in Inner Mongolia, China. Unexpectedly, moisture, belowground net primary production, and NO 3 − content in subsoils were all affected more by climate changes than topsoils. Moreover, using multiple resistance metrics, including α‐diversity, β‐diversity, microbial network complexity, and network robustness, we found that both bacterial and protistan communities in subsoils exhibited greater resistance to climate change than those in topsoils, while fungal communities showed no consistent pattern. Enhanced bacterial resistance in subsoils was associated with lower 16S rRNA gene operon ( rrn ) copy number, reduced GC content, lower genome and cell size, and other oligotrophic traits, collectively supporting adaptation to nutrient‐poor and stressful environments. Protistan resistance in subsoils tracked bacterial resistance and was reinforced by stronger trophic interactions and functional traits such as protective shells, greater motility, and reduced cell size, reflecting a bottom‐up control, as soil protists are primarily phagotrophs shaped by bacterial prey supply. Abundant bacteria enhanced resistance through oligotrophic adaptations and positive intra‐community interactions, while abundant protists reduced resistance, potentially due to the dominance of negative intra‐community interactions. Partial least squares analyses revealed that microbial community resistance modulated soil heterotrophic respiration (R h ), connecting community resistance to carbon cycling. Together, these findings demonstrate that the often‐overlooked resistance of subsoil microbiomes could buffer ecosystem functions under future climate conditions, suggesting that traits (e.g., rrn copy number) and trophic interactions can outweigh diversity for community stability.

Chronic Excessive Exposure to Fluoride Impairs the Intestinal Mucosal Barrier to Cause Inflammatory Response and Microbiome Dysbiosis in Rats - Jia-Rong Zhang; Yi-Wen Li; Hong-Xuan Chen; Yi Luo; Ru-Ming Liu; Jian-Bin Wang; Ning-Ning Liu; Jian-Hui Xiao (Biological Trace Element Research, 2026)

Recent understanding of crosstalk between muscle and different organs in regulating freshwater fish flesh quality under stress condition: A review - Liwen Wu; Liangzi Zhang; Ling Peng; Yong Long; Guili Song; Soottawat Benjakul; Juan You; Ru Liu; Qilin Huang; Huawei Ma; Dan Jia; Tao Yin (Aquaculture, 2026)

Transcriptomic reveals the acute exposure of ammonia nitrogen on muscle quality in fish: the coupling effect of acidity, thermal, and salinity - Ling Peng; Tao Yin; Shanbai Xiong; Juan You; Ru Liu; Qiling Huang; Soottawat Benjakul; Dan Jia (Aquaculture, 2026)

Causal-informed domain adaptation with cross-attention for predicting anomalous effluent quality fluctuations in wastewater treatment plants - Hanxin Zhang; Haiping Zhang; Jia Liu; Kaiming Peng; Ru Guo; Feiyun Sun; Xiangfeng Huang; Chen Cai (Water Research, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Bacillus velezensis synergizes with coal gangue to enhance Medicago sativa growth: Insights into nutrient cycling and soil fertility enhancement - Yaya Wang; Mingwu Liu; Zijie Xi; Kuanysh T. Tastambek; Meili Du; Xiangrong Liu; Xuan Xie; Ru Zhang; Nuraly S. Akimbekov (Rhizosphere, 2026)

Overexpression of SlPMEI3 in tomato increased the viscosity of ketchup and juice - Chunyu Liu; Yonghui Zhu; John B. Golding; Penta Pristijono; Yue Guan; Youjian Yu; Yong He; Yongxin Li; Zhujun Zhu; Lei Ru (Plant Science, 2026)

Cyclopentanoid monoterpene glycosides from the aerial parts of Paederia foetida L - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry, 2026)

The variations of the North African monsoon precipitation over the past 200 years - Sainan Liu; Ru Huang; S.-Y. Simon Wang; Chenxi Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Manganese acts as savior rather than accomplice of antibiotic stress: Dual cycles of ROS scavenging and Mnammox - Dong-Jun Hou; Wei-Lin Guo; Qian-Ru Liu; Hong-Wei Yang; Qiu-You Xu; Yun-Fei He; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Microplastic-pathogen interactions differentially modulate tomato Fusarium wilt severity: The dependence of polymer biodegradability - Siqi Shen; Yawei Zhou; Ru Zhao; Meng Liu; Wenjiang Fu; Shuting Zhao; Chaokai Yan; Qi Gao; Dan Zhang; Yanhua Wang; Hanzhong Jia; Yahong Wei (Journal of Hazardous Materials, 2026)

Biovoltage-driven, sulfurized Fe–Co anode promoted the generation of salt source active species for enhanced antibiotic removal - Shengtao Jiang; Jie Fang; Hao Zhou; Xiaojun Wang; Haoyang Liu; Deman Han; Ru Jiang; Yutong Cai; Yiting Shi; Yanbiao Liu (Journal of Environmental Management, 2026)

Temperature-driven regime shifts in riverine bacterial communities: Machine learning identifies key thresholds and seasonal management implications - Ru Liu; Peng Wang; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang; Qinwei Chen; Wei Yang (Journal of Environmental Sciences, 2026)

Impact of polysaccharide addition on the digestive properties of porcine bone soup:Based on the gastrointestinal tracts of adults and elderly - Meiqi Dang; Dongmei Zhang; Huilong Dong; Shanbai Xiong; Ru Liu; Tao Yin; Juan You (Food Research International, 2026)

Mechanism of flavor enhancement by yeast extract and clam extract in ginger-surimi cake: Insights from flavoromics and machine learning - Yiling Tian; Hanpu Gao; Tong Li; Yunyue Shan; Shanbai Xiong; Ru Liu; Yueqi An (Food Research International, 2026)

Preparation of indicator cards for freshness detection of rice with four different processing degrees during storage based on olfactory visualization technology - Wan-ru Liu; Yang Yang; Yue Xu; Bing Wang; Guang Zhang; Xin-yu Xu; Yuan-yuan Wang; Chun-min Ma; Na Zhang (Food Chemistry, 2026)

Influence of extraction conditions on self-assembled colloidal particle formation in ginseng aqueous extract - Di Qu; Ru Tian; Huifang Liu; Jiyue Sha; Zhitong Wang; Liankui Wen (Food Chemistry, 2026)

Grape seed extract incorporated into konjac glucomannan-based batter inhibits acrylamide and advanced glycation end products in fried fish nuggets - Runlin Wu; Jingwen Sun; Xia Mou; Shanbai Xiong; Ru Liu (Food Chemistry, 2026)

Natural yeast proteins as pickering particles: structural features driving their emulsification behavior - Qiqi Li; Shuo Shen; Shanbai Xiong; Tao Yin; Juan You; Ru Liu (Food Hydrocolloids, 2026)

Mechanism of the influence of single-phase dynamic gelation process on the structure and properties of bigels - Yanlei Gao; Qing Xiong; Shilin Zhao; Qilin Huang; Yang Hu; Ru Liu (Food Hydrocolloids, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

GaAs/GaN-based self-powered catalytic systems driven by tribovoltaic effect enable efficient degradation of azo dyes - Meng-Nan Liu; Yan-Xin Wu; Yu-Tong Sun; Xu Li; Ru Li; Jun Zhang; Yun-Ze Long (Chemical Engineering Journal, 2026)

A microgel-microstructure synergistically enhanced flexible sensor via DLP 3D printing for wearable electronics - Xiangyu Liu; Lijun Dong; Yi Ru; Lanlan Dong; Wurikaixi Aiyiti; Cijun Shuai (Chemical Engineering Journal, 2026)

Soil biogeochemical controls on the distribution of phosphorus fractions in the Qilian Mountains of China’s drylands - Zeng-Ru Wang; Ji-Liang Liu; Feng-Rui Li (Plant and Soil, 2026)

Multi-source remote sensing for spatial mapping of salt-affected agricultural soils in Taiwan - Nguyen-Thanh Son; Chein-Hui Syu; Chi-Farn Chen; Cheng-Ru Chen; Huan-Sheng Lin; Yi-Ting Zhang; Tsang-Sen Liu; Chun-Chien Yen (Applied Geomatics, 2026)

Bridging Aquaculture and Human Medicine: A Comprehensive Review of Zebrafish Models for Chronic Kidney Disease - Feng‐Yi Guo; Hao‐Yu Yang; Lan‐Chen Zhang; Xiang‐Ru Liu; Pan‐Pan Jia; De‐Sheng Pei (Reviews in Aquaculture, 2026)
Chronic kidney disease (CKD) poses a significant global health burden, necessitating robust animal models for mechanistic studies and drug discovery. Zebrafish offers unique advantages as a powerful models in kidney disease, including high‐throughput compatibility, optical transparency, and significant genetic and nephron homology with both humans and farmed teleosts. However, challenges, such as the species' potent regenerative capacity and a lack of standardized diagnostic thresholds, hinder their broad application. This review systematically summarizes four principal induction strategies: environmental stress, nephrotoxic chemical exposure, CRISPR/Cas‐based gene editing, and transgenesis. We further outline a validation pipeline that integrates functional assays, morphometrics, and histopathology, while advocating for cross‐laboratory harmonization. Additionally, we compare risk factors for CKD and CKD of unknown etiology (CKDu), emphasizing environmental contributors. Collectively, we propose zebrafish as a reproducible platform for aquaculture applications, specifically for nephropathy early‐warning systems and functional feed assessment, and for human therapeutic research. These standardized models hold great promise for high‐throughput drug screening and elucidating disease mechanisms, facilitating the translation of findings to both aquaculture and clinical medicine.

Research progress on chemical constituents and biological activities of medicinal plants from Euonymus genus - Ying-Jun Ma; Xin-Ru Li; Meng-Qi Gao; Jia-Jia Liu; Ammara Khalid; Jie-Ting Chen; Fan-Cheng Meng (Natural Product Research, 2026)

Real-time visualization of Nocardia seriolae proliferation and macrophage migration in the Northern snakehead (Channa argus) - Jian Teng; Jian-Ru Liu; Yi-Xiang Zhai; Sheng-Liang Cao; Zhen-Shu Si; Qing-Teng Ren; Xiang-Shan Ji; Mei-Hua Lu; Yu-Bao Li; Yan Zhao (Aquaculture, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Construction of WO3/ZnIn2S4 Z-scheme heterojunction by electrostatic self-assembly to enhance charge separation and reactive oxygen species generation - Mengge Yan; Tingting Liu; Yushan Hu; Wenlong Bai; Mingfei Wei; Yuxuan Zhang; Xusheng He; Ru Li (Journal of Water Process Engineering, 2026)

Quantifying contributions of iron (oxyhydr)oxides and organic matter to chromium dynamics in paddy soils - Guojun Chen; Yang Yang; Ke Zhang; Yan Ru; Zebin Hong; Xiaomin Li; Taicheng An; Pei Wang; Songxiong Zhong; Qi Wang; Shiwen Hu; Fangbai Li; et al. (Geochimica et Cosmochimica Acta, 2026)

Coconut shell pyrolysis oil: dual-pathway approach to antioxidants and renewable aromatic biofuels - Ru Sun; Jincheng Zhang; Meng Sun; Xinghua Liu; Dan Qian; Ping Huang (Fuel, 2026)

Lactic acid modulates empty-cup aroma persistence in Baijiu via molecular interaction mechanisms: a case study of strong-aroma and soy-sauce-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Xiao-Juan Zhang; Zheng-Juan Zhu; Ru-Yi Li; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Guan-Yu Fang; Qing-Qing Liu; Yong-Jun Yuan; et al. (Food Chemistry, 2026)

Construction of acyl-homoserine lactone-producing engineered bacteria for activating low-temperature anammox process - Jiangwei Wang; Jianhang Zhou; Yiming Feng; Jingqi Sun; Ru Zheng; Kuo Zhang; Juejun Pan; Xiaogang Wu; Liguo Zhang; Sitong Liu (Environmental Research, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Side-chain modified covalent organic frameworks for enhanced visible light photocatalytic degradation of bisphenol A and application in seawater - Tianshuo Liu; Jing Sun; Meng Xie; Ru-Song Zhao (Chemical Engineering Journal, 2026)

Dual-modal antioxidant nanozyme hydrogel for protection against noise-induced hearing loss via attenuation of oxidative stress and NF-κB/MAPK signaling - Liang Xia; Ru Tang; Yi Chen; Ning Ma; Lili Xiao; Xiaoyan Chen; Xiaoyin Mao; Keyi Li; Yanmei Feng; Jingjing Liu; Amin Zhang (Chemical Engineering Journal, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Mechanisms and Scenario Predictions of the Digital Economy’s Impact on Pollution and Carbon Emission Reduction: A Case Study of the Yellow River Basin in China - Tianle Shi; Zhengmeng Hou; Jianhua Liu; Hao Fang; Qichen Wang; Yilin Guo; Ru Zhang; Liangchao Huang (International Journal of Environmental Research, 2026)
This study investigates how the digital economy reduces pollution and carbon emissions (RPCE) in the Yellow River Basin through three core mechanisms: (1) enabling real-time environmental monitoring and precision regulation, (2) fostering enterprise green production via digital transformation, and (3) driving technological innovation and industrial upgrading, proposing three testable hypotheses on these pathways. Indicators for the digital economy and RPCE are developed, and a spatiotemporal analysis of RPCE levels is conducted at both the municipal and grid scales. Employing the STIRPAT (Stochastic Impacts by Regression on Population, Affluence, and Technology) model to comprehensively examine population, affluence, and technology drivers, and innovatively integrating analysis at both municipal and grid scales to overcome traditional limitations, this study examines the direct and mediating effects of the digital economy on RPCE, along with heterogeneity analysis, endogeneity discussions, and exogenous shock tests, providing a more refined framework for revealing the mechanisms. Based on empirical findings, future RPCE trends in the basin are projected, with a proposed three-pronged strategy: digital infrastructure deployment, sector-specific interventions, and place-based prioritization (technology-upgrading midstream; clean-energy transition upstream). The main conclusions are as follows: (1) During the study period, RPCE in the Yellow River Basin showed significant improvement, with an upstream > downstream > midstream pattern and a block-like distribution. (2) The statistically significant regression coefficient (β = -0.476, p < 0.01) indicates a positive impact of the digital economy on RPCE, thus validating Hypothesis 1. Both technological innovation and industrial structure upgrading serve as positive mediators in the influence of the digital economy on RPCE, confirming Hypotheses 2 and Hypotheses 3. (3) The growth rate of population size is a major factor driving divergence in the RPCE index across the basin. To advance RPCE in the Yellow River Basin, policies should prioritize the development of the digital economy while promoting high-quality economic growth and stabilizing population growth rates.

Artificial restoration improved the complexity of the soil microbial co-occurrence network and the resistance of microbial communities to environmental changes in degraded sandy grassland - Wentao Mi; Ru Meng; Weibo Ren; Ting Yuan; Yi Liu; Huijie Han; Jialu Liang; Jinqi Zhang (Agriculture, Ecosystems & Environment, 2026)

Optimizing the spatial configuration of scallop suspended cultivation net cages by leveraging seston flux variables based on the lattice Boltzmann hydrodynamics - Gangqin Tu; Haifei Liu; Zhiming Ru; Tao Sun; Wei Yang; Wei Huang; Li Cheng (Aquaculture, 2026)

Knockdown of chitinase genes enhances larvae susceptibility to Beauveria bassiana in Spodoptera frugiperda - Yue Zhang; Ru Chen; Xiaoying Lv; Lina Zeng; Zexin Gao; Xianyi Wang; Hongmei Liu (Pesticide Biochemistry and Physiology, 2026)

Ecological impacts and sustainable development of offshore wind farm pile foundations in the Bodhi Island area - Xiaochen Cheng; Ting Wang; Zhaoming Gao; Xu Wang; Shuai Liu; Yongchao Hu; Beini Deng; Libin Zhang; Xiaoshang Ru (Marine Environmental Research, 2026)

Autophagy, ROS, and their interplay in plant adaptive responses - Chi Zhang; Song-Qi Li; Pengwei Jing; Run-Xin Wu; Yu-Qing Ma; Ji-Xiao Wu; Ru-Feng Song; Wen-Cheng Liu (Journal of Plant Physiology, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Optimizing intermittent rotary aeration to enhance efficiency and reduce greenhouse gas and ammonia emissions during fish manure composting - Kai Zhang; Jishu Zheng; Ke Liu; Lihong Gao; Ru Bi; Fangying Ji (Journal of Environmental Management, 2026)

Zinc isotopes equilibrium fractionation induced by α-Al2O3 surface adsorption and its implications: A density functional theory study - Yin-Chuan Li; Hai-Zhen Wei; Martin R. Palmer; Ya-Ru Zhou; Hao-Long Li; Zhi-Jie Liu; Yong-Hui Li (Geochimica et Cosmochimica Acta, 2026)

Improvement of surimi gel quality by lotus leaf and its aqueous extract: Insights from gel properties, digestive characteristics, and functional activities - Meiqi Dang; Shuning Cao; Shikang Sang; Shanbai Xiong; Ru Liu; Tao Yin; Juan You (Food Research International, 2026)

Untargeted metabolomics elucidates the enhanced protective effects of blackberry juice fermented with Lacticaseibacillus paracasei on hypothalamic-pituitary-adrenal (HPA) axis neuronal dysfunction - Han Wu; Qing-Ru Di; Anthony Pius Bassey; Shu-Dong Xie; Maria G. Corradini; Jian-Zhong Zhou; Xiao-Li Liu (Food Chemistry, 2026)

Proteomic analysis of exudates reveals the quality of marinated snakehead fish slice as affected by precooling and freezing treatments - Ziaur Rahman; Yajin Zhang; Arsalan Khan; Soottawat Benjakul; Qilin Huang; Shanbai Xiong; Juan You; Ru Liu; Tao Yin (Food Chemistry, 2026)

Food byproduct-derived as sustainable nano-stabilizers for Pickering emulsions influenced by macronutrient composition - Ramy M. Khoder; Mahmoud Abou-Elsoud; Nayyar Iqbal; Ibrahim Khalifa; Juan You; Qilin Huang; Tao Yin; Ru Liu (Food Chemistry, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Effect of environmentally relevant concentrations of estrogens on the fear-like response of male zebrafish - Ying-Ying Zhang; Ru-Yi Tan; Hong Tao; Qi-Liang Chen; Yan-Jun Shen; Zhi-Hao Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Configurational entropy–induced lattice distortion in high-entropy Prussian blue analogues derived transition metal phosphide accelerates electrocatalytic hydrogen evolution in alkaline media - Yu-Ru Liu; Mia Rinawati; Ping-Chen Shi; Sofiannisa Aulia; Wuttichai Tanmathusorachai; Hsin-Chih Huang; Wei-Nien Su; Ling-Yu Chang; Wei-Hsiang Huang; Min-Hsin Yeh (Chemical Engineering Journal, 2026)

A hydrogel-based SERS sensor with wearable potential and machine learning integration for sweat stimulant detection - Ru Liu; Xin Zhuang; Ping Lin; Luyao Lin; Jiajia Liu; Yuhua Hu; Ruiyun You; Yudong Lu (Chemical Engineering Journal, 2026)

Behaviors and adaptive strategies of anammox microbiota in response to typical ionic liquid: Metabolic compensation and gene regulation - Dong-Jun Hou; Wei-Lin Guo; Hong-Wei Yang; Qian-Ru Liu; Nian-Si Fan; Ren-Cun Jin (Bioresource Technology, 2026)

Seasonal and day-night variations in light absorption properties of humic-like substances and effects of aqueous-phase photooxidation - Wei Yuan; Jing Duan; Ting Wang; Yi Liu; Jie Guo; Wenjuan Cao; Ru-Jin Huang (Atmospheric Research, 2026)

A proposed framework based on traffic volume and the design of a bottom-up methodology to estimate the CO emission of on-road vehicles - Shan-Yi Shen; Ru-Yun Chang; Yun-Wei Liao; Wei-Chun Chou; Yu-Hao Lin; Ping-Yu Liu (Atmospheric Pollution Research, 2026)

Synthetic microalgae community promotes chili growth planted in waste stone powder by enriching beneficial root endophytic bacteria and fungi - Cong Liu; Hongqing Wei; Shaoguo Ru; Weizhong Wang; Zhengmao Li; Lijuan Liu; Xiukai Song; Jun Wang (Plant and Soil, 2026)

Microglial Activation Mediates Drp1-Dependent Mitochondrial Fission and Neuronal Apoptosis in a Lipopolysaccharide-Induced Model of Cognitive Dysfunction - Meng-Jie Chen; Jia-Qi Ning; Jia-Xi Liu; Jian-Sheng Luo; Ru-Yu Yan; Yu-Xuan Yang; Xiang Li; Ling-Ling Ding (Molecular Neurobiology, 2026)

Fluorescent aptasensor based on magnetic bead–assisted displacement reaction for monitoring vancomycin in plasma - Cheng-Shiuan Hsieh; Hsu-Yun Tsai; Ting-Chien Tsai; Yang-Chun Wang; Yi-Tung Cheng; Jing-Ru Liou; Meng-Yu Liu; Yen-Ling Chen; Chien-Chin Chen (Analytica Chimica Acta, 2026)

Overlooked Roles of Pharmaceutical Metabolic Products in Stimulating Microbial Metabolism and Antibiotic Resistance Gene Dissemination of Anaerobic Sludge - Jing Wu; Dan Sun; Yuan Pan; Dong‐Feng Liu; Hui Zhang; Jun‐Hua Zhou; Tong Gao; Jie Wu; Ru‐Li He; Yin‐Guang Chen; Wen‐Wei Li (Environmental Microbiology, 2026)
The roles of non‐antibiotic pharmaceuticals in shaping the dissemination behaviours of antibiotic resistance genes (ARGs) in wastewater treatment systems remain poorly understood, and the influences of their transformation products have been overlooked. Here, we unveil more profound impacts of the metformin (MET) biotransformation product than the parent pollutant on the microbial community structure and ARG propagation of wastewater anaerobic sludge. The exposure to MET and its metabolic products guanylurea (GUA) at environmentally relevant concentrations both raised the methane production and resulted in up to 52.5% higher sludge ARGs abundance relative to the unexposed control. Especially, the GUA group showed up to 188‐fold upregulation in several ARGs including bcrA , PmrF , acrB and mexF , enabled 3218‐fold enrichment of plasmids from several bacteria. The underlying mechanisms were elucidated by integrated metagenomics, molecular dynamics simulations, and metabolic profiling analyses. MET and GUA were found to trigger coordinated cellular responses including disrupted glycerophospholipid metabolism, increased membrane permeability and broad metabolic reprogramming, which collectively boosted the ARGs dissemination. Overall, this work establishes a mechanistic link between micropollutant‐induced microbial stress and ARGs propagation in anaerobic sludge, and advocates for re‐evaluating the environmental risks of non‐antibiotic pharmaceuticals and integrating resistance control into wastewater management framework.

Prediction Of Relative Permeability Curve Based On Machine Learning Driven By Logging Data - Jia-ru Zou; Shou-dong Huo; En-liang Liu; Tong-sheng Zeng; Lian-lian Hu; Ya-ying Song; Meng Li (Applied Geophysics, 2025)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

Pathogenic and beneficial microbial communities determine the shelf life of stored 'Fengtangli' plums - Yu-Ru Wang; Tomislav Cernava; Shi-Xian Zeng; Hong Chen; Feng-Quan Liu; Zheng-Qing Fu; Tao Zhou; Yong Wang; Jia Liu (Postharvest Biology and Technology, 2025)

Mechanistic advances in hyperuricemia and anti-hyperuricemia therapies - Mingyue Ao; Xi Zhang; Ru Chen; Chun Xiao; Yinhua Liu; Min Gao; Ya Zhang (PharmaNutrition, 2025)

Mixed gas nanobubbles promote microbial CO2 fixation: Universal verification, mechanism, and application - Jia Wang; Piao Yi Jiang; Jia Bing Liu; Han Tang; Wang Kai Tong; Jia Jie Zou; Mei Ru Yue; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Management, 2025)

High efficient protein recovery from surimi rinsing wastewater by coupling isoelectric and electrophoretic effects in an electric field - Shilin Zhao; Jiani Zhang; Yanlei Gao; Shanbai Xiong; Juan You; Tao Yin; Ru Liu (Innovative Food Science & Emerging Technologies, 2025)

Interactive effect of various fatty acids and the Maillard reaction of sesame meal enzymatic hydrolysates on aroma generation - Qing-qing Ruan; Bei-bei Hu; Kai-yue Su; Jun-ru Li; Wen-ting Yin; Zi-qi Han; Yu-xin Liu; Xiao-shuang Cai (Food Research International, 2025)

Enhancing emulsion stability in pork bone soup: Exploring the synergistic effects of polysaccharides and high-pressure homogenization - Yajin Zhang; Dongmei Zhang; Huilong Dong; Shanbai Xiong; Tao Yin; Ru Liu; Juan You (Food Chemistry, 2025)

Natural and built environments and heart failure risk: An exposome-wide analysis in the UK Biobank - Xuewei Huang; Siyu Yin; Meng Yao; Fang Lei; Weifang Liu; Lijin Lin; Tao Sun; Yuanyuan Cao; Xingyuan Zhang; Ru Li; Liwen Wang; Yufeng Hu; et al. (Environmental Research, 2025)

Performance and toxicity assessment of photocatalytic degradation of sulfanilamide by g-C3N4 nanosheets constructed using temperature gradient regulated etching - Yujie Jiao; Yaqi Mao; Fei Fu; Yongxia Ma; Ru Li; Qikai Liu; Jiali Lei; Sujin Lu; Yang Liu (Environmental Research, 2025)

Deciphering actomyosin functions in plant cytokinesis: A half-century odyssey - Bo Liu; Takumi Higaki; Yuh-Ru Julie Lee (Current Opinion in Plant Biology, 2025)

Millisecond-scale removal of ciprofloxacin hydrochloride using self-assembled nanolayered CoFe catalytic membrane - Shengtao Jiang; Xiaoli Liu; Deman Han; Jianqiang Zhu; Ru Jiang; Xiaohuan Liu; Haoyang Liu; Yanbiao Liu (Chemical Engineering Journal, 2025)

Selective energy transfer via chromium clusters for high-performance blue-excitable shortwave infrared phosphors - Shih-En Chen; Kuan-Chun Chen; Chuan-Fang Tsao; Yu-Chieh Huang; Agata Lazarowska; Mikołaj Kamiński; Natalia Majewska; Tadeusz Leśniewski; Grzegorz Leniec; Ewa Mijowska; Ding-Hwa Cherng; Ting-Wei Yeh; et al. (Chemical Engineering Journal, 2025)

Isorhamnetin alleviates acute liver injury by blocking ferroptosis - Didi Liu; Yao Zeng; Tao Meng; Yi Ru; Xinru Zhou; Yun Huang; Wei Jiang; Xueting Lang; Ye Tao; Yi Huang (Chemical Engineering Journal, 2025)

Designing light-guiding carriers in microalgal-bacterial systems: From optimization to integration and development perspectives - Cong-Cong Tang; Jin-Qiao Liu; Yong-Qi Cheng; Ya-Ru Hu; Zhang-Wei He; Wen-Qiong Wang; Zhi-Hua Li; Xiaochang C. Wang; Yu Tian (Chemical Engineering Journal, 2025)

A Transformer-based framework with generative spectral augmentation for online monitoring of hyaluronic acid fermentation - Weilu Tian; Lixuan Zang; Yunyi Li; Cheng Peng; Jinhua Zhang; Huarong Shao; Ruiqing Xian; Ru Sun; Fei Liu; Haining Tan; Peixue Ling (Carbohydrate Polymers, 2025)

GNF-5837 attenuates acute liver injury by inhibiting oxidative stress - Xinru Zhou; Xianyu Luo; Qian Huang; Yi Ru; Didi Liu; Maoyuan Linghu; Yi Huang (Molecular Biology Reports, 2025)

Renal Denervation Improves Myocardial Mitochondrial Dysfunction and Myocardial Fibrosis by Inhibiting the NE/KLF15/renalase Pathway - Ye Chen; Ru Fu; Miao Huang; Tao Liu; Lixiong Zeng; Xiaogang Li (Molecular Neurobiology, 2025)

Transcriptome analysis reveals no obvious unintended effects in the spleen of CRISPR/Cas9-mediated CD163 and pAPN double-knockout pigs - Zhi-Guo Liu; Nan Wang; Wan-Jie Wang; Lei Huang; Shun-Shun Chi; Yu-Xin Nie; Mao-Sha Yuan; Ya-Ru Sun; Yu-Lian Mu; Kui Li (Functional & Integrative Genomics, 2025)

Association between legume consumption and risk of esophageal cancer among Chinese adults: a 17-year prospective cohort study - Fengyi Huang; Xiaorui Zhang; Jiayue Li; Xinqing Li; Ru Chen; Shaoming Wang; Fen Liu; Wenqiang Wei (Cancer Causes & Control, 2025)

Nitrogen enrichment offsets the stimulation of soil respiration by increased precipitation in temperate grasslands - Ru Tian; Jiatao Zhang; Yan Shen; Lan Du; Jinbao Zhang; Shijia Yang; Zhongxiang Liu; Mengle Wang; Zhuwen Xu (Agricultural and Forest Meteorology, 2025)

High Quality, Granular, Timely, Trustworthy and Efficient Vertebrate Species Distribution Data Across a 30,000 km 2 Protected Area Complex - Yinqiu Ji; Alex Diana; Xueyou Li; Eleni Matechou; Jim E. Griffin; Shuwei Liu; Mingjie Luo; Chunying Wu; Ru Bai; Chenyang Yao; Tingting Yin; Feng Dong; et al. (Ecology Letters, 2025)
The routine generation of species distribution data at scale remains a challenge. We used aquatic environmental DNA metabarcoding to sample vertebrate species across the 30,000 km 2 Gaoligongshan region along the China–Myanmar border. In just 56 calendar days (33 researcher‐field‐days + 69 researcher‐lab‐days), we detected 389 vertebrate species, of which 35 are Red‐Listed. We introduce the ‘eDNA‐aware’ OccPlus occupancy model, which accounts for false‐negative and false‐positive error in the field and lab. OccPlus leverages the taxonomic breadth of eDNA datasets by using ordination to estimate species occupancies. We recover known biogeographic patterns and find that native terrestrial and fish species have higher occupancies inside protected areas while domesticated species and non‐native fishes have higher occupancies outside them. Our study demonstrates how eDNA metabarcoding can obtain high‐quality, granular, timely, trustworthy and efficient species distribution data to facilitate nature conservation and restoration.

Mechanism of Permeability Evolution in Coral Reef Limestone Under Variable Confined Pressure Using Nuclear Magnetic Resonance Technology - Yang Mo; Haifeng Liu; Yongtao Zhang; Shun Zhai; Peishuai Chen; Ru Qu; Fuquan Ji (Journal of Marine Science and Engineering, 2025)
The development of underground space in the South China Sea islands is an important way to enhance their protection capabilities. This study focuses on the stress loading and unloading conditions of surrounding rock during the excavation of underground caverns in island reefs. Laboratory variable confining pressure permeability tests were conducted to quantify the stress sensitivity of permeability in coral reef limestone based on Darcy’s law and the stress sensitivity index model equation for permeability. In addition, the use of nuclear magnetic resonance technology reveals the microscopic mechanism of coral reef limestone permeability evolution. The results of the experiments show that the permeability of coral reef limestone sample is mainly controlled by the advantaged permeable channels formed by large pores. During the stress loading stage, the pore structure inside the sample changes, with compression of large pores and generation of smaller pores, resulting in a decrease in effective permeable pathways and a decrease in permeability. When the stress loading reaches 4 MPa, the damage rate of the sample’s permeability is 19.6%. During the stress unloading stage, the recovery of the sample’s permeability shows a significant hysteresis effect. Due to the irreversible damage caused by the compression and collapse of the pore structure during the loading stage, the permeability of the sample cannot fully recover when unloaded to the initial stress state. Based on the experimental results, calculations show that the stress sensitivity coefficient of coral reef limestone permeability is 1.1 × 10−1 MPa−1, which is higher than that of conventional land-based rocks. The conclusions of this study can provide important design references for the stability control of surrounding rocks and geological hazard prevention during the excavation of underground chambers on the islands.

The function of salt responsive promoter of Suaeda salsa SsCLCb explains why the species can accumulate large amount of nitrate from saline soils - Chenyang Li; Runtai Zhao; Ru Liu; Ruiqi Zhang; Xiaolei Yang; Chaoran Shi; Lei Wang; Jie Song (Marine Pollution Bulletin, 2025)

Mechanistic insights into aristolochic acid-induced hepatocellular carcinoma: a multi-dimensional analysis integrating network toxicology, machine learning, and molecular dynamics simulation - Can Liu; Ru Qiao; Peng He; Wang Chen; Xiangting Gao; Fuyuan He (Toxicon, 2025)

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

Effects of pressure cooker treatment-induced protein oxidation of cereals on human gut microbiota using an in vitro fermentation model - Keying Chu; Xiaojie Cui; Yuhui Yang; Qiong Wu; Ru Liu; Yanli Xie (Food Research International, 2025)

Molecular insights into freeze–induced quality deterioration in surimi: Mechanisms and mitigation strategies - Zhijun Yang; Qing Xiong; Tao Yin; Juan You; Shanbai Xiong; Ru Liu (Food Chemistry, 2025)

Alteration in conformation and emulsibility of lactoferrin-low methoxyl pectin complexes induced by non-covalent interactions with rosmarinic acid - Chuanrui Jiang; Fujun Liu; Yuxin He; Ru Zhao; Chao Dong; Tiehua Zhang; Cuina Wang (Food Chemistry, 2025)

Effects of EGCG/TGase on the physicochemical properties and in vitro dynamic digestion characteristics of water-saving rinsed surimi gels - Qin Yang; Weixia Zhou; Die Hu; Chuan Li; Lu Zhang; Yongqiang Zhao; Shengbi Zou; Ru Liu; Youming Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Insights into the synergistic cross-linking effect of EGCG and TGase on surimi gels - Qin Yang; Jinling Li; Wentao Ma; Ru Liu; Shengbi Zou; Yongqiang Zhao; Shanbai Xiong; Jianhua Rong; Yang Hu (Food Chemistry, 2025)

AO168=O at environmentally relevant concentrations induces reproductive toxicity by causing germline apoptosis and cell cycle arrest in Caenorhabditis elegans - Yuxing Wang; Luyao Gu; Simin Li; Ru Liu; Tong Meng; Yue Yu; Rong Ye; Houhu Zhang; Rong Zhou; Yuanqing Bu (Environmental Research, 2025)

Cross-altitude distribution patterns of bacterial communities in Chinese rivers: evidence from meta-analysis - Ru Liu; Peng Wang; Qinwei Chen; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang (Environmental Research, 2025)

Accelerated abatement and de-alkalization of red mud tailings by enhanced solar evaporation - Zhi Qi; Liying Liu; Ru Xin; Nan Li; Zhe Wang; Xiaojing Di; Gang Kevin Li (Chemical Engineering Journal, 2025)

Ionic liquids accelerate the crystallization of a magnetic fluorine-functionalized 3D covalent organic framework for efficient capture of trace benzoylurea insecticides in juices and beverages - Zekun Liu; Lu Liu; Yan Dong; Yan Li; Chong Zhang; Xiao-Li Wang; Lingxi Zhao; Hai-Long Jiang; Yong-Ning Wu; Xiangfeng Chen; Feng Li; Ru-Song Zhao (Chemical Engineering Journal, 2025)

A Li-ion permeable poly(phenylene ether-ether-sulfone) interphase to address interfacial instability and structural degradation of Ni-rich NCM cathodes in poly(ethylene oxide)-based all-solid-state Li-ion batteries - Cheng-Hung Liao; Yu-Ting Weng; Senthil-Kumar Parthasarathi; Hsi Chen; Shu-Jui Chang; Guan-Yi Liu; Tsung-Yu Yu; Chih-Wen Pao; Ting-Shan Chan; Wei-Tsung Chuang; Chun-Chieh Wang; Ru-Jong Jeng; et al. (Chemical Engineering Journal, 2025)

Inspired by traditional printing pastes: Green eco-design of phytic acid-modified starch and durable flame-retardant cellulose-based fabrics - Wan-Meng Song; Bao-Hong Wang; Ru-Yu Fan; Yun Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Modeling Dress-Out Traits Based on Morphological Traits in the Siberian Prawn, Exopalaemon modestus (Heller, 1862) - Liangjie Zhao; Zhiguo Hu; Congying Duan; Ru Zhang; Jiahui Liu; Xusheng Guo (Fishes, 2025)
Dress-out traits, such as abdominal meat weight and abdominal meat percentage, are difficult to improve through direct selection in aquatic species due to the lack of reliable measurement methods. To facilitate the prediction of these traits from morphological characteristics in live prawn, Exopalaemon modestus, a total of 518 individuals were collected in 2025 from Suyahu Reservoir in the upper Huaihe River, China. After excluding individuals with incomplete appendages and egg-bearing females, 301 prawns were randomly selected for model development, and the remaining 60 were used for validation. Based on integrated grey relational analysis and path analysis, body mass was identified as the most effective predictor of abdominal meat weight (p

Inhibition of the NLR pathway alleviates MAPK1 mutation-driven proliferation and differentiation deficits and enhanced apoptosis in P19 cells - Tingying Lei; Lei Liu; Fei Guo; Ru Li; Li Zhen; Fang Fu; Min Pan; Jin Han; Hang Zhou; Chunling Ma; Ruibin Huang; Xinyi Zhao; et al. (Tissue and Cell, 2025)

Effects of curcumin on jejunal morphology and intestinal integrity of broiler under heat stress - Ding-Ding Zhang; Meng-Ru Xue; Yu-Ting Liu; Hong-Jie Cui; Ding-Ping Bai (Journal of Thermal Biology, 2025)

Salicylic acid promotes arsenic uptake in Pteris vittata via regulation of key genes and elevated nitric oxide and spermidine - Zhi-Hua Dai; Ze-Chao Li; Xi Chen; Ru Huang; Jian-Hua Sun; Chen-Jing Liu; Lena Q. Ma; Ru-Yi Yang (Journal of Hazardous Materials, 2025)

Porous Janus membrane for ultrasensitive detection and efficient degradation of sulfur mustard simulant - Meiyang Jin; Shuya Liu; Hailong Jiang; Xia Wang; Yongxian Guo; Yanjun Gong; Qiongzheng Hu; Ru-Song Zhao (Journal of Hazardous Materials, 2025)

Dewaterability and heavy metals stability of aerobically digested sludge improved by citric acid assisting Fe2+-activated percarbonate oxidation - Changgeng Liu; Ru Chen; Qiang Niu; Dandan Chen (Journal of Environmental Management, 2025)

Enhancing soil carbon sequestration capacity: Synergistic effect of low-release biochar and autotrophic microbial agents over one year - Han Tang; Jiajun Hu; Yundong Liu; Bu Li; Jia Wang; Wang Kai Tong; Mei Ru Yue; Jia Jie Zou; Min-tian Gao; Saiwei Zhang; Nan Liu; Jixiang Li (Journal of Environmental Chemical Engineering, 2025)

Effect on the characteristics of biofilm and activated sludge of different COD/TN in H-MABR reactor - Shizhang Wu; Xiaolin Li; Xing Zheng; Pengyu Zhuang; Chi Zhang; Qiujin Ru; Tong Liu; Kun Zhang; Xiaoguang Zhao; Guan Wang; Mingyang Qi; Xiaoliang Li (Journal of Environmental Chemical Engineering, 2025)

Nano architectonics via in situ growth of MIL-101(Fe) on modified sugarcane bagasse for selective capture of glyphosate from aqueous solution - Ru-yi Zhou; Ming-hua Liu; Yun Xiao; Yu Qin; Bo Zuo; Muhammad Akhtar Abbas; Jun-xia Yu; Xiao-di Li; Yue-fei Zhang; Ru-an Chi (Journal of Environmental Chemical Engineering, 2025)

Iron and zinc isotopes constrain the continental crust formation - Jianfeng Ma; Hamed Gamaleldien; Sheng-Ao Liu; Yuan-Ru Qu (Geochimica et Cosmochimica Acta, 2025)

Exploring the quality changes of carp roes: perspective from flavor characteristics and microstructure - Gaomin Han; Qiqi Li; Hui Hong; Juan You; Tao Yin; Shanbai Xiong; Ru Liu (Food Research International, 2025)

Effect of ice crystal formation on the mechanical and protein properties of grass carp (Ctenopharyngodon idella) flesh: Contributions of salt ions and freezing rate - Yajin Zhang; Huiyuan Jin; Ziaur Rahman; Shanbai Xiong; Tao Yin; Ru Liu; Qilin Huang; Juan You (Food Chemistry, 2025)

Mitigating fishy odor in surimi gels: Interactions between myofibril proteins and chito-oligosaccharides - Huifang Yang; Jing Qiu; Ramy M. Khoder; Shanbai Xiong; Ru. Liu; Yueqi. An (Food Hydrocolloids, 2025)

The threat of microplastics to human kidney health: Mechanisms of nephrotoxicity and future research directions - Ru-Yu Tan; Qin-Ying She; Yun-Ci Ma; Ming-Hong Liu; Li-Juan Li; Li-Li Huang; Yi-Wen Zhong; Hui-Xin Bi (Environmental Research, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Bi@Bi2WO6 with oxygen vacancies: A strategy for enhancing piezo-response and bandgap reconstruction to improve 2,4-DCP degradation - Guoguan Liu; Shan Zhong; Lishan Zhang; Hangyu Shi; Qian Zhang; Xuan Ru; Yifu Li (Chemical Engineering Journal, 2025)

SERS sensor based on carboxymethyl cellulose-silver hydrogel for dynamic detection of hydrogen sulfide in the inflammatory microenvironment - Qingling Nie; Ru Liu; Jiajia Liu; Yirong Xie; Yeting Tu; Ruiyun You; Yudong Lu; ChengLu Li; Zhenhua Liu; Jingbo Chen (Chemical Engineering Journal, 2025)

Reprocessable cross-linked EPDM elastomers with dynamic and tuneable imine network based on electronic effect - Zhongyang Liu; Ming Cao; Haoran Liu; Bin Wu; Jibin Miao; Youfeng Tian; Yuchao Ke; Ru Xia; Jiasheng Qian (Chemical Engineering Journal, 2025)

Fabrication of superhydrophobic PDMS/EP/ODA-MWCNT/MXene@PT electrode with electroactive shape memory effect for enhanced response stability - Ya-ru Ding; Hao-jie Zhang; Yi-fan Wang; Zhe Jia; Rang-tong Liu; Jing-jing Wang (Chemical Engineering Journal, 2025)

Corrigendum to “Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices” [Chem. Eng. J. 510 (2025) 161390/CEJ 161390] - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Polyphenol-synthesized nanoparticles with ALDH3A1 delivery ability for activating estrogen signaling for diabetic wound healing - Xiaoxuan Ma; Yiqiong Liu; Jingsi Jiang; Yi Ru; Ying Luo; Jiankun Song; Zhan Zhang; Ying Zhang; Dan Yang; Haotian Xu; Haiqing Dong; Yongyong Li; et al. (Chemical Engineering Journal, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Bigels as novel fat substitutes: fat simulation characteristics, quality regulation, future trends and challenges - Yanlei Gao; Qing Xiong; Qilin Huang; Yang Hu; Ru Liu (Trends in Food Science & Technology, 2025)

Effect of particle morphology on the dynamic properties of coral sands in the South China Sea: An experimental study - Ru Qu; Changqi Zhu; Haifeng Liu; Xinzhi Wang; Hexuan Zhang (Soil Dynamics and Earthquake Engineering, 2025)

Green manure roots return drives saline-alkali soil organic carbon accumulation via microbial necromass formation - Fangdi Chang; Hongyuan Zhang; Peiyi Zhao; Na Zhao; Jiashen Song; Ru Yu; Jing Wang; Xiquan Wang; Dongxun Han; Xiaodong Liu; Jie Zhou; Yuyi Li (Soil and Tillage Research, 2025)

Integrating machine learning and metabolomics to uncover new biomarkers for predicting pesticide exposure among patients with kidney function decline - Junne-Ming Sung; Yu-Chi Hung; Wan-Ru Wang; Chiau-Jun Chu; Yen-Ping Lin; Kuan-Hung Liu; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Arabidopsis HSFA1b functions as a heat sensor inhibiting OST1-mediated stomatal closure through its adenylate-cyclase activity - Yu Zhang; Ru-Feng Song; Xiao-Yu Hu; Hui Zhou; Wei Wang; Junli Zhang; Xin Zhang; Liu-Mei Li; Su-Ting Wang; Yuwei Song; Fuyou Xiang; Jingjing Xing; et al. (Molecular Plant, 2025)

Genomic analysis of Pseudoalteromonas sp. SD03 reveals its potential in chitin hydrolysis - Yu-Xuan Jiang; Wen-Yue Xu; Hui Liu; Si-Qi Lin; Sha-Sha Liu; Xi-Ying Zhang; Yan-Ru Dang (Marine Genomics, 2025)

FlexiSAM: A flexible SAM-based semantic segmentation model for land cover classification using high-resolution multimodal remote sensing imagery - Zhan Zhang; Daoyu Shu; Cunyi Liao; Chengzhi Liu; Yuanxin Zhao; Ru Wang; Xiao Huang; Mi Zhang; Jianya Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Cross-view geo-localization with panoramic street-view and VHR satellite imagery in decentrality settings - Panwang Xia; Lei Yu; Yi Wan; Qiong Wu; Peiqi Chen; Liheng Zhong; Yongxiang Yao; Dong Wei; Xinyi Liu; Lixiang Ru; Yingying Zhang; Jiangwei Lao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Comparison of hydroxylated flavonoids and their interaction with protein-based carriers - Zhi-Yuan Yang; Shan-Dan Zhao; Yu-Ru Wu; Qian Zhou; Wei Wang; Yi-Bin Zhou; Kang Liu (Food Chemistry, 2025)

Covalent binding of vitamin K3 photosensitizers to nanofibrous membranes for daylight-driven antimicrobial applications - Yibo Ru; Qingli Dong; Kexin Li; Xinyi Zhao; Lang Yan; Xiang Wang; Yangtai Liu; Yue Ma (Chemical Engineering Journal, 2025)

The effect of ligand regulation on mechanism of alkaline oxygen evolution reaction under industrial scale - Xin-Ru Li; Xue-Jun Zhai; Hao-Zheng Liu; Xin Wen; Yanbin Qi; Chen Zhang; Guodong Li; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2025)

Facile blending modification and high-voltage activation strategy enabled long-cycle performance of single crystalline nickel-rich cathode materials - Honglei Liu; Yong Wu; Deli Li; Chengzhi Hu; Lei Zou; Tao Xu; Qiang Wang; Weijian Tang; Dongxu Liu; Ranlin Dong; Ru Song; Zeheng Yang; et al. (Chemical Engineering Journal, 2025)

Overcoming the bottleneck in one-electron reduction of CO2 with mechanical energy-driven triboelectric plasma-enabled catalysis - Qinglong Ru; Bao Zhang; Sumin Li; Jiao Wang; Wei Jiang; Nannan Liu; Hui Hu; Yongcui Yang; Taifeng Liu; Qianhong Gao; Yifei Zhu; Yu Jia; et al. (Chemical Engineering Journal, 2025)

Construction and optimization of low carbon-to-nitrogen ratio-adapted Chlorococcum-Bacteria symbiosis for energy-efficient wastewater remediation - Ru Yan; Han Ji; Zhuo-Chao Liu; Mei-Qi Ren; Shuai Wang; Li-Ming Yang; Dan Cui (Bioresource Technology, 2025)

A new combined model for forecasting geomagnetic variation - Chao Niu; Yi-wei Wei; Xi-hai Li; Hong-ru Li; Xiao-niu Zeng; Ji-hao Liu; Ai-min Du (Applied Geophysics, 2025)

Collision Avoidance of Multi-UUV Systems Based on Deep Reinforcement Learning in Complex Marine Environments - Fuyu Cao; Hongli Xu; Jingyu Ru; Zhengqi Li; Haopeng Zhang; Hao Liu (Journal of Marine Science and Engineering, 2025)
For multiple unmanned underwater vehicles (UUVs) systems, obstacle avoidance during cooperative operation in complex marine environments remains a challenging issue. Recent studies demonstrate the effectiveness of deep reinforcement learning (DRL) for obstacle avoidance in unknown marine environments. However, existing methods struggle in marine environments with complex non-convex obstacles, especially during multi-UUV cooperative operation, as they typically simplify environmental obstacles to convex shapes with sparse distributions and ignore the dynamic coupling between cooperative operation and collision avoidance. To address these limitations, we propose a centralized training with decentralized execution framework with a novel multi-agent dynamic encoder based on an efficient self-attention mechanism. The framework, to our knowledge, is the first to dynamically process observations from an arbitrary number of neighbors that effectively addresses multi-UUV collision avoidance in marine environments with complex non-convex obstacles while satisfying additional constraints derived from cooperative operation. Experimental results show that the proposed method effectively avoids obstacles and satisfies cooperative constraints in both simulated and real-world scenarios with complex non-convex obstacles. Our method outperforms typical collision avoidance baselines and enables policy transfer from simulation to real-world scenarios without additional training, demonstrating practical application potential.

Orchard variable rate spraying method and experimental study based on multidimensional prescription maps - Chenming Hu; Yu Ru; Shuping Fang; Zifan Rong; Hongping Zhou; Xianghai Yan; Mengnan Liu (Computers and Electronics in Agriculture, 2025)

Avian reovirus induces autophagy-mediated cargo of progeny viruses to extracellular vesicles and enhancement of virus release - Chao-Yu Hsu; Wei-Ru Huang; I.-Hsun Chiang; Jyun-Yi Li; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

Oncolytic avian reovirus regulates the TLR3-IRF3-IFN-γ-JAK-STAT1 and TLR3-NF-κB-IFN-γ-JAK-STAT1 pathways inducing autophagy in murine melanoma cells - Chao-Yu Hsu; Zi-Yang Lo; Yi-Ying Wu; Wei-Ru Huang; Tz-Chuen Ju; Kuo-Pin Chuang; Lon-Fye Lye; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

UGPase: A novel molecule that regulates LPS synthesis, virulence, and immunogenicity of Brucella melitensis - Si Chen; Yuxin Liu; Yang Gao; Dong Zhang; Ru Zhang; Fei Tu; Nan Li; Qingkui Jiang; Linna Liu; Yanling Yang (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Flavonoids and butanolides from the bark of Machilus robusta and their bioactivities - Rui-Qi Liu; Shan-Shan Ling; Xian-Da Hu; Bing Peng; Yan-Ru Li (Phytochemistry Letters, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

Tracing anthropogenic imprints on polybrominated and polychlorinated dibenzo-p-dioxin/furans in soil: A comprehensive field study in an urban agglomeration of China - Ming-Yang Liu; Hui-Ru Li; Ping-An Peng; Ai-Min Song; Yang Li; Fei-Xiang Xie; Yong-Hong Zhang; Jian-Fang Hu (Environmental Research, 2025)

Nepenthes-inspired liquid-infused membranes with capillary-enhanced thermal efficiency anti-scaling, and anti-fouling for direct contact membrane distillation - Rishun Li; Ru Liu; Volker Abetz; Lizhi Zhao; Zhenzhen Zhang; Xiaoniu Yang (Chemical Engineering Journal, 2025)

Transcriptome-Wide Sequencing Identifies Non-Coding RNAs and Their Competing Endogenous RNA Networks During the Stages of pPGCLCs-Induced Differentiation - Zhan-Zhong Qiao; Qiu-Yuan Pang; Chang Xu; Xin-Lei Feng; Ming-Xin Zang; Ping Wang; Ying Zhang; Yong-Chao Liu; Qian-Ru Han; Wei Shen; Wei Ge; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2025)

TISCalling: leveraging machine learning to identify translational initiation sites in plants and viruses - Ming-Ren Yen; Ya-Ru Li; Chia-Yi Cheng; Ting-Ying Wu; Ming-Jung Liu (Plant Molecular Biology, 2025)

Intermittent Drought Priming Improves Photosynthesis, Water Status, Antioxidant Capacity, and Tolerance to Drought Stress in Winter Wheat - Chen Ru; Yuxuan Liu; Xiaotao Hu; Wene Wang (Journal of Plant Growth Regulation, 2025)

Combined genome and transcriptome provides insight into the genetic evolution of an edible halophyte Suaeda salsa adaptation to high salinity - Bing Cui; Ranran Liu; Qiong Yu; Jianrong Guo; Xihua Du; Zixin Chen; Chenyang Li; Tong Wang; Ru Liu; Rui He; Congcong Song; Yue Liu; et al. (Molecular Ecology, 2025)
Suaeda salsa L. is a typical halophyte with high value as a vegetable. Here, we report a 447.98 Mb, chromosomal‐level genome of S. salsa , assembled into nine pseudomolecules (contig N50 = 1.36 Mb) and annotated with 27,927 annotated protein‐coding genes. Most of the assembled S. salsa genome, 58.03%, consists of transposable elements. Some gene families including HKT1 , NHX , SOS and CASP related to salt resistance were significantly amplified. We also observed expansion of genes encoding protein that bind the trace elements Zn, Fe, Cu and Mn, and genes related to flavonoid and α‐linolenic acid metabolism. Many expanded genes were significantly up‐regulated under salinity, which might have contributed to the acquisition of salt tolerance in S. salsa . Transcriptomic data showed that high salinity markedly up‐regulated salt‐resistance related genes, compared to low salinity. Abundant metabolic pathways of secondary metabolites including flavonoid, unsaturated fatty acids and selenocompound were enriched, which indicates that the species is a nutrient‐rich vegetable. Particularly worth mentioning is that there was no significant difference in the numbers of cis ‐elements in the promoters of salt‐related and randomly selected genes in S. salsa when compared with Arabidopsis thaliana , which may affirm that plant salt tolerance is a quantitative rather than a qualitative trait in terms of promoter evolution. Our findings provide deep insight into the adaptation of halophytes to salinity from a genetic evolution perspective.

Spatiotemporal distribution and priority assessment of steroids in the estuarine environment: Implications for environmental risk management - Ru Xu; Nian-Nian Wu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Bing Hong; Shen Yu; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Phylogenomics provides new insight into the phylogeny and diversification of Asian Lappula (Boraginaceae) - Dan-Hui Liu; Quan-Ru Liu; Komiljon Sh. Tojibaev; Alexander P. Sukhorukov; Hafiz Muhammad Wariss; Yue Zhao; Lei Yang; Wen-Jun Li (Molecular Phylogenetics and Evolution, 2025)

Transfer patterns of human blood to follicular fluid of per- and polyfluoroalkyl substances with distinct molecular structures and physico-chemical properties - Yun-Ting Zhang; Michael S. Bloom; Yang Zhou; Saif Ur Rehman; Chu Chu; Kun Zhao; Biao Yin; Zhong Lin; Yuan-Yuan Fan; Li-Zi Lin; Ru-Qing Liu; Weihong Tan; et al. (Journal of Hazardous Materials, 2025)

Comprehensive molecular biology and metabolomics analysis reveal the changes on muscle quality of Megalobrama amblycephala exposure to ammonia nitrogen during transportation - Ling Peng; Ziaur Rahman; Yuanyong Tian; Tao Yin; Shanbai Xiong; Juan You; Ru Liu; Lan Wang; Qilin Huang; Huawei Ma (Food Research International, 2025)

Designing fish scale gelatin microgel network by moderate pre-dispersion: A new attempt to construct a bigels-based pig fat analog - Yanlei Gao; Qing Xiong; Ruonan Li; Huixian Yang; Ru Liu (Food Hydrocolloids, 2025)

Schiff base crosslinking based dialdehyde-chitosan/gelatin/tea polyphenol electrospun nanofibrous membranes with excellent antibacterial and antioxidant activity for food packaging - Yu Ma; Ru Tian; Yudong Song; Mengxiao Liu; Jie Li; Zhichun Bi; Hui Huang; Yongxin Li (Food Packaging and Shelf Life, 2025)

Fluorinated Amino-acid-doped microarray-based biochemical patches Deciphers in-situ spatiotemporal dynamics amidst intricate Bio-Interfaces - Ru Zhang; Ran Duan; Deqi Yang; Haofan Wu; Bingfang Wang; Zhiqiang Chang; Jing Chen; Jing Dai; Yingying Lv; Yi Liu; Menahem Y. Rotenberg; Dandan Liang; et al. (Chemical Engineering Journal, 2025)

Zirconium phosphate nanonetworks for enhanced soft tissue integration and antibacterial performance of zirconia implant abutments - Yingyue Sun; Qihong Zhang; Shuyi Wu; Kendrick Hii Ru Yie; Lei Cai; Yinyan Zhang; Wen Si; Huan Cheng; Zijian Zheng; Peng Gao; Jinsong Liu; Lei Lu (Chemical Engineering Journal, 2025)

Degradation-Resistant Biochar Improves Soil Organic Carbon Storage: Promoting Autotrophic Metabolism & Increasing Refractory Organic Carbon - Han Tang; Jiajun Hu; Bu Li; Yundong Liu; Wang Kai Tong; Mei Ru Yue; Jia Wang; Wenjuan Wang; Min-tian Gao; Nan Liu; Jixiang Li (Bioresource Technology, 2025)

Engineering an Ag2Se@PANi core–shell nanozymes – Klebsiella pasteurii hybrid system with enhanced ammonia synthesis - Meng-Xin Zhao; Si-Ru Chen; Bo Hu; Hao Chen; Ya-Xuan Xiao; Ting-Ting Liu; Shan-Shan Hu; Su-Fang Qin; Xuee Wu; Le-Xing You; Feng Zhao (Bioresource Technology, 2025)

Four saprobic species associated with Mahonia in Guizhou Province, China - Ya-Ru Sun; Kevin D. Hyde; Ning-Guo Liu; Fatimah O. Al-Otibi; Yong Wang; Ruvishika S. Jayawardena (Mycological Progress, 2025)

Characteristic noise of offshore wind turbine impacts the behavior and muscle physiology of sea cucumber Apostichopus japonicus - Xiaochen Cheng; Zhaoming Gao; Shuai Liu; Yongchao Hu; Wanyi Li; Libin Zhang; Xiaoshang Ru (Marine Pollution Bulletin, 2025)

Calcium phytate cross-linked polysaccharide hydrogels for selective removal of U(VI) from tailings wastewater - Lan Lei; Rui Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Xin Liu; Tie-Ying Shi; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Water Research, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Enhancement mechanism of residue Gd (III)-induced in anaerobic ammonia oxidation for nitrogen removal from rare earth tailings leachate - Xiangyi Deng; Ting Zeng; Shengnan Huang; Chunqiao Xiao; Liu Liu; Wanqiang Dong; Zhenyue Zhang; Ru’an Chi (Journal of Environmental Chemical Engineering, 2025)

Surface and interface modification of biochar based on thermal nanobubble water - Mei Ru Yue; Jia Bing Liu; Piao Yi Jiang; Wang Kai Tong; Han Tang; Jia Wang; Wenjuan Wang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Chemical Engineering, 2025)

Floated Bi4Ti3O12@MoS2 p-n heterojunction anti-fouling hydrogels for efficient seawater purification - Ying Liu; Bingyan Ni; Ruotong Ru; Linlin Zhang; Hongfei Sun; Jianjun Liao; Cheng Li; Dexin Wang; Xiaodong Zhang; Wei Zhou (Journal of Environmental Chemical Engineering, 2025)

Advancements in emerging non-thermal preservation techniques for aquatic products: A comprehensive review of mechanisms, applications, and future directions - Zhijun Yang; Qing Xiong; Tao Yin; Juan You; Shanbai Xiong; Ru Liu (Innovative Food Science & Emerging Technologies, 2025)

Fabrication, characterization, and application in 3D printing of high internal phase emulsion stabilized by alkaline thermal treated pea protein and pectin complex - Ru Zhao; Boxue Xia; Abbas Khan; Yanjiao Chang; Xin Guo; Yaxuan Liu; Xin Huang; Cuina Wang (Food Research International, 2025)

Effects of modified KGM on the gelling capability of fish protein: Novel insights into hooking effect - Ziaur Rahman; Sijin Zhang; Arsalan Khan; Juan You; Ru Liu; Qilin Huang; Huawei Ma; Soottawat Benjakul; Tao Yin (Food Chemistry, 2025)

Structural evaluation and formation regularities of garlic clove-like meat in prefabricated grass carp - Qin Yang; Junhong Xie; Yuting Zhang; Yiling Tian; Liang Song; Yongqiang Zhao; Jian Xiong; Ru Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Co-encapsulation and stability evaluation of myricetin and epicatechin in the oxidized starch-coated edible dock protein hydrogels - Si-Qi Li; Zhi-Yuan Yang; Ming Yang; Wei Wang; Yu-Ru Wu; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2025)

Overcrowded steric engineering of through-space interactions for anti-quenching multi-resonance TADF materials - Ru-Jia Wang; Fan Zheng; Jie Hu; Yu-Lan Wu; Xiao-Long Liu; Jia-Xiong Chen; Longjiang Xing; Qiao-Er Wu; Yanping Huo; Wen-Cheng Chen (Chemical Engineering Journal, 2025)

Superior ammonia nitrogen adsorption capacity and reusability biochar microsphere applied in live fish transportation - Ling Peng; Tao Yin; Zhiyong Song; Shanbai Xiong; Ru Liu; Juan You; Qiling Huang (Chemical Engineering Journal, 2025)

Efficient catalyst-free CO2 reduction by CO2— radical anions at gas–liquid interface under ambient conditions - Nannan Liu; Qinglong Ru; Wei Jiang; Hui Hu; Yongcui Yang; Kailan Ma; Zuliang Du; Yu Jia; Xiaojing Yang; Bao Zhang; Gang Cheng (Chemical Engineering Journal, 2025)

Effects of combined exposure to polyethylene and oxidized polycyclic aromatic hydrocarbons on growth, development, and neurobehavior in Zebrafish - Yu Liu; Yujun Ning; Yi Jiang; Yiquan Ou; Xiaobing Chen; Chiting Zhong; Ru Wang; Zhibo Zhang; Kongfan Wang; Dingxin Long; Weichao Zhao (Aquatic Toxicology, 2025)

Study on the mechanical genesis mechanism and reservoir-controlled pattern of strike-slip fault pressure-ridge structures in the Shunbei Area, Tarim Basin - Zhixing Ru; Xinjing Yu; Yingtao Li; Huabiao Qiu; Shuang Liu (Carbonates and Evaporites, 2025)

Using unmanned aerial vehicle monitoring for the landslide and dammed lake: a case study of the Xiuluan area in Taiwan - Che-Hsin Liu; Jui-Yi Ho; Horn-Ru Liao; Shih-Chiang Lee; Naoki Sakai; Chen-Yu Chen; Chih-Hsin Chang (Bulletin of Engineering Geology and the Environment, 2025)

Mathematical modelling the variation of sodium chloride (NaCl) diffusion behavior and quality of grass carp fillets during salting - Kun Yang; Runlin Wu; Ramy M. Khoder; Shanbai Xiong; Ru Liu (Journal of Food Engineering, 2025)

Impact of freezing technologies on the quality of catfish (Ictalurus punctatus) fillets: Insights from protein properties and ice crystal analysis - Huiyuan Jin; Yajin Zhang; Miao Shi; Tao Yin; Ru Liu; Youming Liu; Juan You (International Journal of Refrigeration, 2025)

Recent progress in protein-based high internal-phase Pickering emulsions: Composition, stabilization, applications, and future trends - Wei Liang; Xiaofeng Zhan; Pengkai Wang; Chuan Li; Lu Zhang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Research International, 2025)

Changes in physicochemical properties of snakehead fish slices incorporated with nano fish bones during freeze-thaw cycles: Effects of marinating methods - Ziaur Rahman; Yajin Zhang; Abroo Tabasum; Jirawat Yongsawatdigul; Qilin Huang; Shanbai Xiong; Juan You; Ru Liu; Tao Yin (Food Chemistry, 2025)

Chlorinated paraffins exposure in particulate matter increase the risk of attention-deficit/hyperactivity disorder symptoms in children and adolescents - Wan-Ting He; Jing-Wen Huang; Yun-Ting Zhang; Edwin Trevathan; Zhengmin Qian; Ri'enna Boyd; Michael Elliott; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Guang-Hui Dong (Environmental Pollution, 2025)

SERS-ATB: A comprehensive database server for antibiotic SERS spectral visualization and deep-learning identification - Quan Yuan; Jia-Wei Tang; Jie Chen; Yi-Wen Liao; Wen-Wen Zhang; Xin-Ru Wen; Xin Liu; Hui-Jin Chen; Liang Wang (Environmental Pollution, 2025)

Role of earthworms and their excretion products in reducing antimicrobial resistance and putative pathogens during vermicomposting - Ning Liu; David W. Graham; Yi Zhao; Xiao-Ru Yang; Gang Li; Yong-Guan Zhu (Chemical Engineering Journal, 2025)

Energy storage in Hf0.5Zr0.5O2(3):ZrO2(12)-based films with heterostructures formed at different deposition temperatures - Haiyan Chen; Chengfeng Jiang; Lei Liu; Ru Guo; Zhongna Yan; Chuanchang Li; Dou Zhang (Chemical Engineering Journal, 2025)

Enhancing color conversion of perovskite quantum dot-based micro-light-emitting diodes via electrochemical etching and flow chemistry system - Wen-Tse Huang; Yen-Huei Lin; Po-Yi Tu; Loan Thi Ngo; Wei-Cheng Chen; Kai-Ling Liang; Yen-Hsiang Fang; Chaochin Su; Ru-Shi Liu (Chemical Engineering Journal, 2025)

Interface selectivity-based biochar: Directional evolution of properties, application & carbon neutralization evaluation - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Mei Ru Yue; Yun Dong Liu; Bu Li; Jia Jie Zou; Jia Wang; Han Tang; Min-tian Gao; Yucang Liang; Wenjuan Wang; et al. (Chemical Engineering Journal, 2025)

Targeted restoration of endothelial hypoxic response prevents angiogenic bone loss against liver fibrosis - Nan Zhang; Sheng-Feng Bai; Jia-Ning Liu; Xin Huang; Lu Liu; Yu-Ru Gao; Si-Qi Ying; Chen-Xi Zheng; Hao-Kun Xu; Ji Chen; Xiao Lei; Yu-Bo-Han Zhang; et al. (Chemical Engineering Journal, 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Erratum to: CXCL16 promotes proliferation of head and neck squamous cell carcinoma by regulating GPX1-mediated antioxidant levels - Ru He; Hongyi Jiang; Chengchi Zhang; Yuan Chen; Wenshun Liu; Xinyue Deng; Xiaozheng Zhu; Yunye Liu; Chuanming Zheng; Yining Zhang; Chengying Shao; Yanting Duan; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Novel screening of molecular markers reveals genetic basis for heterosis in hybrids from red crucian carp and white crucian carp - He Zhang; Ru Li; Yun Zeng; Jun Wang; Zhizhi Liu; Yi Zhou; Chenghui Wang; Dong Liu (Aquaculture, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Molecular mechanisms of ascorbic acid affected by ozone in fresh-cut kiwifruit: Insights from salicylic acid synthesis and signal transduction - Yajing Wang; Jingxuan Ma; Tianyu Wang; Liyan Rong; Yingqi Zhao; Shuyue Zhang; Zixuan Liu; Ru Wang; Zhaoxia Wu (Postharvest Biology and Technology, 2025)

Quantitational life cycle assessment of Effluent-Energy-Carbon synergies and trade-offs in drinking water treatment plant upgrades - Yumeng Zhang; Zongqi Ding; Zewei Lin; Shoubin Chen; Shunjian Cheng; Kaiming Peng; Ru Guo; Xiangfeng Huang; Chen Cai; Jia Liu (Journal of Water Process Engineering, 2025)

Repeated measurements of urinary bisphenol A and its analogues in relation to sperm DNA damage - Yang-Juan Li; A-Xue Liu; Jia-Yue Zeng; Yu Miao; Min Zhang; Xiao-Ying Liu; Wu Yang; Ru-Cheng Li; Jin-Qin Zhu; Chang-Jiang Liu; Qiang Zeng (Journal of Hazardous Materials, 2025)

Metallization-mediated charge transfer in cocrystals for efficient photocatalytic decontamination of mustard-gas simulant - Li Zhang; Xiao-Lin Liu; Chen Sun; Yu-Ting Luo; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2025)

Investigation on the synergistic effects and thermokinetic analyses during co-combustion of corn stalk and polyethylene plastic: Effect of heating rate and placement method - Mengjie Liu; Bin Han; Jin Bai; Jiayao Ru; Xuetao Wang; Lili Xing; Haojie Li; Siyu Lv; Aopeng Gao; Yiming Wang; Lingxue Kong; Zongqing Bai; et al. (Fuel, 2025)

Preparation of two-step cold-set low oleogel-microgels phase bigels and its application in tender fish balls: Pork fat substitute and cryoprotectant - Yanlei Gao; Qing Xiong; Qilin Huang; Yang Hu; Ru Liu (Food Research International, 2025)

Generation characteristics of polybrominated and polychlorinated dibenzo-p-dioxins/furans (PBDD/Fs and PCDD/Fs) under varying incineration conditions of municipal solid waste - Ming-Yang Liu; Ai-Min Song; Hui-Ru Li; Sheng-Tao Ma; Ren-Jie Shang; Yao Xiao; Ping-An Peng; Jian-Fang Hu (Environmental Pollution, 2025)

Granular ferric hydroxide adsorption as a pretreatment to achieve phosphorus reclamation and high water-recovery wastewater effluent desalination - Hao Huang; Ru Liu; Mangut Sunday Jikmyan; Shihong Lin; Oded Nir; Roy Bernstein (Chemical Engineering Journal, 2025)

Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Metal-organic coordinated self-assembled nanomedicine for enhanced cuproptosis-mediated chemo-photo-chemodynamic synergistic therapy of non-small cell lung cancer - Ru-Gui Liu; Rui-Rui Zhao; Zi-Wei Yu; Feng-Juan Liu; Chun-Zhao Liu; Xiao Wu (Chemical Engineering Journal, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Protective role of Tongxinluo in mitigating myocardial fibrosis in mice with acute myocardial infarction via neuregulin-1 upregulation and Inhibition of endothelium-interstitial transition - Zhen Li; Yu-jie Yin; Ya-ru Wei; Yi Liu; Ning-xin Han; Xiao-qi Wang; Yuan-jie Hao; Ya-fen Wang; Yun-long Hou; Zhen-hua Jia (Journal of Molecular Histology, 2025)

Relaxin-like gonad-stimulating peptide promotes gamete maturation and spawning in the sea cucumber Apostichopus japonicus - Jiaze Wang; Zhaoming Gao; Shuai Liu; Yongchao Hu; Libin Zhang; Beini Deng; Zhenxia Sha; Xiaoshang Ru (Animal Reproduction Science, 2025)

Exploring the multifaceted roles of histone deacetylase inhibitor vorinostat in the cell growth, mycelial morphology, pigments, and citrinin biosynthesis of Monascus purpureus - Run-Ya Li; Chen-Yu Zhang; Shaoxiang Xiao; Xin-Yi Liu; Ru-Xue Li; Jing Li; Hao Li; Jun Liu (Archives of Microbiology, 2025)

Characterizing temporal trends and meteorological influences on ozone pollution in Shenyang region (2018–2021) - Shuangshuang Wu; Le Hou; Xuebin Sun; Min Liu; Nan Wang; Ru Li (Air Quality, Atmosphere & Health, 2025)

Characterization of the gut microbiota in drug abuse: prediction, prevention, and personalized medicine to benefit affected populations - Xin Wang; Ya-Jie Yu; Cai Liao; Xiao-Ru Liu; Rui Yu; Yun Wang (EPMA Journal, 2025)

Photoelectrocatalytic Coupling of Chlorine Radicals Enhances Sulfonamide Antibiotic Degradation in Saline-Alkaline Waters in Cold-Water Fish Aquaculture - Qikai Liu; Yang Liu; Yaqi Mao; Ru Li; Yujie Jiao; Jiali Lei; Fenzhen Zhang (Fishes, 2025)
The degradation of organic matter using TiO2 nanotube photocatalytic technology is limited by the short lifetime and diffusion radius of the generated hydroxyl radicals, decreasing the removal efficiency. This study developed a chlorine radical-coupled photoelectrocatalytic system, significantly enhancing the performance of TiO2 nanotube arrays in removing sulfonamide antibiotics (SAs) from cold-water aquaculture systems. The highest degradation rates were observed at 5 mM NaCl and 15 mM NaNO3. When SA concentrations were 0.1–10 mg/L, degradation efficiency decreased with higher initial concentrations. The best degradation was achieved at an initial pH of 3 for SA. Humic acid and sodium acetate, natural organic matter in the water column, served as low-concentration promoters and high-concentration inhibitors. In our study, three degradation intermediates were identified, and hydrolysis and nitration reactions are proposed as the primary pathways for SA degradation. We confirmed that oxygen radicals play a major role in this system. Furthermore, toxicology experiments revealed the weakening of the toxicity of the degraded products. This study provides an efficient method for treating organic matter in cold-water fish culture water in chloride-containing saline and alkaline waters.

Location optimization of unmanned aerial vehicle (UAV) drone port for coastal zone management: The case of Guangdong coastal zone in China - Jia Sun; Sijing Shu; Hongda Hu; Yingbin Deng; Zhao Li; Shengnan Zhou; Yue Liu; Minwen Dang; Wumeng Huang; Zhiwei Hou; Xiaoling Yin; Ru Zhang; et al. (Ocean & Coastal Management, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

A dual-functional vertical oriented C/TiO2 nanotubes for superior solar evaporation of sewage treatment - Lifen Su; Haoming Xie; Xiaoyu Liu; Bin Yang; Jibin Miao; Ru Xia; Jiasheng Qian; Lei Miao (Journal of Water Process Engineering, 2025)

Efficient fluconazole degradation by activating peroxymonosulfate with LDH-coated nickel foam: Synergism of radical and non-radical pathways - Xiang-Yang Li; Ling-Xi Zhao; Meng Xie; Ning Liu; Xiang-Feng Chen; Ru-Song Zhao (Journal of Water Process Engineering, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Study of the brittleness properties of granites under thermal and mechanical action through a new brittleness evaluation method - Huijun Lu; Ru Zhang; Li Ren; Anlin Zhang; Zidong Fan; Kun Xiao; Wei Liu; Tao Huang (Geothermics, 2025)

Effect of cinnamaldehyde and tannic acid nano-emulsions on meat quality and protein oxidation during cold storage - Ramy M. Khoder; Xinqun Deng; Liangzi Zhang; Qilin Huang; Juan You; Ru Liu; Huawei Ma; Tao Yin (Food Packaging and Shelf Life, 2025)

Efficient adsorption behavior of Fe-based ternary magnetic LDHs for naphthalene acetic acid: Role of Fe element - Ning Liu; Ti-Bo Fang; Ling-Xi Zhao; Na Li; Xiang-Feng Chen; Ru-Song Zhao (Environmental Research, 2025)

Is there an association between eye-level greenness and childhood hypertension using street view? Findings from the Seven Northeastern Cities study in China - Huang-Min Yang; Jing-Yao Wang; Cheng Li; Ya-Qin Zhang; Ruoyu Wang; Qi Yang; Yao Yao; Zilong Wang; Shu-Li Xu; He-Hai Huang; Qian-Sheng Hu; Ru-Qing Liu; et al. (Environmental Research, 2025)

Dissimilatory nitrate reduction to ammonium driven by different electron donors: Mechanisms, recent advances, and future perspectives - Wan-Ru Wen; Tian-Chen Liu; Sheng-Qiang Fan; Xin Tan; Yang Lu; De-Feng Xing; Bing-Feng Liu; Nan-Qi Ren; Guo-Jun Xie (Chemical Engineering Journal, 2025)

Modeling Li isotope fractionation during the coal-combustion process and evaluating its capacity as an environmental tracer - Jing Chen; Yilin Xiao; Jack Geary Murphy; Dong-Bo Tan; Yang-Yang Wang; Biao Fu; Guijian Liu; Ru-Wei Wang; Xiaoxia Wang; Feng-Tai Tong (Chemical Geology, 2025)

Toxicokinetics and reproductive toxicity of maternal bisphenol AF exposure during gestation in offspring of Sprague Dawley rats - Yaxuan Zhu; Xiuxiang Liu; Xiuying Liu; Yijiao Shi; Huaxin Li; Shaoguo Ru; Hua Tian (Chemico-Biological Interactions, 2025)

Drug–drug interaction of phenytoin sodium and methylprednisolone on voriconazole: a population pharmacokinetic model in children with thalassemia undergoing allogeneic hematopoietic stem cell transplantation - Yun Wu; Lu-lu Niu; Ya-yun Ling; Si-ru Zhou; Tian-min Huang; Jian-ying Qi; Dong-ni Wu; Rong-da Cai; Ting-qing Wu; Yang Xiao; Taotao Liu (European Journal of Clinical Pharmacology, 2025)

Glycosylation on the Antifreeze and Antioxidant Capacities of Tilapia Gelatin Hydrolysates - Ying Liu; Zongcai Tu; Qiuyu Lu; Shengnan Zhan; Ru Jia; Zhaohui Qiao; Huamao Wei; Tao Huang (Fishes, 2025)
The antifreeze and antioxidant capacities of tilapia (Oreochromis mossambicus) gelatin hydrolysates were investigated, after glycosylation with saccharides of varying molecular weights, to enhance their functional properties to widen its commercial application in frozen aquatic products. Glycosylation was conducted by mixing gelatin hydrolysates with ribose, glucose, maltose, and dextran (20 kDa) at a 1:1 mass ratio; the glycosylation products had a pH of 10 and were incubated at 80 °C for 1 h. The results showed that the glycosylation degree ranked as: ribose > glucose > maltose > dextran. The mass spectrometry analysis showed that 17, 32, and 5 glycosylation sites were identified for ribose, glucose, and maltose, respectively, suggesting a molecular weight-dependent effect. Spectroscopic analyses, including ultraviolet and infrared spectroscopy, revealed that the gelatin hydrolysate structure was expanded, with chromophores in hydrophilic environments; a blue shift in the amide A and II bands confirmed that the amino group was involved. Fluorescence spectroscopy showed conformational changes with a red shift at 303.4 nm and a reduction in intensity. Antifreeze activity, such as catalase freezing protection and shrimp surimi protein stability, and antioxidant activity, including radical scavenging and metal ion chelation, were significantly improved. Ribose exhibited the strongest effects, followed by maltose and glucose. These results demonstrate the potential of glycosylation to improve gelatin hydrolysates for functional applications.

The effects of water flow velocity and odor release frequency on the odor-tracking behavior of swimming crabs (Portunus trituberculatus) - Ru Wang; Xin Wang; Qihang Liang; Teng Jiang; Liang Yue; Fang Wang; Dapeng Liu (Aquaculture, 2025)

Two new phenolic glycosides from the rhizomes of Paris yunnanensis - Yu-Rui Xie; Shan-Shan Ling; Yan-Xi Li; Mei-Ru Wang; Hai-Yang Liu (Phytochemistry Letters, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Insights into the source characterization, risk assessment and ozone formation sensitivity of ambient VOCs at an urban site in the Fenwei Plain, China - Huan Zhang; Chen Zhang; Shasha Liu; Shijie Yin; Siqing Zhang; Hongji Zhu; Fengyu Yan; Hua Yang; Xiaoning Ru; Xingang Liu (Journal of Hazardous Materials, 2025)

Effect of vacuum frying on the structure and bioactivity of proanthocyanidins in Chinese quince (Chaenomeles sinensis Koehne) fruit - Yu Lou; Xu Fang; Zi-Cheng Yang; Jia-Lin Fei; Yu-Ru Feng; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma; Xue-De Wang (Food Chemistry, 2025)

Nano fish bone prepared by high-energy media milling extends the shelf life of tofu during cold storage: Unlocking the restriction on water mobility - Ramy M. Khoder; Liangzi Zhang; Qilin Huang; Juan You; Huawei Ma; Tao Yin; Ru Liu (Food Chemistry, 2025)

Efficient adsorption and separation of glyphosate in aqueous solution by amino-functionalized Poly(glycidyl methacrylate) - Qiyu Meng; Yupei Wang; Meng Rong; Huifang Xing; Ru-An Chi; Congmei Chen; Huizhou Liu; Liangrong Yang (Chemical Engineering Journal, 2025)

Global surface eddy mixing ellipses: spatio-temporal variability and machine learning prediction - Tian Jing; Ru Chen; Chuanyu Liu; Chunhua Qiu; Cuicui Zhang; Mei Hong (Frontiers in Marine Science, 2025)
Mesoscale eddy mixing significantly influences ocean circulation and climate system. Coarse-resolution climate models are sensitive to the specification of eddy diffusivity tensor. Mixing ellipses, derived from eddy diffusivity tensor, illustrate mixing geometry, i.e., the magnitude, anisotropy, and dominant direction of eddy mixing. Using satellite altimetry data and the Lagrangian single-particle method, we estimate eddy mixing ellipses across the global surface ocean, revealing substantial spatio-temporal variability. Notably, large mixing ellipses predominantly occur in eddy-rich and energetic ocean regions. We also assessed the predictability of global mixing ellipses using machine learning algorithms, including Spatial Transformer Networks (STN), Convolutional Neural Network (CNN) and Random Forest (RF), with mean-flow and eddy- properties as features. All three models effectively represent and predict spatiotemporal variations, with the STN model, which incorporates an adaptive spatial attention mechanism, outperforming RF and CNN models in predicting mixing anisotropy. Feature importance rankings indicate that eddy velocity magnitude and eddy size are the most significant factors in predicting the major axis and anisotropy. Furthermore, training the models with a 2-year temporal duration, aligned with the El Niño Southern Oscillation (ENSO) timescale, improved predictions in the northern equatorial central Pacific region compared to models trained with a 12-year duration. This resulted in a spatially averaged correlation increase of over 0.5 for predicting the minor axis and anisotropy, along with a reduction of more than 0.15 in the Normalized Root Mean Square Error. These findings highlight the considerable potential of machine learning algorithms in predicting mixing ellipses and parameterizing eddy mixing processes within climate models.

Evaluation on the antibacterial activity of glycyrrhizin against Pseudomonas plecoglossicida in ayu fish (Plecoglossus altivelis) - Fan Tao; Jia-Feng Cao; Yan-Jun Liu; Ru-Yi Chen; Jin-Jin Shi; Chang-Yun Li; Jian-Fei Lu; Guan-Jun Yang; Jiong Chen (Aquaculture, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Self-driven electrochemical system for struvite and energy recovery from digested wastewater: Device optimization strategy and long-term operation - Yi-fan Niu; Ting-ting Dong; Zhi-guo Zhao; Meng-Yu Liu; Ru Wang; Lin-jiang Yuan (Journal of Environmental Management, 2025)

Recycled fish oil and lard: Influences on the textural and structural properties of Surimi Gels - Jingyan Zhang; Ramy M. Khoder; Hong Yang; Tao Yin; Ru Liu; Juan You (Food Structure, 2025)

Impact of lotus seed Starch-EGCG complex on gut microbiota: Structural changes and fermentation effects - Ru Jia; Lu Liu; Wenjing Chen; Wenyu Chen; Xiaoying Wang; Zebin Guo (Food Bioscience, 2025)

Carboxymethyl chitosan-assisted formation of stable soy protein isolate emulsions and their impact on the properties of squid (Dosidicus gigas) surimi gel - Siqi Liu; Zhufen Wang; Wenge Yang; Tao Huang; Jie-Ting Geng; Huamao Wei; Yuanpei Gao; Ru Jia (Food Hydrocolloids, 2025)

SARS-CoV-2 Inhibits Exo-Endocytosis and Enhances Short-Term Depression at a Central Synapse - Jiawei Hu; Yuhan Zhang; Qingzhuo Liu; Jiaqi Hu; Yichen Ru; Lu Zhang; Lixin Xie; Lei Xue (Neuroscience Bulletin, 2025)

CXCL16 promotes proliferation of head and neck squamous cell carcinoma by regulating GPX1-mediated antioxidant levels - Ru He; Hongyi Jiang; Chengchi Zhang; Yuan Chen; Wenshun Liu; Xinyue Deng; Xiaozheng Zhu; Yunye Liu; Chuanming Zheng; Yining Zhang; Chengying Shao; Yanting Duan; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Effects of imidacloprid on Orius similis: assessing growth, development, and reproduction through age-stage two-sex life table analysis under contact and stomach toxicity treatments - Bo Zhang; Yi-Ru Li; Jin-Long Zhang; Guo-Hua Chen; Nian Yang; Ji-Huan Liu; Guo-Ting Yuan; Xiao-Ming Zhang (Journal of Pest Science, 2025)

Automatic and integrated detection of nucleic acid by using a dual-mode thermal controlled digital microfluidic chip - Jiaqi Liao; Chonghao Li; Jiajia Liu; Hao Cheng; Linmin Li; Guixi Tang; Ru Huang; Yating Lu; Siyue Chen; Qian Zhang; Hao Chen; Qinyuan Chen; et al. (Analytica Chimica Acta, 2025)

Adaptive Positioning Control of Multi-Point Moorings with Disturbance Observation Under Input Constraints - Run Lu; Guichen Zhang; Ru Liu; Chaojian Gao; Wei Chen; Huanglong Fu (Journal of Marine Science and Engineering, 2024)
In the presence of dynamic uncertainties, external time-varying disturbances, and limited inputs to the multi-point mooring system (MPMS) of a floating offshore platform (FOP), this paper proposes a robust adaptive dynamic surface (RADS) control method incorporating a disturbance observer. A disturbance observer is designed to estimate the unknown time-varying disturbance and apply feedforward compensation to the control variable. Simultaneously, the adaptive law of the σ-corrected leakage term is employed to estimate the bound of the disturbance observation error, thereby enhancing positioning accuracy. An auxiliary dynamic system (ADS) is then introduced to address input constraints, while the differential explosion problem associated with the traditional inversion method is resolved through the integration of the dynamic surface control (DSC) algorithm. The Lyapunov function is utilized to demonstrate that the controller ensures the consistent ultimate boundedness of all signals within the closed-loop system. Finally, a simulation experiment was conducted based on the eight-point mooring platform of the “Kantan3”, and the positioning accuracy reached 3%, which is higher than the specification requirements of the classification society. The results indicate that the designed controller achieves higher positioning accuracy and improved anti-interference performance and has been put into practical application on “Kantan3”.

Amorphous Solid Dispersions of Glycyrrhetinic Acid: Using Soluplus, PVP, and PVPVA as the Polymer Matrix to Enhance Solubility, Bioavailability, and Stability - Meng-yu Zhao; Xian-bao Shi; Jin-hua Chang; Ru-xing Wang; Jian-yu Zhou; Pei Liu (AAPS PharmSciTech, 2024)

Heavy metal emissions from on-road vehicles in Xia-Zhang-Quan metropolitan area in southeastern China from 2015 to 2060: impact of vehicle electrification - Zhe-Nan Wen; Qi-Yu Miao; Jiang-Ru Chen; Shui-Ping Wu; Li-Xiong He; Bing-Qi Jiang; Yi-Jing Liu; Zhi Huang (Environmental Science and Pollution Research, 2024)

A comprehensive unraveling of the mystery of reduced-salt surimi gels: From molecular mechanism to future prospects - Qiqi Li; Shengjun Chen; Juan You; Yang Hu; Tao Yin; Ru Liu (Trends in Food Science & Technology, 2024)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Phase transformation of schwertmannite changes microbial iron and sulfate-reducing processes in flooded paddy soil and decreases arsenic accumulation in rice (Oryza sativa L.) - Ru Wang; Xinxin Wang; Hua Li; Xiaomeng Wang; Zengping Ning; Chengshuai Liu; Lixiang Zhou; Guanyu Zheng (Soil Biology and Biochemistry, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

A novel hybrid variable cross layer-based machine learning model improves the accuracy and interpretation of energy intensity prediction of wastewater treatment plant - Yucheng Li; Chen Cai; Erwu Liu; Xiaofeng Lin; Ying Zhang; Hongjing Chen; Zhongqing Wei; Xiangfeng Huang; Ru Guo; Kaiming Peng; Jia Liu (Journal of Environmental Management, 2024)

Ovalbumin/sodium alginate Pickering emulsion: Structural characteristics and its contribution to enhancing the gel properties of Hairtail (Trichiurus haumela) surimi - Zhufen Wang; Siqi Liu; Wenge Yang; Jie-Ting Geng; Tao Huang; Huamao Wei; Zhaohui Qiao; Ru Jia (Food Chemistry, 2024)

Formation and kinetic analysis of AGEs in Pacific white shrimp during frying - Runlin Wu; Xia Mou; Shiyuan Dong; Ramy M. Khoder; Shanbai Xiong; Ru Liu (Food Chemistry, 2024)

Uncovering the freezing energy release of salted grass carp (Ctenopharyngodon idella) flesh: Effects of water state and protein structure on the thermal properties - Yajin Zhang; Shanbai Xiong; Tao Yin; Ru Liu; Ziaur Rahman; Cuie Tang; Hui Hong; Juan You (Food Chemistry, 2024)

The impact of the addition of vitamin C, NaCl, clove oil on the muscle of live blunt-snout bream during transportation - Yu Chen; Ramy M. Khoder; Jun Mei; Hong Yang; Qilin Huang; Juan You; Tao Yin; Ru Liu (Food Bioscience, 2024)

The formation of protein coronas and its effect on the quercetin-edible dock protein nanoparticles - Yu-Ru Wu; Qian Zhou; Jing Li; Wei Wang; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2024)

Zebrafish FKBP5 facilitates apoptosis and SVCV propagation by suppressing NF-κB signaling pathway - Zijia Yin; Hongying Zhang; Kaiwen Zhao; Yulong Liu; Ru Guo; Pengxia Xu; Guannan Zhao; Menglei Hu; Chengyu Hu; Xiaowen Xu (Fish & Shellfish Immunology, 2024)

Recent advances in methane and hydrogen production from lignocellulosic degradation with anaerobic fungi - Jinsong Liang; Shiqi Liu; Zhangping Du; Ru Zhang; Longyi Lv; Li Sun; Mohammad Nabi; Guangming Zhang; Panyue Zhang (Bioresource Technology, 2024)

A novel heat recovery VRF system: Principle and cooling performance analysis - Shurong Liu; Tianchan Yu; Baolong Wang; Hongmei Lyu; Ru Gao; Wenxing Shi (Building and Environment, 2024)

Effect of Bacillus subtilis Supplemented Diet on Broiler’s Intestinal Microbiota and TLRs Gene Expression - Salman Khan; Anam Khalid; Ru Yang; Fatima Khalid; Muhammad Hamza Zahid; Haozhe Liu; Yunhua Zhang; Zaigui Wang (Probiotics and Antimicrobial Proteins, 2024)

Post translational modifications of connexin 43 in ventricular arrhythmias after myocardial infarction - Fan Yang; Xiao-Lu Zhang; Huan-Huan Liu; Ling-Ling Qian; Ru-Xing Wang (Molecular Biology Reports, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Abnormal Changes of IL3/IL3R and Its Downstream Signaling Pathways in the Prion-Infected Cell Line and in the Brains of Scrapie-Infected Rodents - Xiao-Xi Jia; Cao Chen; Chao Hu; Zhi-Yue Chao; Wei-Wei Zhang; Yue-Zhang Wu; Qin Fan; Ru-Han A; Xin Liu; Kang Xiao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2024)

MiR-3571 modulates traumatic brain injury by regulating the PI3K/AKT signaling pathway via Fbxo31 - Yang Zhang; Zongying He; Qiongfang Hu; Huali Liu; Rongai Wen; Na Ru; Jinghua Yu; Shaokun Lv; Rui Tao (Cell Biochemistry and Biophysics, 2024)

Classification method of infrasound events based on the MVIDA algorithm and MS-SE-ResNet - Xiao-Feng Tan; Xi-Hai Li; Chao Niu; Xiao-Niu Zeng; Hong-Ru Li; Tian-You Liu (Applied Geophysics, 2024)

Effects of Hydroxypropyl Distarch Phosphate on Surimi Gel Properties Under ’Setting–Freezing–Reheating’ Procedure During Frozen Storage - Shutong Zhang; Min Mao; Xinxin Zhang; Zhufen Wang; Siqi Liu; Yuanpei Gao; Wenge Yang; Ru Jia (Journal of Aquatic Food Product Technology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Experimental study on the influence of particle morphology on compression characteristics of coral sand in South China Sea - Ru Qu; Cheng-hao Ma; Chang-qi Zhu; Hai-feng Liu (Ocean Engineering, 2024)

Yeast culture enhances long-term fermentation of corn straw by ruminal microbes for volatile fatty acid production: Performance and mechanism - Jinsong Liang; Shiqi Liu; Ru Zhang; Jianning Chang; Longyi Lv; Mohammad Nabi; Guangming Zhang; Panyue Zhang (Journal of Environmental Management, 2024)

Proteomic analysis revealed the deterioration of surimi gelling capability to fish stress during transportation - Zhiying Xiang; Tao Yin; Zenan Huang; Ziaur Rahman; Yongsawatdigul Jirawat; Tanye Xu; Qilin Huang; Juan You; Ru Liu; Hong Yang (Food Research International, 2024)

A ratiometric fluorescent probe based on UiO-66-TCPP for selective and visual detection of quercetin in food - Yiran Wang; Xiaolong Sun; Yufeng Zhou; Jiachen Liu; Huayue Zhu; Ru Jiang; Yingjie Miao; Yongqian Fu (Food Chemistry, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Regulating N-doped biochar with Fe-Mo heterojunctions as cathode in long-life zinc-air battery - Xiao-ru Meng; Shuai Gao; Nianxi Liu; Pei-dong Wu; Zhen Fang (Chemical Engineering Journal, 2024)

Sludge carbon quantum dots-activated peroxymonosulfate oxidation for sludge conditioning - Changgeng Liu; Yue Lai; Ru Chen; Jie Ye (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Geranylgeraniol: Bio-based platform for teprenone, menaquinone-4, and α-tocotrienol synthesis - Haoming Chi; Shun Wen; Tian Wen; Liying Er; Ru Lei; Chong Dai; Guangkai Bian; Kun Shen; Tiangang Liu (Bioresource Technology, 2024)

Heterogeneous degradation kinetics of typical pyrimidine pesticides toward OH radicals - Ru Chen; Dandan Chen; Qiang Niu; Lu Fan; Mingchao Sun; Zhengzheng Yang; Changgeng Liu (Atmospheric Environment, 2024)

Trichoderma harzianum promoting chrysanthemum cutting rooting and reshaping microbial communities in endophytic and rhizosphere environments - Ya-Jie Wu; Murad Muhammad; Yu Jiao; Xiu Chen; Hai-Long Wang; Chun-Mei Lu; Xiao-Ming Wang; Guo-Xing Zhu; Kai-Qing Liu; Yue Zhang; Zi-Chao Liu; Zhi-Xing Chen; et al. (Applied Soil Ecology, 2024)

Dually-amplified electrochemical aptasensor based on the self-linking AuPt nanoflowers for ultrasensitive determination of hemagglutinin - Qing-Cai Yu; Yan Wang; Yao Liu; Chan-Ru Xiong; Xing Chen (Analytica Chimica Acta, 2024)

Efficacy of swallowing rehabilitative therapies for adults with dysphagia: a network meta-analysis of randomized controlled trials - Chi-Li Lee; Kondwani Joseph Banda; Yu-Hao Chu; Doresses Liu; Chiu-Kuei Lee; Chien-Mei Sung; Hidayat Arifin; Kuei-Ru Chou (GeroScience, 2024)

Ubiquity and ecological risks of conjugated steroids cannot be overlooked: First evidence from estuarine sediments - Fei Tian; Shan Liu; Ru Xu; Nian-Nian Wu; Shuang-Shuang Liu; Yuan-Yue Cheng; Qian Xiong; Zhen-Zhao Tang; Lin-Bao Zhang; Zhe Zhang; Hai-Gang Chen (Marine Pollution Bulletin, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

ESR chronology of the Quaternary sedimentary sequence of the Shinaimiao borehole in Hebi City, Henan Province, China - Hao Ji; Zhong-shan Shen; Chun-Ru Liu; Xiong-Nan Huang; Xiao-Ping Yang; Chuan-Yi Wei; Xin-Xiu Li; Qing Zhou; Gong-Ming Yin (Quaternary Geochronology, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Metabolic pathways altered by air pollutant exposure in association with coagulation function among the rural elderly - Haoyu Huang; Ru-Qing Liu; Yan Chen; Yuewei Liu; Guang-Hui Dong; Jian Hou; Shanshan Li; Yuming Guo; Chongjian Wang; Gongbo Chen (Journal of Hazardous Materials, 2024)

The construction of yeast β-glucan coated-edible dock protein nanomicelles for the encapsulation and sustained release of apigenin - Qian Zhou; Xiao-Jie Wang; Yu-Ru Wu; Weinan Zhang; Jing Li; Wei Wang; Ying-Nan Liu; Zhen-Yu Yu; Ming-Ming Zheng; Yi-Bin Zhou; Kang Liu (Journal of Food Engineering, 2024)

Technology-driven carbon-neutral pathway analysis for Urban Wastewater Treatment Plants - Haoran Wu; Chen Cai; Lian Yu; Zhenxing Shang; Yumeng Zhang; Xiaojing Ni; Ru Guo; Jia Liu; Kaiming Peng; Xiangfeng Huang; Limin Zhang; Zhaochang Huang; et al. (Journal of Cleaner Production, 2024)

Insight into the mechanism on nano fish bone improving the quality of marinated snakehead fish slices during freeze-thaw cycles - Ziaur Rahman; Tao Yin; Ramy M. Khoder; Abroo Tabasum; Qilin Huang; Juan You; Huawei Ma; Ru Liu; Shanbai Xiong (Innovative Food Science & Emerging Technologies, 2024)

Comparative study on dynamic in vitro digestion characteristics of lotus seed starch-EGCG complex prepared by different processing methods - Wenjing Chen; Ru Jia; Lu Liu; Wanyi Lin; Zebin Guo (Food Chemistry, 2024)

Development of easy-to-swallow and lipid-enhanced 3D printed surimi based on high internal phase emulsions - Wei Liang; Yuhang Wang; Chuan Li; Pengkai Wang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Prenatal exposure to bisphenol AF causes toxicities in liver, spleen, and kidney tissues of SD rats - Yaxuan Zhu; Xiuxiang Liu; Yijiao Shi; Xiuying Liu; Huaxin Li; Shaoguo Ru; Hua Tian (Food and Chemical Toxicology, 2024)

Enhancing osseointegration and angiogenesis of Titanium implants through KMnO4-Modified Montmorillonite nano-clay coating - Lifeng Xiong; Binwei Dai; Baodi Yin; Kendrick Hii Ru Yie; Haobo Sun; Yang Liu; Zheyuan Liu; Ahmed S. Mahany; Huan Cheng; Lihua Xu; Peng Gao; Lei Lu; et al. (Chemical Engineering Journal, 2024)

Diaper-based wearable SERS sensing system with a silver nano dual-structure composite hydrogel for the detection of biomarkers and pH in urine - Ru Liu; Qingling Nie; Yanhanzhuo Wang; Yan Wu; Yeting Tu; Chunling Xie; Xiufeng Xiao; Ruiyun You; Yudong Lu (Chemical Engineering Journal, 2024)

Circular hybrid membrane process treating high-salinity ammonium-rich pharmaceutical wastewater - Musie Welldegerima Atsbha; Ru Liu; Oded Nir (Chemical Engineering Journal, 2024)

Ingenane-type diterpenoids inhibit non-small cell lung cancer cells by regulating SRC/PI3K/Akt pathway - Xin-Ye Wang; Yu-Jue Wang; Zi-Lin Hou; Bo-Wen Guo; Ru-Qi Wang; Qingbo Liu; Guo-Dong Yao; Shao-Jiang Song (Natural Product Research, 2024)

Silencing of the Phytoene Desaturase (PDS) gene through virus infection using Tobacco Rattle Virus in Physalis grisea - Hai-Meng Zhang; Ru-Xin Wang; Yi-Ting Liu; Peng-Wei Jing; Qiao-Fang Shi; Yi-He Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Improved prediction of swimming talent through random forest analysis of anthropometric and physiological phenotypes - Cheng Liu; Bingxiang Xu; Kang Wan; Qin Sun; Ruwen Wang; Yue Feng; Hui Shao; Tiemin Liu; Ru Wang (Phenomics, 2024)

Mechanism of Efferocytosis in Determining Ischaemic Stroke Resolution—Diving into Microglia/Macrophage Functions and Therapeutic Modality - Xiao-Di Xie; Shan-Shan Dong; Ru-Juan Liu; Liu-Liu Shi; Ting Zhu (Molecular Neurobiology, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Sodium Selenite Ameliorates Silver Nanoparticles Induced Vascular Endothelial Cytotoxic Injury by Antioxidative Properties and Suppressing Inflammation Through Activating the Nrf2 Signaling Pathway - Yunyun Ma; Lei Wang; Jing He; Xueping Ma; Jingjing Wang; Ru Yan; Wanrui Ma; Huiyan Ma; Yajuan Liu; Hongqian Sun; Xiaoxia Zhang; Shaobin Jia; et al. (Biological Trace Element Research, 2024)
Silver nanoparticles (AgNP) are the dominant nanomaterials in commercial products and the medical field, but the widespread occurrence of AgNP has become a global threat to human health. Growing studies indicate that AgNP exposure can induce vascular endothelial toxicity by excessive oxidative stress and inflammation, which is closely related to cardiovascular disease (CVD), but the potential intrinsic mechanism remains poorly elucidated. Thus, it has been crucial to control the toxicological effects of AgNP in order to improve their safety and increase the outcome of their applications. Multiple researches have demonstrated that sodium selenite (Se) possesses the capability to counteract the toxicity of AgNP, but the functional role of Se in AgNP-induced CVD is largely unexplored. The aim of this study was to explore the potential protective effect of Se on AgNP-induced vascular endothelial lesion and elucidate the underlying mechanisms. An in vivo model of toxicity in animals was established by the instillation of 200 µL of AgNP into the trachea of rats both with (0.2 mg/kg/day) and without Se treated. In vitro experiments, human umbilical vein endothelial cells (HUVECs) were incubated with AgNP (0.3 µg/mL ) and Se for a duration of 24 h. Utilizing transmission electron microscopy, we observed that the internalization of AgNP-induced endothelial cells was desquamated from the internal elastic lamina, the endoplasmic reticulum was dilated, and the medullary vesicle formed. Se treatment reduced the levels of vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1), inhibited the release of pro-inflammatory cytokines (specifically tumor necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6), improved endothelial cell permeability, integrity, and dysfunction, and prevented damage to the aortic endothelium caused by AgNP. Importantly, we found that Se showed the capacity against AgNP with biological functions in guiding the intracellular reactive oxygen species (ROS) scavenging and meanwhile exhibiting anti-inflammation effects. Se supplementation decreased the intracellular ROS release and suppressed NOD-like receptor protein 3 (NLRP3) and nuclear factor kappa-B (NF-κB) mediated inflammation within AgNP-intoxicated rats and HUVECs. The anti-oxidant stress and anti-inflammatory effects of Se were at least partly dependent on nuclear factor erythroid 2-related factor 2 (Nrf2). Overall, our results indicated that the protectiveness of Se against AgNP-induced vascular endothelial toxicity injury was at least attributed to the inhibition of oxidative ROS and pro-inflammatory NF-κB/NLRP3 inflammasome by activating the Nrf2 and antioxidant enzyme (HO-1) signal pathway.

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Development and application of bisphenol S electrochemical immunosensor and iridium oxide nanoparticle-based lateral flow immunoassay - Zhenzhong Zhang; Yongliang Feng; Hayan Teng; Shaoguo Ru; Yuejiao Li; Minhao Liu; Jun Wang (Chemosphere, 2024)

Do government resource management policies influence green productivity? New perspectives from fintech and digital resource policy in China - Pei Liu; Shiyu Feng; Yueze Liu; Xue Ru; Shengli Zhang (Resources Policy, 2024)

Water–Rock reactions in the acid leaching of Uranium: Hydrochemical characteristics and reaction mechanisms - Bing Wang; Yue Luo; Xun Li; Ya–zhou Liu; Chang–rui Xu; Yu–xiu Zheng; Yan–hong Zhang; Yi–ru Zhou (Journal of Hydrology, 2024)

Pollution level and ecological risk assessment of triazine herbicides in Laizhou Bay and derivation of seawater quality criteria - Zhenzhong Zhang; Yongliang Feng; Weizhong Wang; Shaoguo Ru; Lingchao Zhao; Yuanqing Ma; Xiukai Song; Lijuan Liu; Jun Wang (Journal of Hazardous Materials, 2024)

The effectiveness of gliding arc discharge plasma in sterilizing artificial seawater contaminated with Vibrio parahaemolyticus - Meng-Ru Du; Yu-yi Guo; Han-ze Wei; Yu-pan Zhu; Rong-rong Liu; Ruo-nan Ma; Fu-kun Shi; Jin-song Guo; Jie Zhuang (Journal of Hazardous Materials, 2024)

Effect of ozone oxidation on gastrointestinal digestion and absorption characteristics of silver carp (Hypophthalmichthys molitrix) surimi gels in vitro - Shuning Cao; Yuping Pan; Wendong Zheng; Shengjun Chen; Tao Yin; Ru Liu; Juan You (Food Research International, 2024)

Synthesis and application of gelatin-based controlled-release antibacterial films containing oregano essential oil/β-cyclodextrin microcapsules for chilling preservation of grass carp fillets - Tianhao Ying; Chenghong Jiang; Sadia Munir; Ru Liu; Tao Yin; Juan You; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Phase transformation of schwertmannite in paddy soil under different water management regimes and its impact on the migration of arsenic in soil - Ru Wang; Jing Zhuang; Shufan Chen; Hua Li; Xiaomeng Wang; Zengping Ning; Chengshuai Liu; Guanyu Zheng; Lixiang Zhou (Environmental Pollution, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

Thiophene-containing conjugated polymers modified Zn0.5Cd0.5S inorganic/organic S-scheme heterojunction for boosting photocatalytic hydrogen production coupled with benzyl alcohol oxidation - Lele Wei; Ru Song; Jiarui Song; Yaping Li; Yina Nie; Lin Liu; Jun Wan (Chemical Engineering Journal, 2024)

Astrocyte Activation in the ACC Contributes to Comorbid Anxiety in Chronic Inflammatory Pain and Involves in The Excitation-Inhibition Imbalance - Naixuan Wei; Zi Guo; Mengting Qiu; Ru Ye; Xiaomei Shao; Yi Liang; Boyi Liu; Jianqiao Fang; Junfan Fang; Junying Du (Molecular Neurobiology, 2024)

A comprehensive review of matcha: production, food application, potential health benefits, and gastrointestinal fate of main phenolics - Jian-Hui Ye; Qi-Ting Fang; Lin Zeng; Ru-Yi Liu; Lu Lu; Jun-Jie Dong; Jun-Feng Yin; Yue-Rong Liang; Yong-Quan Xu; Zhong-Hua Liu (Critical Reviews in Food Science and Nutrition, 2024)

Evaluating signal bleaching of Al and Ti–Li centers in fluvio-lacustrine sediments of Datong, North China, and its implications for the volcanic eruption chronology - Hao Ji; Chun-Ru Liu; Wen-Peng Li; Chuan-Yi Wei; Bhupati Neupane; Gong-Ming Yin (Quaternary Geochronology, 2024)

Glucoconjugated monoterpene indole alkaloids with xanthine oxidase inhibitory activity from Ophiorrhiza japonica - Bao-Bao Shi; Fan Xu; Guang-Ru Zhang; Yu He; Qing Liu; Meng-Lin Feng; Zheng-Hui Li; Ji-Kai Liu (Phytochemistry, 2024)

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Assessing spatial heterogeneity of nutrient loads in a large shallow lake using a lattice Boltzmann water quality model - Haifei Liu; Chuqi Zhang; Wei Yang; Zhiming Ru; Jiewei Ding; Yuetong Jing; Cheng Li (Journal of Environmental Management, 2024)

Study on factors influencing carbon dioxide emissions and carbon peak heterogenous pathways in Chinese provinces - Runpu Liu; Yan Ru Fang; Shuan Peng; Nihed Benani; Xuefang Wu; Yushuo Chen; Tao Wang; Qimin Chai; Pingjian Yang (Journal of Environmental Management, 2024)

Effect of heating treatment on processing characteristics of rice dough - Wan-ru Liu; Chun-min Ma; Yang Yang; Bing Wang; Xiao-fei Liu; Yan Wang; Xin Bian; Xiao-xue Guo; Guang Zhang; Na Zhang (Innovative Food Science & Emerging Technologies, 2024)

Digestion and absorption characteristics of iron-chelating silver carp scale collagen peptide and insights into their chelation mechanism - Qiannan Zhao; Wei Liang; Zhe Xiong; Chuan Li; Lu Zhang; Jianhua Rong; Shanbai Xiong; Ru Liu; Juan You; Tao Yin; Yang Hu (Food Research International, 2024)

Effect of guar gum, gelatin, and pectin on moisture changes in freeze-dried restructured strawberry blocks - Jiaqi Hu; Xiyun Sun; Hongwei Xiao; Chunju Liu; Feifei Yang; Wuyi Liu; Yulong Wu; Yaoyao Wang; Ru Zhao; Haiou Wang (Food Chemistry, 2024)

Green tea polyphenols reduced Porphyromonas gingivalis virulence and ameliorated aggravated gut inflammation by improving immunity and gut microbiota dysbiosis - Ming Li; Ru Qu; Ping Li; Xuan Mo; Juan Liu; Zhenjiang Zech Xu (Food Bioscience, 2024)

LECT2 mediates antibacterial immune response induced by Nocardia seriolae infection in the northern snakehead - Jian Teng; Yan Zhao; Yu Bao Li; Liang Yi Xue; Yi Xiang Zhai; Jian Ru Liu; Hui Wang; Xiang Shan Ji (Fish & Shellfish Immunology, 2024)

The role and mechanism of heme oxygenase-1 in arrhythmias - Huan-Huan Liu; Lei Zhang; Fan Yang; Ling-Ling Qian; Ru-Xing Wang (Journal of Molecular Medicine, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Author Correction: Multiscale nest-site selection and breeding biology: infrared camera monitoring of the great crested grebe Podiceps cristatus in a plateau freshwater lake in southwestern China - Zu K. Luo; Xian H. Shao; Yu B. Liu; Ru B. Wang (Ornithology Research, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Response model between nanobubble preparation parameters and properties: Controllable preparation & its application example - Xin Ru Feng; Jiajun Hu; Nan Liu; Wang Kai Tong; Mintian Gao; Chaomeng Dai; Yueming Han; Jixiang Li (Journal of Water Process Engineering, 2024)

Identification and functional analyses of CD4-1+ cells in grass carp (Ctenopharyngodon idella) - Xue-Qing Han; Yi-Ru Pan; Ya-Qin Zhong; Tian-Tian Tian; Xun Liu; Xu-Jie Zhang; Yong-An Zhang (Fish & Shellfish Immunology, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Multiscale nest-site selection and breeding biology: infrared camera monitoring of the great crested grebe Podiceps cristatus in a plateau freshwater lake in southwestern China - Zu K. Luo; Xian H. Shao; Yu B. Liu; Ru B. Wang (Ornithology Research, 2024)

Effects of exercise training on the external morphology, growth performance, swimming ability, body composition and metabolism of juvenile black seabream Acanthopagrus schlegelii - Haoyu Guo; Jinbo Zhai; Mengjia Tian; Joacim Näslund; Jiangfeng Ru; Yingying Ou; Yulu Qi; Qingsong Hu; Kai Liu; Xiumei Zhang (Aquaculture, 2024)

Path tracking control for brake-steering tracked vehicles based on an improved pure pursuit algorithm - Chenming Hu; Yu Ru; Xianzhe Li; Shuping Fang; Hongping Zhou; Xianghai Yan; Mengnan Liu; Rong Xie (Biosystems Engineering, 2024)

Cysteine and glycine-rich protein 2 is crucial for maintaining the malignant phenotypes of gliomas through its action on Notch signalling cascade - Lingtong Liu; Fei Li; Lingxue Zhang; Yingying Cheng; Lin Wu; Ru Tie; Xiaobing Jiang; Wenwen Gao; Bochuan Liu; Yao Wei; Pan Chang; Jun Xu; et al. (Toxicology and Applied Pharmacology, 2024)

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

Zinc isotope evidence for enhanced organic carbon burial driving transient oxygenation of the Mesoproterozoic ocean - Kexin Song; Dandan Li; Yi-Wen Lv; Chengshuai Yuan; Yuan-Ru Qu; Sheng-Ao Liu (Precambrian Research, 2024)

Neoproterozoic back-arc and arc-type magmatisms in the Rutong and Shiquanhe region, west of Tibet: Tectonic implications for the early-stage evolution of the Bangong-Nujiang suture zone and North Lhasa terrane - Xu Zhang; Di-Zhu Cai; Harald Furnes; Wei-Liang Liu; Rui Wang; Wei Li; Xing Liao; Chi Yan; Ru-Xin Ding; Yun Zhong (Precambrian Research, 2024)

A macromolecular Gleditsia Saponin induces apoptosis of leukemia cells through Fas-mediated death receptor pathway and mitochondrial pathway - Wen-jie Ding; Yao Huo; Zhen-tong Li; Yan-ru Liu; Ke-yao Dai; Chao Liu; Hai-yu Ji; An-jun Liu (Food Bioscience, 2024)

Differences among Lactiplantibacillus plantarum strains isolated from different fermented foods in their potential cholesterol-lowering properties - Shu-Jun Guo; Chang-Cheng Li; Yu-Ting Feng; Yan-Ru Zhou; Bin Liu; Zhen-Peng Gao; Chun-Feng Guo (Food Bioscience, 2024)

Halogenated aromatic pollutants in routine animal-derived food of south China: Occurrence, sources, and dietary intake risks - Li-Na Zhang; Ping-An Peng; Hui-Ru Li; Ming-Yang Liu; Jian-Fang Hu (Environmental Pollution, 2024)

Polymer composite membranes as SERS substrate materials: Recyclable and highly stable - Haonan Wang; Chuyi Wang; Qingling Nie; Ru Liu; Yixuan Yang; Jiayi Lin; Bohan Zhang; Ruiyun You; Yunzhen Liu; Xiufeng Xiao; Yudong Lu (Chemical Engineering Journal, 2024)

A freestanding rotating triboelectric nanogenerator with large area and high efficiency for triboelectric plasma CO2 reduction - Hongjie Cao; Qinglong Ru; Dongyang Fang; Sumin Li; Nannan Liu; Wei Jiang; Hui Hu; Yongcui Yang; Guangqin Gu; Bao Zhang; Gang Cheng; Sanjun Yang; et al. (Chemical Engineering Journal, 2024)

Biomimetic design of micro- and nano-wrinkle wood surface via coating reinforced with hyperbranched polymer grafted cellulose nanofibers for skin-tactile performance - Ru Liu; Yuhui Sun; Yingchun Sun; Hui Li; Minggui Chen; Ling Long; Jingya Gong; Bin Lv; Yonghao Ni (Carbohydrate Polymers, 2024)

Di- and tri-methylation of histone H3K36 play distinct roles in DNA double-strand break repair - Runfa Chen; Meng-Jie Zhao; Yu-Min Li; Ao-Hui Liu; Ru-Xin Wang; Yu-Chao Mei; Xuefeng Chen; Hai-Ning Du (Science China Life Sciences, 2024)

Cadmium Treatment Affected the Growth and Physiology of Larix Olgensis Seedlings, the Chemical Properties of Haplic Cambisols and Toxicity Threshold Determination - Haixia Wang; Kunshu Yao; Jiaxin Ru; Jiagui Guo; Ding Liu; Yunlong Liu; LingYun Bai; Jixiang Lin; Chengbo Gu; Jinfeng Song (Journal of Soil Science and Plant Nutrition, 2024)

Dissolved oxygen and ammonia affect ammonia production via GDH/AMPK signaling pathway and alter flesh quality in Chinese perch (Siniperca chuatsi) - Ru Yang; Xuange Liu; Yong Liu; Qingda Tian; Ziwei Wang; Dejie Zhu; Zhisong Qian; Yi Yi; Jiacheng Hu; Yan Li; Xu-Fang Liang; Liwei Liu; et al. (Fish Physiology and Biochemistry, 2024)

Addition of α-ketoglutaric acid (AKG) reduces deamination in Chinese perch (Siniperca chuatsi) fed with fermented soybean meal as a substitute for fishmeal - Yufei Zhang; Jiacheng Hu; Peisong Lu; Ru Yang; Xu-Fang Liang; Liwei Liu (Fish Physiology and Biochemistry, 2024)

Evaluation of natural fractures and geological sweet spot in the Shunbei ultra-deep carbonate fault-controlled reservoir, Tarim Basin - Gemeng Zhang; Zhixing Ru; Yingtao Li; Shuang Liu (Carbonates and Evaporites, 2024)

Effect of the CYBA C242T Polymorphism on Preeclampsia Pathogenesis in the Chinese Population - Ru Zhang; Shuhui Liu; Ping Tan; Zihan Guo; Huabin Hou; Shiguo Liu; Hui Li; Xibing Wang (Biochemical Genetics, 2024)

Aconitum coreanum and processed products on its base prevent stroke via the PI3K/Akt and KEAP1/NRF2 in the in vivo study - Wan-ting Zeng; Li-ting Zhou; Ru Jia; Yue Liu; Qian Cai; Yang Qu (Metabolic Brain Disease, 2024)

Application of a water-energy-carbon coupling index to evaluate the long-term operational stability of the anaerobic-anoxic-oxic-membrane bioreactor (A2/O-MBR) process under the influence of rainstorms - Lian Yu; Kaiming Peng; Yizhen Huang; Feng Chen; Shoubin Chen; Yulong Xia; Xiangfeng Huang; Xiaojing Ni; Ru Guo; Chen Cai; Jia Liu (Water Research, 2024)

Blue-light irradiation induced partial nitrification - Ru Zheng; Yiming Feng; Lingrui Kong; Xiaogang Wu; Jianhang Zhou; Liguo Zhang; Sitong Liu (Water Research, 2024)

BDNF mimetics recover palmitic acid-induced injury in cardiomyocytes by ameliorating Akt-dependent mitochondrial impairments - Man-Ru Zhang; Bang-Yun Zuo; Yu-Chen Song; Dan-Dan Guo; Qing-Liu Li; Jin-Xiu Lyu; Hua Zhu; Jing Zhao; Peng-Zhou Hang (Toxicology and Applied Pharmacology, 2024)

Assessing climate/air quality synergies and cost-effectiveness for Beijing transportation: Insights into sustainable development - Xuefang Wu; Roy M. Harrison; Min Chen; Tao Wang; Ruihe Lyu; Shuan Peng; Runpu Liu; Yushuo Chen; Yan Ru Fang; Pingjian Yang (Sustainable Cities and Society, 2024)

Green manure removal with reduced nitrogen improves saline-alkali soil organic carbon storage in a wheat-green manure cropping system - Fangdi Chang; Hongyuan Zhang; Na Zhao; Peiyi Zhao; Jiashen Song; Ru Yu; Zhengrong Kan; Xiquan Wang; Jing Wang; Hanjiang Liu; Dongxun Han; Xinya Wen; et al. (Science of The Total Environment, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Direct and indirect monitoring methods for nitrous oxide emissions in full-scale wastewater treatment plants: A critical review - Zhenxin Shang; Chen Cai; Yanli Guo; Xiangfeng Huang; Kaiming Peng; Ru Guo; Zhongqing Wei; Chenyuan Wu; Shunjian Cheng; Youxiang Liao; Chih-Yu Hung; Jia Liu (Journal of Environmental Management, 2024)

Effect of ultrasound-assisted enzyme pretreatment on γ-aminobutyric acid content, eating quality and starch properties of germinated brown rice - Bing-jie Chen; Xiao Wang; Hong-ru Liu; Yi Zhang; Song-heng Wu; Chun-fang Wang; Chen-xia Liu; Yong-jin Qiao (Journal of Cereal Science, 2024)

High-Performance enrichment and sensitive analysis of bisphenol and its analogues in water and milk using a novel Ni-Based cationic Metal-Organic framework - Jin-Yan Ma; Hai-Long Jiang; Fu-Shuai Kang; Lu Liu; Xia Wang; Ru-Song Zhao (Food Chemistry, 2024)

Pretreatment with low-frequency magnetic fields can improve the functional properties of pea globulin amyloid-like fibrils - Qing-Qing Liu; Qin Yang; Ya-Ru Wang; Yi-Xuan Jiang; Han-Qing Chen (Food Chemistry, 2024)

Ultrasound-regulated fibrillation of arachin: Structural characteristics, foaming and emulsifying properties - Qin Yang; Ya-Ru Wang; Qing-Qing Liu; Yi-Xuan Jiang; Han-Qing Chen (Food Hydrocolloids, 2024)

Uptake, translocation, and metabolism of organophosphate esters (OPEs) in plants and health perspective for human: A review - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yu-Fei Feng; Long-Wei Zhang; Xue-Yi Jiang; Yi-Shan Liu; Dong-Wei Wu; Jun-Jie Hu (Environmental Research, 2024)

A novel ionic-liquid-mediated covalent organic framework as a strong electrophile for high-performance iodine removal - Jie Fu; Jia-Ying Liu; Yue-Ru Zhou; Lei Zhang; Shuang-Long Wang; Song Qin; Maohong Fan; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

Exercise-induced microbial changes in preventing type 2 diabetes - Ting Yao; Hui Wang; Kaiqing Lin; Ruwen Wang; Shanshan Guo; Peijie Chen; Hao Wu; Tiemin Liu; Ru Wang (Science China Life Sciences, 2024)

The NADase CD38 is a central regulator in gouty inflammation and a novel druggable therapeutic target - Paulo Gil Alabarse; Patricia Oliveira; Huaping Qin; Tiffany Yan; Marie Migaud; Robert Terkeltaub; Ru Liu-Bryan (Inflammation Research, 2024)
Objectives Cellular NAD + declines in inflammatory states associated with increased activity of the leukocyte-expressed NADase CD38. In this study, we tested the potential role of therapeutically targeting CD38 and NAD + in gout. Methods We studied cultured mouse wild type and CD38 knockout (KO) murine bone marrow derived macrophages (BMDMs) stimulated by monosodium urate (MSU) crystals and used the air pouch gouty inflammation model. Results MSU crystals induced CD38 in BMDMs in vitro, associated with NAD + depletion, and IL-1β and CXCL1 release, effects reversed by pharmacologic CD38 inhibitors (apigenin, 78c). Mouse air pouch inflammatory responses to MSU crystals were blunted by CD38 KO and apigenin. Pharmacologic CD38 inhibition suppressed MSU crystal-induced NLRP3 inflammasome activation and increased anti-inflammatory SIRT3–SOD2 activity in macrophages. BMDM RNA-seq analysis of differentially expressed genes (DEGs) revealed CD38 to control multiple MSU crystal-modulated inflammation pathways. Top DEGs included the circadian rhythm modulator GRP176 , and the metalloreductase STEAP4 that mediates iron homeostasis, and promotes oxidative stress and NF-κB activation when it is overexpressed. Conclusions CD38 and NAD + depletion are druggable targets controlling the MSU crystal- induced inflammation program. Targeting CD38 and NAD + are potentially novel selective molecular approaches to limit gouty arthritis.

CircRNA: a rising therapeutic strategy for lung injury induced by pulmonary toxicants - Cai Liao; Zhen-Wei He; Rui Yu; Ya-Jie Yu; Xiao-Ru Liu; De-Lei Kong; Yun Wang (Archives of Toxicology, 2024)

Prediction of cytochrome P450-mediated bioactivation using machine learning models and in vitro validation - Xin-Man Hu; Yan-Yao Hou; Xin-Ru Teng; Yong Liu; Yu Li; Wei Li; Yan Li; Chun-Zhi Ai (Archives of Toxicology, 2024)

One new triterpenoids from Momordica charantia L - Yue Jiang; Bing Liang; Qiong Wu; Jing-Ru Wang; Bing Liu (Natural Product Research, 2024)

Experiments and CFD simulation of downwash airflow and fog distribution discharged from a single-rotor UAV fitted with a pulse-jet thermal fogging machine - Jian Zhang; Qing Chen; Jian Liu; Yan Wang; Hongping Zhou; Fengbo Yang; Yu Ru (Biosystems Engineering, 2024)

Time-dependent nonmonotonic concentration-response and synergism of alkyl glycosides with different alkyl side chain to Vibrio qinghaiensis sp. -Q67 - Meng-Ting Tao; Shu-Shen Liu; Ting-Ting Ding; Zhong-Wei Gu; Ru-Jun Cheng (Science of The Total Environment, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Carbon emissions of urban rail transit in Chinese cities: A comprehensive analysis - Jing Pu; Chen Cai; Ru Guo; Jiangchuan Su; Ruimin Lin; Jia Liu; Kaiming Peng; Chaoguang Huang; Xiangfeng Huang (Science of The Total Environment, 2024)

Proteomics revealed composition- and size-related regulators for hepatic impairments induced by silica nanoparticles - Xinying Zhao; Ru Ma; Alimire Abulikemu; Yi Qi; Xiaoying Liu; Ji Wang; Kun Xu; Caixia Guo; Yanbo Li (Science of The Total Environment, 2024)

Arabidopsis HAPLESS13/AP-1µ is critical for pollen sac formation and tapetal function - Gui-Min Yin; Yi-Ru Fang; Jia-Gang Wang; Yue Liu; Xiaojiao Xiang; Sha Li; Yan Zhang (Plant Science, 2024)

Sulfur and nitrogen co-metabolism during composting: A role of sodium sulfide in regulating microbial communities and functional genes - Shuaipeng Liu; Heng Lu; Ao Wang; Xiaojing Chen; Hongmei Yang; Xueling Liang; Ru Sun; Xiaoli Wen; Qunliang Li (Journal of Environmental Chemical Engineering, 2024)

Interfacial behavior and micro-rheological performance of Pickering emulsions co-stabilized by β-cyclodextrin and xanthan gum - Wei Liang; Fanghui Deng; Yuhang Wang; Wei Yue; Die Hu; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Insights into the response of nitrogen metabolism to sulfamethoxazole contamination in constructed wetlands with varied substrates - Ya-Ru Zhang; Jia-Min Xu; Hao-Ran Xu; Guo-Dong Zhang; Xian-Bin Liu; Hao-Yi Cheng (Bioresource Technology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Subsurface organic amendment of a saline soil increases ecosystem multifunctionality and sunflower yield - Jiashen Song; Hongyuan Zhang; Fangdi Chang; Ru Yu; Jing Wang; Aiping Chen; Yang Xu; Yu Liu; Jie Zhou; Yuyi Li (Science of The Total Environment, 2024)

Communication mediated interaction between bacteria and microalgae advances photogranulation - Xiaogang Wu; Lingrui Kong; Yiming Feng; Ru Zheng; Jianhang Zhou; Jingqi Sun; Sitong Liu (Science of The Total Environment, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Relationship of single and co-exposure of per-and polyfluoroalkyl substances and their alternatives with uric acid: A community-based study in China - Li-Xia Liang; Li-Zi Lin; Mohammed Zeeshan; Yang Zhou; Yong-Xiang Tang; Chu Chu; Yun-Ting Zhang; Ru-Qing Liu; Wenru Feng; Guang-Hui Dong (Journal of Hazardous Materials, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

6PPD-quinone exposure induces neuronal mitochondrial dysfunction to exacerbate Lewy neurites formation induced by α-synuclein preformed fibrils seeding - Jiacheng Fang; Xiaoxiao Wang; Guodong Cao; Fuyue Wang; Yi Ru; Bolun Wang; Yanhao Zhang; Doudou Zhang; Jie Yan; Ji Xu; Jing Ji; Fenfen Ji; et al. (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Study by means of 1H nuclear magnetic resonance of the oxidation process in high oleic sunflower oil and palm oil during deep-frying of fish cakes - Xiaoyu Luo; Benlun Hu; Caihua Jia; Ru Liu; Jianhua Rong; Siming Zhao; Meng Niu; Yan Xu; Tao Yin; Juan You (Food Research International, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Exposures to drinking water disinfection byproducts and kidney function in Chinese women - Cheng-Ru Li; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Chong Liu; Qiang Zeng (Environmental Research, 2024)

Experimental and theoretical study on seismic behavior of a new UHPFRC sandwich wall and wall-wall joint - Ru-Rui Liu; Ran Ding; Yong-Tao Sun; Jian-Sheng Fan; Ding-Qiu Chen; Jian-Chao Xu (Engineering Structures, 2024)

Formation of lithium-rich pegmatites via rapid crystallization and shearing – case study from the South Tibetan Detachment, Himalaya - Xiao-Chi Liu; Matthew J. Kohn; Jia-Min Wang; Shao-Xiong He; Ru-Cheng Wang; Fu-Yuan Wu (Earth and Planetary Science Letters, 2024)

Efficient synthesis of squalene by cytoplasmic-peroxisomal engineering and regulating lipid metabolism in Yarrowia lipolytica - Yang Ning; Mengsu Liu; Ziyun Ru; Weizhu Zeng; Song Liu; Jingwen Zhou (Bioresource Technology, 2024)

Inflammation and Brain Structure in Alzheimer’s Disease and Other Neurodegenerative Disorders: a Mendelian Randomization Study - Wei-Shi Liu; Ya-Ru Zhang; Yi-Jun Ge; Hui-Fu Wang; Wei Cheng; Jin-Tai Yu (Molecular Neurobiology, 2024)

Chiral zeolite beta used as stationary phase for enantioseparation in miniaturized open tubular capillary electrochromatography with amperometric detection - Li Yang; Ru Liu; Chaodan Li; Boning Gu; Jiannong Ye; Li Chen; Qingcui Chu (Analytica Chimica Acta, 2024)

TPN10475 Constrains Effector T Lymphocytes Activation and Attenuates Experimental Autoimmune Encephalomyelitis Pathogenesis by Facilitating TGF-β Signal Transduction - Chun Wang; Xiangrui Jiang; Jie Lv; Wei Zhuang; Ling Xie; Guangyu Liu; Kaidireya Saimaier; Sanxing Han; Changjie Shi; Qiuhong Hua; Ru Zhang; Changsheng Du (Journal of Neuroimmune Pharmacology, 2024)

Biological upcycling of nickel and sulfate as electrocatalyst from electroplating wastewater - Xian-Zhong Fu; Yu-Ru Yang; Tian Liu; Zhi-Yan Guo; Chen-Xuan Li; Hai-Yang Li; Kang-Ping Cui; Wen-Wei Li (Water Research, 2024)

Adaptive shifts in plant traits associated with nitrogen removal driven by phytoremediation strategies in subtropical river restoration - Yu Xin; Lin Liu; Xiao-Ru Yang; Le-Yang Yang; Shan-Bin Guang; Yu-Ming Zheng; Quan-Bao Zhao (Water Research, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

The associations of secondhand smoke exposure with neurodevelopmental disorders and critical time window identification: A systematic review and meta-analysis - Xiao-Xuan Ou; Xin Wang; Xiao-Ling Zhan; Shu-Li Shen; Shamshad Karatela; Jin Jing; Li Cai; Ru-Qing Liu; Li-Zi Lin; Guang-Hui Dong (Science of The Total Environment, 2024)

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

Addressing the influencing path of social noise exposure risk perception on noise mitigation behavior - Chunyan Wang; Yihan Li; Yayun Shen; Yi Liu; Peng Ru; Zeyang Wei; Dan Xie (Journal of Environmental Management, 2024)

Maize/peanut rotation intercropping improves ecosystem carbon budget and economic benefits in the dry farming regions of China - Fei Han; Talha Javed; Sadam Hussain; Shuqing Guo; Ru Guo; Lihua Yang; Xiantong Liu; Tie Cai; Peng Zhang; Zhikuan Jia; Anis Ali Shah; Xiaoli Chen; et al. (Journal of Environmental Management, 2024)

Formation and structural characteristics of pea globulin amyloid-like fibrils pretreated with low-frequency magnetic field - Qing-Qing Liu; Qin Yang; Ya-Ru Wang; Yi-Xuan Jiang; Han-Qing Chen (Food Hydrocolloids, 2024)

Low-temperature fabrication of potassium single-atom solid base catalysts with high activity in transesterification - Xiang-Bin Shao; Xing-Ru Song; Song-Song Peng; Xiao-Qin Zheng; Shi-Chao Qi; Peng Tan; Xiao-Qin Liu; Lin-Bing Sun (Chemical Engineering Journal, 2024)

Design, synthesis and insecticidal activity of benzenesulfonamide derivatives containing various alkynyl, alkenyl and cyclopropyl groups in para position - Jian-Jun Zhu; Tao Guo; Hong-Xiang Liu; Xin-Ru Tan; Zi-Wei Zhang; Wen-Jun Wu; Ji-Wen Zhang (Natural Product Research, 2024)

ABA functions in low phosphate-induced anthocyanin accumulation through the transcription factor ABI5 in Arabidopsis - Ru-Feng Song; Xiao-Yu Hu; Wen-Cheng Liu; Hong-Mei Yuan (Plant Cell Reports, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Rapid detection of human adenovirus subgroup B using recombinase polymerase amplification assay - Yongzhe Zhu; Binghui Xia; Haizhou Xu; Zengxin Liu; Ru Wang; Qingqing Cai; Ping Zhao; Zhongtian Qi (Virus Genes, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Assessing production–living–ecological spaces and its urban–rural gradients in Xiangyang City, China: insights from land-use function symbiosis - Chao Liu; Qingke Yang; Fenghua Zhou; Ru Ai; Long Cheng (Environmental Science and Pollution Research, 2024)

Peduncle collision-free grasping based on deep reinforcement learning for tomato harvesting robot - Yajun Li; Qingchun Feng; Yifan Zhang; Chuanlang Peng; Yuhang Ma; Cheng Liu; Mengfei Ru; Jiahui Sun; Chunjiang Zhao (Computers and Electronics in Agriculture, 2024)

The application of static digestive models simulating the digestion system of infants and young children for the development of accessory food: Current status and future perspective - Jing Lin; Caiyu Liu; Ru Bai; Jinzhu Pang; Junan Li; Chi Zhang; Xinqi Liu; He Li; Sumei Hu (Trends in Food Science & Technology, 2024)

Transcriptomic analysis reveals the immune response mechanisms of sea cucumber Apostichopus japonicus under noise stress from offshore wind turbine - Xiaochen Cheng; Libin Zhang; Zhaoming Gao; Kehan Li; Jialei Xu; Weijian Liu; Xiaoshang Ru (Science of The Total Environment, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Associations between urinary biomarkers of exposure to disinfection byproducts and semen parameters: A repeated measures analysis - Min Zhang; Xiao-Ying Liu; Yan-Ling Deng; Chong Liu; Jia-Yue Zeng; Yu Miao; Yang Wu; Cheng-Ru Li; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Qiang Zeng (Journal of Hazardous Materials, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

Tree ring oxygen isotope in Asia - Chenxi Xu; Ru Huang; Wenling An; Qingyu Zhao; Yaru Zhao; Junbo Ren; Yucheng Liu; Zhengtang Guo (Global and Planetary Change, 2024)

Effects of freezing methods on physicochemical properties, protein/fat oxidation and odor characteristics of surimi gels with different cross-linking degrees - Xiaoying Luo; Kang Huang; Yongxin Niu; Xu Zhang; Yueqi An; Ru Liu; Shanbai Xiong; Yang Hu (Food Chemistry, 2024)

Expression of polyphenol oxidase of Litopenaeus vannamei and its characterization - Qian Hong; Yu-Lei Chen; Duanquan Lin; Ru-Qing Yang; Kai-Yuan Cao; Ling-Jing Zhang; Yi-Ming Liu; Le-Chang Sun; Min-Jie Cao (Food Chemistry, 2024)

Study on low methoxyl pectin (LMP) with varied molecular structures cross-linked with calcium inducing differences in the gel properties - Chun-lin Wu; Jun-ru Qi; Jin-song Liao; Zi-wei Liu; Chun-ai He (Food Hydrocolloids, 2024)

High internal phase emulsions of ω-3 fatty acids stabilized by fish scale gelatin particles: Application to lipid-enhanced surimi 3D printing - Yuhang Wang; Die Hu; Wei Yue; Juan You; Tao Yin; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Study and application of coupling relationship between water-salt-resistivity-soil structure in saline soils in arid and semi-arid areas of northwest China - Yang Liu; Feng-jie Li; Hong-li Liu; Yu-ru Hou; Nusrat Nazir (Environmental Research, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

Uptake mechanism, translocation, and transformation of organophosphate esters in water hyacinth (Eichhornia crassipes): A hydroponic study - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yi-Shan Liu; Long-Wei Zhang; Yu-Fei Feng; Xue-Yi Jiang; Dong-Wei Wu; Jun-Jie Hu; Guang-Guo Ying (Environmental Pollution, 2024)

Fully space-confined donor-acceptor interaction for highly efficient thermally activated delayed fluorescence emitters - Wen-Cheng Chen; Ming-Hui Zheng; Yu-Lan Wu; Ru-Jia Wang; Jia-Ming Jin; Si-Wei Chen; Bo Liu; Jia-Xiong Chen; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2024)

Stress Threshold Determination Method and Damage Evolution Modelling Based on Micritic Bioclastic Limestone - Zuguo Mo; Li Qian; Tianzhi Yao; Yunpeng Gao; Jianhai Zhang; Ru Zhang; Enlong Liu; Haibo Jiang (Rock Mechanics and Rock Engineering, 2024)

Sympatric munias in tropical areas segregate spatially through different nest site selections to achieve coexistence - Chen-Wei Guo; Li-Li Li; Chen-Yang Liu; Ru-Chuan He; Rui-Chang Quan (Acta Oecologica, 2024)

Occurrence, ecological risk, and advanced removal methods of herbicides in waters: a timely review - Lingxiao Li; Yunsheng Wang; Lijuan Liu; Chen Gao; Shaoguo Ru; Liqiang Yang (Environmental Science and Pollution Research, 2023)

A Dual Functional Fluorescent Probe Based on Phenothiazine for Detecting Hg2+ and ClO− and its Applications - Cheng-lu Zhang; Chang Liu; Shi-ru Nie; Yang Zhang; Jing-hao Guo; Xiang-ling Li; Cui Liu (Journal of Fluorescence, 2023)

Effect of swimming training on the flesh quality in Chinese Perch (Siniperca chuatsi) and its relationship with muscle metabolism - Tingyao Zhu; Ru Yang; Runguo Xiao; Weiqiang Ni; Liwei Liu; Jian Zhao; Zhangying Ye (Aquaculture, 2023)

Corrigendum to “Silica nanoparticles promote oxLDL-induced macrophage lipid accumulation and apoptosis via endoplasmic reticulum stress signaling” [Sci. Total Environ., 631-632 (2018): 570-579] - Caixia Guo; Ru Ma; Xiaoying Liu; Tian Chen; Yang Li; Yang Yu; Junchao Duan; Xianqing Zhou; Yanbo Li; Zhiwei Sun (Science of The Total Environment, 2023)

Plastic pollution from takeaway food industry in China - Qian-Qian Zhang; Min-Yi Lan; Hui-Ru Li; Shu-Qing Qiu; Zhao Guo; You-Sheng Liu; Jian-Liang Zhao; Guang-Guo Ying (Science of The Total Environment, 2023)

Insights into greenhouse gas emissions from a wastewater treatment plant in vulnerable water areas of China - Jiemiao Ma; Xiaojing Ni; Chen Cai; Yuewu Da; Kan Hu; Ru Guo; Jia Liu; Kaiming Peng; Erwu Liu; Xiangfeng Huang (Science of The Total Environment, 2023)

The protective immunity induced by Trichinella spiralis galectin against larval challenge and the potential of galactomannan as a novel adjuvant - Ru Zhang; Xin Zhuo Zhang; Xin Guo; Lu Lu Han; Bo Ning Wang; Xi Zhang; Ruo Dan Liu; Jing Cui; Zhong Quan Wang (Research in Veterinary Science, 2023)

Genome resources for the elite bread wheat cultivar Aikang 58 and mining of elite homeologous haplotypes for accelerating wheat improvement - Jizeng Jia; Guangyao Zhao; Danping Li; Kai Wang; Chuizheng Kong; Pingchuan Deng; Xueqing Yan; Xueyong Zhang; Zefu Lu; Shujuan Xu; Yuannian Jiao; Kang Chong; et al. (Molecular Plant, 2023)

Effect of 3D titanium substrates with TiO2 nanotube arrays on photoelectrocatalysis degradation of phenol - He Li; Man Li; Bin Jiang; Ru Liu; Qi Li; Firdoz Shaik (Journal of Environmental Chemical Engineering, 2023)

Polystyrene grafted hollow layered double hydroxides (NiCo-LDH@PS) as solid phase microextraction coating for enhanced capture of polycyclic aromatic hydrocarbons - Xuemei Wang; Jie Zhang; Zhen Zhang; Jing Ru; Yuan Ma; Jingwei Liu; Xinzhen Du; Xiaoquan Lu (Journal of Environmental Chemical Engineering, 2023)

A novel strategy for inhibiting AGEs in fried fish cakes: Grape seed extract surimi slurry coating - Yanlei Gao; Haonan Shi; Qing Xiong; Runlin Wu; Yang Hu; Ru Liu (Food Control, 2023)

Investigation on molecular characteristics of organic compounds during a full-scale landfill leachate treatment process based on non-targeted analysis - Ninghui Song; Qian Zhang; Yixuan Wang; Li Gao; Sitao Liu; Hao Yao; Ru Liu; Hang Xu (Environmental Research, 2023)

Wood frame structured carbons with integrated sieving layer for propylene/propane separation - Cheng-Tong Wang; Wen-Cui Li; Shuang Xu; Ru-Shuai Liu; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2023)

In situ synthesis of bi-functional NH2-Ti2C3Tx@COF Schottky heterojunction through interfacial electron effects for enhancing U(VI) photoreduction - You-Gan Wang; Wei Jiang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Humic acid plus manure increases the soil carbon pool by inhibiting salinity and alleviating the microbial resource limitation in saline soils - Jiashen Song; Hongyuan Zhang; Fangdi Chang; Ru Yu; Xiangqian Zhang; Xiquan Wang; Weini Wang; Junmei Liu; Jie Zhou; Yuyi Li (CATENA, 2023)

North Atlantic Oscillation contributes to the subpolar North Atlantic cooling in the past century - Yifei Fan; Wei Liu; Pengfei Zhang; Ru Chen; Laifang Li (Climate Dynamics, 2023)

Can Antibiotic Resistance Genes in Household Food Waste be Reduced by Earthworm Vermicomposting? Underpinning Mechanisms and Strategies - Ru Fang; Xiaojing Liu; Zhipeng Zheng; Baoyi Lv; Jie Wang; Yinglong Su; Bing Xie; Dong Wu (Reviews of Environmental Contamination and Toxicology, 2023)

Experimental study on vegetation performance improvement of carbonaceous mudstone aggregate vegetation concrete with its micromechanism - Ling Zeng; Zi-Ru Yang; Huan-Yi Zha; Wei Wen; Jie Liu (European Journal of Environmental and Civil Engineering, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Organophosphate esters (OPEs) in a heavily polluted river in South China: Occurrence, spatiotemporal trends, sources, and phase distribution - Yi-Shan Liu; Hui-Ru Li; Zhi-Lang Lao; Sheng-Tao Ma; Zi-Cong Liao; Ai-Min Song; Ming-Yang Liu; You-Sheng Liu; Guang-Guo Ying (Environmental Pollution, 2023)

Mechanical energy-driven triboelectric plasma catalytic CO2 reduction over oxygen-vacancy-introduced In2O3 nanoparticles - Xiaochen Xiang; Jiao Wang; Qinglong Ru; Sumin Li; Ke Zhao; Yifei Zhu; Zhenpan Chen; Liangliang Liu; Guangqin Gu; Yu Jia; Bao Zhang; Gang Cheng; et al. (Chemical Engineering Journal, 2023)

Efficient removal of uranium under strong acid based on charge separation and protonation coupled covalent organic frameworks - Shun-Mo Yi; Cheng-Rong Zhang; Xin Liu; Xiao-Juan Chen; Jia-Xin Qi; Cheng-Peng Niu; Jin-Lan Liu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Cyclodextrin-based metal-organic framework materials: Classifications, synthesis strategies and applications in variegated delivery systems - Ru-nan Zhao; Bei-wei Zhu; Yu Xu; Song-feng Yu; Wen-jun Wang; Dong-hong Liu; Jiang-ning Hu (Carbohydrate Polymers, 2023)

USP22 knockdown protects against cerebral ischemia/reperfusion injury via destabilizing PTEN protein and activating the mTOR/TFEB pathway - Yanling Li; Jing Gao; Chuntian Liu; Ning Bu; Shuqin Zhan; Haiqin Wu; Ru Zhang; Hong Sun; Hong Fan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Paternal lipopolysaccharide exposure induced intrauterine growth restriction via the inactivation of placental MEST/PI3K/AKT pathway in mice - Pei-Ying Jiang; Shuai Lin; Jie-Ru Liu; Yan Liu; Li-Ming Zheng; Qiang Hong; Yi-Jun Fan; De-Xiang Xu; Yuan-Hua Chen (Archives of Toxicology, 2023)

Multivariate Sea Surface Prediction in the Bohai Sea Using a Data-Driven Model - Song Hu; Qi Shao; Wei Li; Guijun Han; Qingyu Zheng; Ru Wang; Hanyu Liu (Journal of Marine Science and Engineering, 2023)
Data-driven predictions of marine environmental variables are typically focused on single variables. However, in real marine environments, there are correlations among different oceanic variables. Additionally, sea–air interactions play a significant role in influencing the evolution of the marine environment. Both internal dynamics and external drivers contribute to these changes. In this study, a data-driven model is proposed using sea surface height anomaly (SSHA), sea surface temperature (SST), and sea surface wind (SSW) in the Bohai Sea. This model combines multivariate empirical orthogonal functions (MEOFs) with long and short-term memory (LSTM). MEOF analysis is used on the multivariate dataset of SSHA and SST, considering the correlation among sea surface variables. SSW is introduced as a predictor to enhance the predictability of the multivariate sea surface model. In the case of the Bohai Sea, the comparative tests of the model without wind field effect, the fully coupled model, and the proposed prediction model were carried out. MEOF analysis is employed in comparative experiments for oceanic variables, atmospheric variables, and combined atmospheric and oceanic variables. The results demonstrate that using wind field as a predictor can improve the forecast accuracy of SSHA and SST in the Bohai Sea. The root mean square errors (RMSE) for SSHA and SST in a 7-day forecast are 0.016 m and 0.3200 °C, respectively.

Inter-brain neural mechanism and influencing factors underlying different cooperative behaviors: a hyperscanning study - Qingming Liu; Huimin Cui; Bincan Huang; Yingying Huang; Huimeng Sun; Xinyi Ru; Mingming Zhang; Wei Chen (Brain Structure and Function, 2023)

YOLACTFusion: An instance segmentation method for RGB-NIR multimodal image fusion based on an attention mechanism - Cheng Liu; Qingchun Feng; Yuhuan Sun; Yajun Li; Mengfei Ru; Lijia Xu (Computers and Electronics in Agriculture, 2023)

Deep insights into the population shift of n-DAMO and Anammox in granular sludge: From sidestream to mainstream - Sheng-Qiang Fan; Wan-Ru Wen; Guo-Jun Xie; Yang Lu; Bing-Feng Liu; De-Feng Xing; Jun Ma; Nan-Qi Ren (Water Research, 2023)

Recent understanding of stress response on muscle quality of fish: From the perspective of industrial chain - Tonghao Zhang; Liangzi Zhang; Tao Yin; Juan You; Ru Liu; Qilin Huang; Liu Shi; Lan Wang; Tao Liao; Weisheng Wang; Huawei Ma (Trends in Food Science & Technology, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Reduction of pesticides and bacteria on Napa cabbage by ozone microbubble water - Hsiu-Ling Chen; Rachelle D. Arcega; Pei-Yu Liao; Chih-Yao Hou; Wen-Chun Liu; Yun-Ru Chen; Jong-Shinn Wu; Wan-Ru Wang; Chia-Min Lin (Postharvest Biology and Technology, 2023)

The sulfate assimilation and reduction of marine microalgae and the regulation of illumination - Wen-Ying Dai; Lu Han; Pei-Feng Li; Qin-Dao Li; Li-Jun Xie; Chun-Ying Liu; Jun-Ru Kong; Ru Jia; Dan-Yang Li; Gui-Peng Yang (Marine Environmental Research, 2023)

Boron nitride quantum dots-enhanced laser desorption/ionization mass spectrometry analysis and imaging of bisphenol A - Yanfang Zhao; Rabah Boukherroub; Lu Liu; Huizhi Li; Ru-Song Zhao; Qin Wei; Xiang Yu; Xiangfeng Chen (Journal of Hazardous Materials, 2023)

Self-assembly and interaction mechanisms of edible dock protein and flavonoids regulated by the phenolic hydroxyl position - Qian Zhou; Xiao-Jie Wang; Jing Li; Yu-Ru Wu; Wei Wang; Zhen-Yu Yu; Ya-Qing Xiao; Ying-Nan Liu; Shi-Yi Li; Ming-Ming Zheng; Yi-Bin Zhou; Kang Liu (Food Chemistry, 2023)

Fungal strain improvement for efficient cellulase production and lignocellulosic biorefinery: Current status and future prospects - Jie Yang; Hou-Ru Yue; Li-Ya Pan; Jia-Xun Feng; Shuai Zhao; Surisa Suwannarangsee; Verawat Champreda; Chen-Guang Liu; Xin-Qing Zhao (Bioresource Technology, 2023)

Human TRMT1 catalyzes m2G or m22G formation on tRNAs in a substrate-dependent manner - Qing-Ping Xiong; Jing Li; Hao Li; Zhi-Xuan Huang; Han Dong; En-Duo Wang; Ru-Juan Liu (Science China Life Sciences, 2023)

Adult Kerion Celsi Caused by Trichophyton tonsurans Secondary to Black Dot Tinea Capitis - Qian-ru Ye; Yu-wu Luo; Xin Zhou; Qing-qing Li; Yu-mei Liu (Mycopathologia, 2023)
A 34-year-old female patient presented with hair loss due to black dot tinea capitis caused by Trichophyton tonsurans for 6 months. Hair loss progressed to painful swelling for 2 months due to kerion Celsi which may be associated with treatment like topical minoxidil, antibiotic and corticosteroid previously. The patient was treated with oral Itraconazole initially without success but cured by Terbinafine eventually. It’s very interesting that the patient caught kerion celsi secondary to a four-month history of hair loss due to black dot tinea capitis.

Exploration of using acoustic vibration technology to non-destructively detect moldy kernels of in-shell hickory nuts (Carya cathayensis Sarg.) - Qing-li Han; Bai-xue Long; Xue-jun Yan; Wu Wang; Feng-ru Liu; Xue Chen; Fei Ma (Computers and Electronics in Agriculture, 2023)

Highly sensitive lateral flow immunoassays based on Ag@Au nanoflowers with marine medaka (Oryzias melastigm) vitellogenin as a target analyte - Zhenzhong Zhang; Jun Wang; Hayan Teng; Minhao Liu; Yuejiao Li; Shaoguo Ru (Marine Pollution Bulletin, 2023)

Permeability decides the effect of antibiotics on sedimentary nitrogen removal in Jiulong River Estuary - Ru Wan; Lianghao Ge; Bin Chen; Jin-Ming Tang; Ehui Tan; Wenbin Zou; Li Tian; Meng Li; Zongbao Liu; Lijun Hou; Guoyu Yin; Shuh-Ji Kao (Water Research, 2023)

Burden of cardiovascular disease attributable to long-term exposure to ambient PM2.5 concentration and the cost–benefit analysis for the optimal control level - Chu-Chih Chen; Yin-Ru Wang; Jhi-Shin Liu; Hsing-Yi Chang; Yue Leon Guo; Pau-Chung Chen (Science of The Total Environment, 2023)

Ferritinophagy activation and sideroflexin1-dependent mitochondrial iron overload contribute to patulin-induced cardiac inflammation and fibrosis - Wen-Chang Sun; Ning-Ning Wang; Ru Li; Xian-Ce Sun; Jia-Wei Liao; Guang Yang; Shuang Liu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

Isolation and identification of 3,4-seco-labdane diterpenoids from Callicarpa nudiflora and investigation of their cytotoxicity against HepG2 cells - Qian-Qian Chen; Ming-Hui Fan; Hong-Tao Xu; Le-Yi Huang; Jin-Ling Liu; Shan-Shan Zhang; Ru-Ru Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

The early Late Triassic Yumen mafic rocks in the eastern Tethyan Himalaya: A record of the progressive opening of the Yarlung Zangbo Neo-Tethyan Ocean - Wei-Liang Liu; Zhong-Xi Xia; Yun Zhong; Chris Yakymchuk; Zhou-Rong Cai; He Xiao; Xing Liao; Chi Yan; Ru-Xin Ding; Jin-Nan Liu (Lithos, 2023)

Identifying potential toxic organic substances in leachates from tire wear particles and their mechanisms of toxicity to Scenedesmus obliquus - Jie-Ru Jiang; Zhi-Feng Chen; Xiao-Liang Liao; Qian-Yi Liu; Jia-Ming Zhou; Shi-Ping Ou; Zongwei Cai (Journal of Hazardous Materials, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Impact of National Industrial Relocation Demonstration Zones (NIRDZs) policy on urban carbon emissions in China - Ke-Liang Wang; Ru-Yu Xu; Wei Jiang; Yuan Liu (Environmental Impact Assessment Review, 2023)

Toxic effects of perfluorocaproic acid (PFHxA) on crucian carp (Carassius auratus) and the response of the intestinal microbial community - Xue Jiao; Zheng yao Guo; Bing li Liu; Long tao Wang; Zhi nan Yang; Yuan ru Yang; Ai-dong Qian; Yue-hong Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Multi-material 3D printing of piezoelectric and triboelectric integrated nanogenerators with voxel structure - Fang Chen; Zimo An; Yinghong Chen; Yijun Li; Xingang Liu; Ning Chen; Yue Ru; Dali Gao (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

(±)-Sarcanan A, a pair of new enantiomeric dihydrobenzofuran neolignans from the aerial parts of Sarcandra glabra - Ju Liu; Qi-yin Wen; Hong-ru Tian; Bing-jin-feng Zhan; Long-ping Zhu; De-po Yang; Zhi-min Zhao (Natural Product Research, 2023)

Strategy for cost-effective BMPs of non-point source pollution in the small agricultural watershed of Poyang Lake: A case study of the Zhuxi River - Wei Liu; Lei Zhang; Huoliang Wu; Yinfeng Wang; Yalan Zhang; Jinying Xu; Dongyang Wei; Ru Zhang; Ying Yu; Daishe Wu; Xianchuan Xie (Chemosphere, 2023)

Effects of dietary starch and metformin levels on the growth performance, body composition, hepatic glycolipid metabolism, and liver histology of juvenile largemouth bass Micropterus salmoides - Qin-Qin Liu; Ru Xia; Xin Deng; Hui-Jun Yang; Li Luo; Shi-Mei Lin; Chuan-Jie Qin; Yong-Jun Chen (Aquaculture, 2023)

Anammox bacteria adapt to long-term light irradiation in photogranules - Lingrui Kong; Ru Zheng; Yiming Feng; Wenran Du; Chen Xie; Yuanqi Gu; Sitong Liu (Water Research, 2023)

Zinc supplementation promotes oocyte maturation and subsequent embryonic development in sheep - Yupei Yao; Yujie Tang; Haoqiang Qin; Ru Meng; Chengtu Zhang; Yingbing Zhang; Ying Yang; Peipei Qiao; Jun Liu; Jianmin Su (Theriogenology, 2023)

Effects of exposure to chlorinated paraffins on human health: A scoping review - Jing-Wen Huang; Ya-Ying Bai; Mohammed Zeeshan; Ru-Qing Liu; Guang-Hui Dong (Science of The Total Environment, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

The sustainable treatment of chemical polishing wastewater under low-carbon economy: Pollutants removal, resource recovery and energy generation - Cong Ding; Meng-yu Liu; Si-zhuo Wan; Zhao-yang Cai; Lin-jiang Yuan; Ru Wang; Ping Zheng (Journal of Cleaner Production, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Carbonate-silicate interaction in subducting slabs recorded by Zn isotopes in western Alps metasediments - Yuan-Ru Qu; Sheng-Ao Liu; Vincent Busigny; Ze-Zhou Wang; Fang-Zhen Teng (Earth and Planetary Science Letters, 2023)

High transmittance, fast response, and high contrast ratio smart window with lateral driving electrophoretic display - Guangyou Liu; Jie Liu; Qitian Fan; Yunhe Liu; Zheng Zeng; Zhuohang Li; Xinzao Wu; Mingyang Yang; Bo-Ru Yang (Chemical Engineering Journal, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Short-term exposure to enrofloxacin causes hepatic metabolism disorder associated with intestinal flora dysbiosis in adult marine medaka (Oryzias melastigma) - Meiru Wang; Yifan Qin; Yifan Liu; Hui Yang; Jun Wang; Shaoguo Ru; Pengfei Cui (Marine Pollution Bulletin, 2023)

Role of phosphite in the environmental phosphorus cycle - Wei Liu; Yalan Zhang; Mengqin Yu; Jinying Xu; Hu Du; Ru Zhang; Daishe Wu; Xianchuan Xie (Science of The Total Environment, 2023)

Three-dimensional flow and turbulence structure around Sea Cucumber Apostichopus japonicus - Yubing Lin; Haifei Liu; Zhiming Ru; Gangqin Tu; Zixin Wang (Ocean Engineering, 2023)

Isopropanol and styrene removal from aqueous solutions and simultaneous power generation using microbial fuel cells with encapsulated deoxygenated anodes - Shu-Hui Liu; Jun-Ru Ke; Hwai Chyuan Ong; Chi-Wen Lin (Journal of Water Process Engineering, 2023)

Effects of flow velocity on the growth performance, antioxidant activity, immunity and intestinal health of Chinese Perch (Siniperca chuatsi) in recirculating aquaculture systems - Tingyao Zhu; Ru Yang; Runguo Xiao; Liwei Liu; Songming Zhu; Jian Zhao; Zhangying Ye (Fish & Shellfish Immunology, 2023)

Plasma-treated nano-enabled multimodal coatings made of phototherapeutic molybdenum disulfide and fucoidan prevent catheter-associated urinary tract issues - Jia-Wei Liang; Chia-Hung Liu; Kevin C.-W. Wu; Pei-Ru Jheng; Er-Yuan Chuang (Chemical Engineering Journal, 2023)

Highly sensitive plasmonic biosensor for hepatitis B virus DNA based on the surface etching of the active helical gold nanorods - Ru Cheng; Liang Tong Li; Min Huang; Fu Zhu; Qian Li; Hui Liu; Jie Gao; Xiao Hui Zhao; Fu Kang Luo; Jian Wang (Chemical Engineering Journal, 2023)

Genetic variation reveals the enhanced microbial hyaluronan biosynthesis via atmospheric and room temperature plasma - Zhi-Yuan Yao; Jin-Song Gong; Yu-Ru Liu; Jia-Yu Jiang; Yue-Sheng Zhang; Chang Su; Heng Li; Chuan-Li Kang; Lei Liu; Zheng-Hong Xu; Jin-Song Shi (Carbohydrate Polymers, 2023)

Effects of fungal agents and biochar on odor emissions and microbial community dynamics during in-situ treatment of food waste - Shu-Ping Zou; Ru-Sheng Liu; Yu Luo; Chun-Tao Bo; Su-Qin Tang; Ya-Ping Xue; Yu-Guo Zheng (Bioresource Technology, 2023)

The relationship between three-dimensional coseismic displacement and distribution of coseismic landslides - Ru Liu; Teng Wang (Science China Earth Sciences, 2023)

Projections from the Prefrontal Cortex to Zona Incerta Mediate Fear Generalization - Kun Tong; Guang-Kai Bu; Si-Qi Jing; Tong Wu; Yu-Tong Song; Yue You; Le Liu; Yuan-Hao Chen; Jing-Ru Hao; Nan Sun; Can Gao (Neuroscience Bulletin, 2023)

Calcination treatment of CoFe-layered double hydroxide enables enhanced chemodynamic and photothermal effects for antibacterial and antitumor applications - Ru Xu; Dongdong Zhang; Shuhan Chen; Jiajun Qiu; Xuanyong Liu (Applied Clay Science, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Nonlocality of scale-dependent eddy mixing at the Kuroshio Extension - Mingyue Liu; Ru Chen; Wenting Guan; Hong Zhang; Tian Jing (Frontiers in Marine Science, 2023)
Although eddy parameterization schemes are often based on the local assumption, previous studies indicate that the nonlocality of total eddy mixing is prevalent at the Kuroshio Extension (KE). For eddy-permitting climate models, only mixing induced by eddies smaller than the resolvable scale of climate models ( L * ) needs to be parameterized. Therefore, here we aim to estimate and predict the nonlocality of scale-dependent eddy mixing at the KE region. We consider the separation scale L * ranging from 0.2 ∘ to 2.5 ∘ , which is comparable to the typical resolution of the ocean component of climate models. Using a submesoscale-permitting model solution (MITgcm llc4320) and Lagrangian particles, we estimate the scale-dependent mixing (SDM) nonlocality ellipses and then diagnose the square root of the ellipse area ( L n , p a r t i c l e ). L n , p a r t i c l e is a metric to quantify the degree of SDM nonlocality. We found that, for all the available L * values we consider, the SDM nonlocality is prevalent in the KE region, and mostly elevated values of L n , p a r t i c l e occur within the KE jet. As L * decreases from 2.5 ∘ to 0.2 ∘ , the ratio L n , p a r t i c l e / L * increases from 0.8 to 8.9. This result indicates that the SDM nonlocality is more non-negligible for smaller L * , which corresponds to climate models with relatively high resolution. As to the SDM nonlocality prediction, we found that compared to the conventional scaling and the curve-fitting methods, the random forest approach can better represent L n , p a r t i c l e , especially in the coastal regions and within the intense KE jet. The area of the Eulerian momentum ellipses well capture the spatial pattern, but not the magnitude, of L n , p a r t i c l e . Our efforts suggest that eddy parameterization schemes for eddy-permitting models may be improved by taking into account mixing nonlocality.

Chronology analysis of huge landslide based on ESR dating materials on sliding face in carbonate areas of south eastern Tibet - Chun-Ru Liu; Ying-Ying Tian; Hao Ji; Xi Ma; Chuan-Yi Wei; Jia-Xiang Dang; Gong-Ming Yin; Yong-Sheng Zhou; Ren-Mao Yuan (Quaternary Geochronology, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Sexual dimorphism-related gene expression analysis based on the transcriptome in Gynaephora qinghaiensis, a pest of grassland on the Qinghai-Tibet Plateau - Hai-Zhen Wang; Ru-yi Zhang; Yuyu-Li; Xin Liu (Journal of Asia-Pacific Entomology, 2023)

Surfactants/citric acid catalyzed hydrothermal carbonization of pomelo peel for solid fuels: Conversion mechanism and combustion performance - Ru Ma; Sandile Fakudze; Shuai Liu; Yingyuan Wei; Jianqiang Chen; Jiangang Han; Chen Wang; Jiaxin Wang (Fuel, 2023)

Effects of microbial transglutaminase on the gelling property and in vitro digestibility of fish scale gelatin from grass carp - Yonggang Chen; Yuhang Wang; Ru Liu; Shanbai Xiong; Yan Xu; Yang Hu (Food Bioscience, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Polybenzimidazole-reinforced polyethylene oxide-based polymer-in-salt electrolytes enabling excellent structural stability and superior electrochemical performance for lithium metal batteries - Lei Zou; Kun Shi; Honglei Liu; Yong Wu; Tao Xu; Qiang Wang; Zhangxian Chen; Zeheng Yang; Ru Song; Jianhui Su; Weixin Zhang (Chemical Engineering Journal, 2023)

PcCLCg is involved in the accumulation of Cl− in shoots for osmotic adjustment and salinity resistance in the Cl−-tolerant xerophyte Pugionium cornutum - Yan-Nong Cui; Zi-Ru Lin; Mei-Mei Cai; Rui-Wen Liu; Suo-Min Wang; Qing Ma (Plant and Soil, 2023)

Cleaved amplified polymorphic sequence (CAP) marker development and haplotype geographic distribution of TaBOR1.2 associated with grain number in common wheat in China - Yuquan Wang; Xigui Hu; Lina Fu; Xiaojun Wu; Zhipeng Niu; Mingjiu Liu; Zhengang Ru (Cereal Research Communications, 2023)

Study on of structural style of fault zone and reservoir characteristics in the northern slope of Tazhong Uplift, Tarim Basin, China - Rui Zhao; Yuan Kang; Jun Han; Xiuxiang Zhu; Teng Zhao; Yuqing Liu; Chongyang Xiao; Shang Deng; Zhixing Ru; Yingtao Li (Carbonates and Evaporites, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

An extended SW-TES algorithm for land surface temperature and emissivity retrieval from ECOSTRESS thermal infrared data over urban areas - Chen Ru; Si-Bo Duan; Xiao-Guang Jiang; Zhao-Liang Li; Cheng Huang; Meng Liu (Remote Sensing of Environment, 2023)

Renewable pickering emulsion system based on bifunctional materials for highly efficient fuel oil desulfurization without stirring - Shuai-Yong Dou; Jia-Yu An; Yan-Ru Feng; Kang Liu; Xuan Wang; Bo-Wen Zhang; Jing-Xuan Zhang; Er-Hong Duan; Ai-Bin Kang (Fuel, 2023)

Machine learning based age-authentication assisted by chemo-kinetics: Case study of strong-flavor Chinese Baijiu - Qing-Ru Liu; Xiao-Juan Zhang; Lei Zheng; Lian-Jun Meng; Guang-Qian Liu; Ting Yang; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Cai-Hong Shen; Zheng-Hong Xu (Food Research International, 2023)

Remediating flooding paddy soils with schwertmannite greatly reduced arsenic accumulation in rice (Oryza sativa L.) but did not decrease the utilization efficiency of P fertilizer - Ru Wang; Yinglin Guo; Yang Song; Yuting Guo; Xiaomeng Wang; Quan Yuan; Zengping Ning; Chengshuai Liu; Lixiang Zhou; Guanyu Zheng (Environmental Pollution, 2023)

Flexible, biocompatible, degradable silk fibroin based display - Zijie Xu; Zhi He; Jiani Huang; Wu Qiu; Leo N.Y. Cao; Aniruddha Patil; Bo-Ru Yang; Xiang Yang Liu; Wenxi Guo (Chemical Engineering Journal, 2023)

Electrochemical etching induced high-valence cobalt with defects site for boosting electrochemical water splitting - Hongmei Gao; Jiaqi Liu; Zijin Zhang; Yuxuan Lu; Ru Chen; Yu-Cheng Huang; Chao Xie; Mengyi Qiu; Tianyu Wu; Jinbo Wang; Yubin Jiang; Chung-Li Dong; et al. (Chemical Engineering Journal, 2023)

Cloning, heterologous expression, and functional characterization of a hydroxyphenylpyruvate reductase (HPPR) gene involved in rosmarinic acid biosynthesis in Prunella vulgaris - Mei Ru; Liuyan Chen; Jiali Liu; Tingting Lan; Chuchu Yang; Xiaoyao Tan; Chuanmei Wu; Pan Liang; Zongsuo Liang (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Prodigiosin as an antibiofilm agent against multidrug-resistant Staphylococcus aureus - Jing Yan; Qi Yin; Hao Nie; Jinyou Liang; Xiang-Ru Liu; Yingli Li; Hong Xiao (Biofouling, 2023)

A comprehensive understanding of adaptive thermal comfort in dynamic environments – An interaction matrix-based path analysis modeling framework - Ru Ming; Baizhan Li; Chenqiu Du; Wei Yu; Hong Liu; Risto Kosonen; Runming Yao (Energy and Buildings, 2023)

Gli2-induced lncRNA Peg13 alleviates cerebral ischemia-reperfusion injury by suppressing Yy1 transcription in a PRC2 complex-dependent manner - Yanling Li; Chuntian Liu; Hong Fan; Yun Du; Ru Zhang; Shuqin Zhan; Guilian Zhang; Ning Bu (Metabolic Brain Disease, 2023)

Efficient coupling of sulfadiazine removal with microalgae lipid production in a membrane photobioreactor - Feng Gao; Jin-Long Zhou; Yu-Ru Zhang; Ashiwin Vadiveloo; Qing-Guo Chen; Jun-Zhi Liu; Qiao Yang; Ya-Ming Ge (Chemosphere, 2023)

Characteristics of dynamic shear modulus and damping ratio and the structural formula of EPS particles lightweight soil - Tian-shun Hou; Yi-xiang Cui; Xing-ru Pan; Ya-sheng Luo; Qian Liu (Soil Dynamics and Earthquake Engineering, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Olefin-linked cationic covalent organic frameworks for efficient extraction of ReO4−/99TcO4− - Wei-Rong Cui; Wei Xu; Yi-Ru Chen; Kai Liu; Wei-Bin Qiu; Yibao Li; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Simultaneous effect of high intensity ultrasound power, time, and salt contents on gelling properties of silver carp surimi - Xia Gao; Juan You; Tao Yin; Shanbai Xiong; Ru Liu (Food Chemistry, 2023)

Aggregating-agent-assisted surface-enhanced Raman spectroscopy–based detection of acrylamide in fried foods: A case study with potato chips - Zhi-hao Ye; Xiao-tong Chen; Hai-yan Zhu; Xiao-qian Liu; Wen-hui Deng; Wei Song; Da-xiang Li; Ru-yan Hou; Hui-mei Cai; Chuan-yi Peng (Food Chemistry, 2023)

Gelation properties of tofu induced by different coagulants: Effects of molecular interactions between nano-sized okara dietary fiber and soybean proteins - Ikram Ullah; Ramy M. Khoder; Tao Yin; Juan You; Qilin Huang; Ru Liu; Shanbai Xiong (Food Chemistry, 2023)

Self-oxidation cycle of oxidized red phosphorus for regeneration of binding sites enables efficient uranium extraction in tributylphosphate-kerosene system - Yingtong Lv; Ru Cheng; Guolin Yang; Wang Liu; Jingye Zhang; Xiaofang Yu; Wencai Bai; Rong He; Wenkun Zhu (Chemical Engineering Journal, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Constructing redox-active 3D covalent organic frameworks with high-affinity hexameric binding sites for enhanced uranium capture - Yi-Ru Chen; Xiu Wang; Wei Xu; Kai Liu; Wei-Bin Qiu; Yongquan Wu; Yibao Li; Wei-Rong Cui (Chemical Engineering Journal, 2023)

Inhibition of perilipin 2 attenuates cerebral ischemia/reperfusion injury by blocking NLRP3 inflammasome activation both in vivo and in vitro - Xu-Ying Liu; Qiu-Shi Li; Wen-Hai Yang; Yue Qiu; Fei-Fei Zhang; Xiu-Hui Mei; Qi-Wen Yuan; Ru-Bo Sui (In Vitro Cellular & Developmental Biology - Animal, 2023)

Effects of H2O2 acclimation on the growth, polysaccharide production and tolerance performance of Nostoc flagelliforme - Shu-ting Liu; Shuai Wang; Na Han; Meng-yuan Li; Jian Li; Yan-ru Li; Shi-ru Jia; Pei-pei Han (Algal Research, 2023)

Condition optimization of iron-air fuel cell to treat phosphate-containing wastewater regarding sustainable development - Ling-ling Lai; Chao Liu; Meng-yu Liu; Si-zhuo Wan; Zhi-guo Zhao; Ru Wang; Lin-jiang Yuan (Chemosphere, 2023)

How Comamonas testosteroni and Rhodococcus ruber enhance nitrification in the presence of quinoline - Ge Zhu; Haiyun Zhang; Ru Yuan; Meng Huang; Fei Liu; Mo Li; Yongming Zhang; Bruce E. Rittmann (Water Research, 2023)

Genomic analysis of Marinimicrobium sp. C6131 reveals its genetic potential involved in chitin metabolism - Yan-Ru Dang; Xiao-Yu Zhang; Sha-Sha Liu; Ping-Yi Li; Xue-Bing Ren; Qi-Long Qin (Marine Genomics, 2023)

The preparation of Co/γ-Al2O3 and treatment of cartap pesticide wastewater by microwave catalytic oxidation - Jia Ru Dai; Kai Xuan Liu; Fang Lian; Xue Peng Tian; Yu Feng Zhang (Journal of Water Process Engineering, 2023)

An all-organic conditioning method to achieve deep dewatering of waste activated sludge and the underlying mechanism - Jie Li; Shaoqin Ru; Chenwei Yuan; Bo Wu; Yiwen Ji; Zijun Dai; Zhongfang Lei; Zhenya Zhang; Tian Yuan; Fengting Li; Misha Liu (Journal of Environmental Management, 2023)

Effects of polystyrene nanoplastics on the physiological and biochemical characteristics of microalga Scenedesmus quadricauda - Ru-ru Li; Bin-liang Wang; Fang-ru Nan; Jun-ping Lv; Xu-dong Liu; Qi Liu; Jia Feng; Shu-lian Xie (Environmental Pollution, 2023)

COSEν: A collective oscillation simulation engine for neutrinos - Manu George; Chun-Yu Lin; Meng-Ru Wu; Tony G. Liu; Zewei Xiong (Computer Physics Communications, 2023)

Intracellularly-photosensitized bio-hybrid with biogenic quantum dots for enhanced wastewater denitrification - Shuo Cui; Yang Si; Xian-Zhong Fu; Hui-Hui Li; Xue-Meng Wang; Wen-Zheng Du; Lang Teng; Ru-Li He; Hou-Qi Liu; Ruquan Ye; Wen-Wei Li (Chemical Engineering Journal, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

FTO inhibits oxidative stress by mediating m6A demethylation of Nrf2 to alleviate cerebral ischemia/reperfusion injury - Lijing Hou; Shuang Li; Shasha Li; Ru Wang; Mengke Zhao; Xiaomin Liu (Journal of Physiology and Biochemistry, 2023)

Analysis of Whole Blood and Urine Trace Elements in Children with Autism Spectrum Disorders and Autistic Behaviors - Gang Zhao; Si-jin Liu; Xin-yu Gan; Jun-ru Li; Xiao-xue Wu; Si-yan Liu; Yi-si Jin; Ke-rang Zhang; Hong-mei Wu (Biological Trace Element Research, 2023)
The relationship between trace elements and neurological development is an emerging research focus. We performed a case–control study to explore (1) the differences of 13 trace elements chromium (Cr), manganese (Mn), cobalt (Co), zinc (Zn), arsenic (As), selenium (Se), molybdenum (Mo), cadmium (Cd), stannum (Sn), stibium (Sb), mercury (Hg), titanium (TI), and plumbum (Pb) concentration in whole blood and urine between autism spectrum disorder (ASD) children and their typical development peers, and (2) the association between the 13 trace elements and core behaviors of ASD. Thirty ASD subjects (cases) and 30 age-sex-matched healthy subjects from Baise City, Guangxi Zhuang Autonomous Region, China, were recruited. Element analysis was carried out by inductively coupled plasma-optical emission spectrometry. Autistic behaviors were assessed using Autism Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS), and Children Neuropsychological and Behavior Scale (CNBS). The whole blood concentrations of Mo ( p = 0.004), Cd (0.007), Sn ( p = 0.003), and Pb ( p = 0.037) were significantly higher in the ASD cases than in the controls. Moreover, Se (0.393), Hg (0.408), and Mn (− 0.373) concentrations were significantly correlated between whole blood and urine levels in ASD case subjects. There were significant correlations between whole blood Sb (0.406), Tl (0.365), Mo (− 0.4237), Mn (− 0.389), Zn (0.476), and Se (0.375) levels and core behaviors of ASD. Although the mechanism of trace element imbalance in ASD is unclear, these data demonstrate that core behaviors of ASD may be affected by certain trace elements. Further studies are recommended for exploring the mechanism of element imbalance and providing corresponding clinical treatment measures.

Contribution of Tibetan Plateau ecosystems to local and remote precipitation through moisture recycling - Yan Li; Ru Xu; Kun Yang; Yanxu Liu; Shuai Wang; Sha Zhou; Zhao Yang; Xiaoming Feng; Chunyang He; Zhengjie Xu; Wenwu Zhao (Global Change Biology, 2023)
The ecosystems of the Tibetan Plateau (TP) provide multiple important ecosystem services that benefit both local populations and those beyond, such as through climate regulation services on precipitation for East Asia and China. However, the precipitation regulation service of the TP ecosystems for supplying moisture and maintaining precipitation is yet to be evaluated. In this study, we used the moisture recycling framework and a moisture tracking model to quantify the precipitation regulation services of TP ecosystems for their contribution to precipitation. We found TP ecosystems contributed substantially to local and downwind precipitation, with a contribution of 221 mm/year for the TP and neighboring areas through evapotranspiration (ET) (104 mm/year through transpiration), declined to

Water–energy–carbon synergies and trade-offs: A daily nexus analysis for wastewater treatment plants - Xiaojing Ni; Xiangfeng Huang; Ru Guo; Jinhui Wang; Kaiming Peng; Wei Zhang; Yuyu Zhu; Weilan Yang; Liya Wang; Chen Cai; Jia Liu; Erwu Liu (Resources, Conservation and Recycling, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Transcriptomic analyses of carvone inhibited sprouting in sweet potato (Ipomoea batatas (L.) Lam cv ‘Yan 25′) storage roots - Shuxian Geng; Zihan Liu; John B. Golding; Penta Pristijono; Zunfu Lv; Guoquan Lu; Huqing Yang; Lei Ru; Yongxin Li (Postharvest Biology and Technology, 2023)

Insights into the influence on 2,4,6-trichlorophenol microbial reductive dechlorination process by exposure to microplastics - Jia-Qi Yang; Zhi-Ling Li; Bin Wu; Ya-Ru Jin; Di Cao; Jun Nan; Xue-Qi Chen; Wen-Zong Liu; Shu-Hong Gao; Ai-Jie Wang (Journal of Hazardous Materials, 2023)

Metallurgical performance and structural characteristics of cokes of hypercoal prepared from the mixture of low-rank coal and biomass residue - Jun Zhao; Hong Liu; Haochen Zhang; Xiaolin Song; Haibin Zuo; Guangwei Wang; Zhigao Xu; Ming Wu; Zhenyue Zhang; Ru'an Chi (Fuel, 2023)

Luteolin ameliorates palmitate-induced lipotoxicity in hepatocytes by mediating endoplasmic reticulum stress and autophagy - Chun-Yin Huang; Haw-Wen Chen; Chia-Wen Lo; Yu-Ru Wang; Chien-Chun Li; Kai-Li Liu; Chong-Kuei Lii (Food and Chemical Toxicology, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Association between long-term ambient ozone exposure and attention-deficit/hyperactivity disorder symptoms among Chinese children - Peien Zhou; Wangjian Zhang; Yu-Jie Xu; Ru-Qing Liu; Zhengmin Qian; Stephen Edward McMillin; Elizabeth Bingheim; Li-Zi Lin; Xiao-Wen Zeng; Bo-Yi Yang; Li-Wen Hu; Wen Chen; et al. (Environmental Research, 2023)

Identifying the impact of Fe nanoparticles encapsulated by nitrogen-doped carbon to Fe single atom sites for boosting oxygen reduction reaction toward Zn-air batteries - Wen-Jun Niu; Ying-Yun Yan; Ru-Ji Li; Wei-Wei Zhao; Jiang-Lei Chen; Ming-Jin Liu; Bingni Gu; Wen-Wu Liu; Yu-Lun Chueh (Chemical Engineering Journal, 2023)

Preparation and application of recyclable polymer aerogels from styrene-maleic anhydride alternating copolymers - Yuan Yao; Xiaohong Zhang; Zhaoyan Guo; Wenlu Liu; Chenxi Hu; Yue Ru; Liangdong Zhang; Chao Jiang; Jinliang Qiao (Chemical Engineering Journal, 2023)

Meta-analysis of neonicotinoid insecticides in global surface waters - Jianqiao Wang; Ru Yin; Yilin Liu; Beijia Wang; Nana Wang; Pengfei Xiao; Tangfu Xiao; Hirofumi Hirai (Environmental Science and Pollution Research, 2023)

Three-dimensional hydroxylated covalent organic frameworks for solid phase extraction of glucocorticoids in environmental water samples - Chuqing Liu; Guiju Xu; Baoyu Li; Xiaoli Wang; Jin-Ming Lin; Ru-Song Zhao (Analytica Chimica Acta, 2023)

A Bounded Near-Bottom Cruise Trajectory Planning Algorithm for Underwater Vehicles - Jingyu Ru; Han Yu; Hao Liu; Jiayuan Liu; Xiangyue Zhang; Hongli Xu (Journal of Marine Science and Engineering, 2022)
The trajectory planning algorithm of underwater vehicle near-bottom cruise is important to scientific investigation, industrial inspection, and military affairs. An autonomous underwater vehicle (AUV) often faces the problems of complex underwater environment and large cruise area in a real environment, and some robots must hide themselves during the cruise. However, to the best of our knowledge, few studies have focused on trajectory planning algorithms for AUVs with multiple constraints on large-scale maps. The currently used algorithms are not effective at solving length-constraint problems, and the mainstream trajectory planning algorithms for robots cannot be directly applied to the needs of underwater vehicle sailing near the bottom. Therefore, we present a bounded ridge-based trajectory planning algorithm (RA*) for an AUV to go on a near-bottom cruise. In the algorithm, we design a safety map based on a spherical structure to ensure the safe operation of the robot. In addressing the length-constraint problem and large-scale map planning problem, this paper proposes a two-stage framework for RA*, which designs map compression and parallel computation using a coarse-fine planning framework to solve the large-scale trajectory planning problem and uses a bounded search method to meet the trajectory planning requirements of length constraint. In this study, experiments based on the virtual ocean ridge are conducted, and the results validate the effectiveness and efficiency of the proposed RA* with MCPC algorithm framework.

Physiological responses of marine Chlorella sp. exposed to environmental levels of triphenyltin - Zhihan Cao; Ping Li; Jinchuang Ru; Xuqian Cao; Xu Wang; Bin Liu; Zhi-Hua Li (Environmental Science and Pollution Research, 2022)

The central role of GmGLP20.4 in root architecture modifications of soybean under low-nitrogen stress - Wei Wang; Jiajia Li; Muhammad Nadeem; Jianxin Wang; Ru Huang; Qian Liu; Wenqiao Fan; Haowei Zheng; Long Yan; Xiaobo Wang (Theoretical and Applied Genetics, 2022)

A UAV-aided prediction system of soil moisture content relying on thermal infrared remote sensing - W. Li; C. Liu; Y. Yang; M. Awais; W. Li; P. Ying; W. Ru; M. J. M. Cheema (International Journal of Environmental Science and Technology, 2022)

Discovery of the oncogenic MDM2, a direct binding target of berberine and a potential therapeutic, in multiple myeloma - Chuting Li; Ru Su; Xiuyuan Wang; Guiping Huang; Yanjun Liu; Juhua Yang; Zhao Yin; Chunming Gu; Jia Fei (Functional & Integrative Genomics, 2022)

High- and low-temperature fracture behavior of pervious asphalt mixtures under different freeze–thaw cycles based on acoustic emission technique - Tianmin Wang; Yu Chen; Changqi Zhu; Haifeng Liu; Chenghao Ma; Xing Wang; Ru Qu (Arabian Journal of Geosciences, 2022)

Siccirubricoccus soli sp. nov., a novel bacterial species isolated from Jiaozi Mountain soil - Guo-Xing Zhu; Ya-Jie Wu; Yan-Ru Cao; Bing-Jun Fan; Yu Jiao; Xiu-Li Hou; Zi-Chao Liu; Yue Zhang; Jiang-Bo He; Lian-Ming Liang (Antonie van Leeuwenhoek, 2022)

Deletions in GSN gene associated with growth traits of four Chinese cattle breeds - Ao Qi; Wenxiu Ru; Yangkai Liu; Yu Yang; Jia Tang; Haiyan Yang; Shuling Yang; Kaixing Qu; Xianyong Lan; Chuzhao Lei; Bizhi Huang; Hong Chen (Molecular Genetics and Genomics, 2022)

The Effect of Co-Exposure to Glyphosate, Cadmium, and Arsenic on Chronic Kidney Disease - Junne-Ming Sung; Wei-Hsiang Chang; Kuan-Hung Liu; Chung Yu Chen; Trias Mahmudiono; Wan-Ru Wang; Ho-Chi Hsu; Zhen-Yi Li; Hsiu-Ling Chen (Exposure and Health, 2022)

ACOT7 protects epidermal stem cells against lipid peroxidation - Guang Zhang; Jiaxu Ma; Zhenjie Wu; Guoqi Cao; Chunyan Liu; Ru Song; Rui Sun; Aoyu Chen; Yibing Wang; Siyuan Yin (In Vitro Cellular & Developmental Biology - Animal, 2022)
Epidermal stem cells (ESCs) are critical for skin regeneration and repair. Previous studies have shown that ESCs are susceptible to oxidative stress, which in turn leads to lipid peroxidation and affects skin repair. Our study aims to explore how ESCs resist lipid peroxidation. By performing proteomics analysis, we found that the expression of Acyl-CoA thioesterase 7 (ACOT7) was positively correlated with the concentration of transferrin. Overexpression adenovirus vectors of ACOT7 were constructed and transfected into ESCs. Levels of lipid peroxidation by flow cytometry, cell viabilities, and MDA levels were measured. The results revealed that ACOT7 could inhibit lipid peroxidation, reduce the level of malondialdehyde (MDA), and improve the survival rate of ESCs induced by H 2 O 2 , Erastin, and RSL3. Our data suggest that ACOT7 has an effect on protecting ESCs against iron-dependent lipid peroxidation.

A fly GWAS for purine metabolites identifies human FAM214 homolog medusa, which acts in a conserved manner to enhance hyperuricemia-driven pathologies by modulating purine metabolism and the inflammatory response - Tyler A. U. Hilsabeck; Ru Liu-Bryan; Tracy Guo; Kenneth A. Wilson; Neelanjan Bose; Daniel Raftery; Jennifer N. Beck; Sven Lang; Kelly Jin; Christopher S. Nelson; Tal Oron; Marshall Stoller; et al. (GeroScience, 2022)

Traffic noise and adiposity: a systematic review and meta-analysis of epidemiological studies - Si-Yu Gui; Ke-Jia Wu; Yue Sun; Yue-Nan Chen; Huan-Ru Liang; Wen Liu; Yao Lu; Cheng-Yang Hu (Environmental Science and Pollution Research, 2022)

Spatiotemporal variations of seasonal temperature at different percentiles in the three provinces of northeast China from 1961 to 2019 - Yaxue Yang; Huixiao Wang; Changming Liu; Ru Feng; Yu Wang; Hongfang Li (International Journal of Climatology, 2022)
The three provinces of northeast China (NEPs) were one of the major grain producing areas in China and has undergone significant climate warming during past decades. However, nowadays researches on climate warming mostly focused on variations of mean temperature or temperature extremes, which missed much information in the other parts of temperature. Therefore, taken NEPs as study area, variations of maximum temperature (Tmax), minimum temperature (Tmin) and diurnal temperature range (DTR) at every 10% percentile from 1961 to 2019 in NEPs were analysed at seasonal scale. The abrupt changes and decadal shifts of Tmax, Tmin and DTR at different percentiles were further highlighted. Results show that (a) for either regional average or station cases, fluctuations of daily Tmax and daily Tmin both decreased in spring and winter, but increased in autumn. In summer, fluctuations of daily Tmin decreased while those of daily Tmax increased. (b) Spatially, Tmax heated up more in south of NEPs at lower percentiles, and in northwest of NEPs at higher percentiles in spring, summer and winter. Tmin and DTR overall showed consistent spatial differences that changes in north and northwest of NEPs were with greater magnitudes. (c) In spring and winter, the higher Tmax/Tmin had earlier abrupt changes than lower Tmax/Tmin, while in summer and autumn, the abrupt changes occurred earlier for lower Tmax/Tmin. (d) In winter, overwhelming positive shifts were significant before 2000, but turned negative after 2000. In summer, Tmax heated up quickly since 1990s and Tmin since 1980s. Shifts in spring and autumn varied during different periods and generally presented alternative warming at higher and lower percentiles. The research can help better depict the warming patterns and figure out the detailed warming procedures in NEPs, which is a strong supplement for current climate change research.

Dataset-based assessment of heavy metal contamination in freshwater fishes and their health risks - Xiao-Bo Liu; Congtian Lin; Yang-Yu Wu; Hai-Ning Huang; Li-Ting Zhu; Ru Jiang; Qiansheng Huang (Environmental Science and Pollution Research, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Clinical efficacy of melatonin as adjunctive therapy to non-surgical treatment of periodontitis: a systematic review and meta-analysis - Ru-Yue Liu; Lin Li; Zhong-Ti Zhang; Ting Wu; Shuang Lin; Xu-Tong Zhang (Inflammopharmacology, 2022)

Exploiting Sentinel-1 data and machine learning–based random forest for collectively mapping rice fields in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Youg-Sin Cheng; Piero Toscano; Chein-Hui Syu; Horng-Yuh Guo; Shu-Ling Chen; Tsang-Sen Liu; Yi-Ting Zhang; Huan-Sheng Lin; Shih-Hsiang Chen; et al. (Applied Geomatics, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Synthesis and biological activity of amide derivatives derived from natural product Waltherione F - Hongbin Fang; Zhanfang Chen; Xuewen Hua; Wenrui Liu; Chenmeng Xue; Yi Liu; Xiaohe Zhu; Man Yuan; Shuang Cheng; Bingxiang Wang; Jing Ru; Dzmitry Bazhanau; et al. (Medicinal Chemistry Research, 2022)

Land development suitability analysis for transport planning evaluation and optimization in mountainous ecological region - Gao-ru Zhu; Man Wang; Qi-li Li; Jie Liu; Yan-ni Zhao; Jia-wei Gao; Hong-lei Xu (Journal of Mountain Science, 2022)

Haloterrigena gelatinilytica sp. nov., a new extremely halophilic archaeon isolated from salt-lake - Bing-Bing Liu; Nimaichand Salam; Manik Prabhu Narsing Rao; Shuang Cheng; Yuan-Guo Xie; Lai-You Wang; Yuan-ru Zhang; Xin-Yuan Yu; Shu-xian Guo; Wen-Jun Li (Archives of Microbiology, 2022)

A New Scheme for Capturing Global Conditional Nonlinear Optimal Perturbation - Siyuan Liu; Qi Shao; Wei Li; Guijun Han; Kangzhuang Liang; Yantian Gong; Ru Wang; Hanyu Liu; Song Hu (Journal of Marine Science and Engineering, 2022)
Conditional nonlinear optimal perturbation (CNOP) represents the initial perturbation that satisfies a certain physical constraint condition, and leads to a maximum prediction error at the moment of prediction. The CNOP method is a useful tool in studying atmosphere and ocean predictability problems. Generally, the optimization algorithm based on the gradient of the cost function to compute CNOP requires an initial guess. The traditional scheme randomly chooses the initial guess of CNOP within the constraint range and therefore this scheme is called RIG-CNOP. However, the RIG-CNOP scheme reduces the probability of capturing the global CNOP in many cases, such as the prediction model is strongly nonlinear or long-term prediction is performed, or multiple extreme values existed in the cost function. Considering the limitations of the RIG-CNOP scheme, we propose a new initial guess selection scheme. In this scheme, we first pre-analyze a series of random initial guesses, and then, an optimal initial guess is selected. The above process replaces the initial guess selection scheme in the traditional scheme, which is called PAIG-CNOP. Numerical experiments are conducted utilizing the Lorenz-63 model. Also, to compare the performance of the PAIG-CNOP method with the RIG-CNOP method in capturing global CNOP, the CNOP and the maximum cost function value (MCFV) obtained by the filtering method (FM) are used as benchmarks (this value is called FMMCFV in brief). The experimental results show that even the prediction model is strongly nonlinear or the prediction time is long, or the cost function has multiple extreme values, the PAIG-CNOP method can capture the global CNOP with a high probability. The results show that the PAIG-CNOP method has a higher probability of capturing the global CNOP than the RIG-CNOP method. In addition, we use an ensemble-based technique in the computation of gradients, thus avoiding the use of adjoint techniques in the maximization process. Due to the attractive features of the new method, the PAIG-CNOP method is an efficient and useful method for solving CNOP, it can be more easily applied to obtain the global CNOP of operational prediction models.

Moisture mediates temperature-growth couplings of high-elevation shrubs in the Tibetan plateau - Yang Han; Yafeng Wang; Bo Liu; Ru Huang; J. Julio Camarero (Trees, 2022)

NNMT is induced dynamically during beige adipogenesis in adipose tissues depot-specific manner - Ru Jia; Xiaojing Wei; Jianan Jiang; Zhao Yang; Jiaqi Huang; Jing Liu; Jianqun Yan; Xiao Luo (Journal of Physiology and Biochemistry, 2022)

Peripheral Administration of an Opioid Peptide Analog Ameliorates Morphine-Produced Hyperalgesia in a Spared Nerve Injury Model - Yuan Wang; Meng-tao Ma; Jing Wang; Chao-zhen-yi Han; Kai Li; Qiao-min Ru; Na Li; Xin Liu; Rui Wang (International Journal of Peptide Research and Therapeutics, 2022)

Evolutionary origin of a tetraploid Allium species on the Qinghai–Tibet Plateau - Minjie Li; Zeyu Zheng; Juncheng Liu; Yongzhi Yang; Guangpeng Ren; Dafu Ru; Shangzhe Zhang; Xin Du; Tao Ma; Richard Milne; Jianquan Liu (Molecular Ecology, 2021)
Extinct taxa may be detectable if they were ancestors to extant hybrid species, which retain their genetic signature. In this study, we combined phylogenomics, population genetics and fluorescence in situ hybridization (GISH and FISH) analyses to trace the origin of the alpine tetraploid Allium tetraploideum (2 n = 4 x = 32), one of the five known members in the subgenus Cyathophora . We found that A. tetraploideum was an obvious allotetrapoploid derived from ancestors including at least two closely related diploid species, A. farreri and A. cyathophorum , from which it differs by multiple ecological and genomic attributes. However, these two species cannot account for the full genome of A. tetraploideum , indicating that at least one extinct diploid is also involved in its ancestry. Furthermore, A. tetraploideum appears to have arisen via homoploid hybrid speciation (HHS) from two extinct allotetraploid parents, which derived in turn from the aforementioned diploids. Other modes of origin were possible, but all were even more complex and involved additional extinct ancestors. Our study together highlights how some polyploid species might have very complex origins, involving both HHS and polyploid speciation and also extinct ancestors.

Novel Alcaligenes ammonioxydans sp. nov. from wastewater treatment sludge oxidizes ammonia to N 2 with a previously unknown pathway - Meng‐Ru Wu; Ting‐Ting Hou; Ying Liu; Li‐Li Miao; Guo‐Min Ai; Lan Ma; Hai‐Zhen Zhu; Ya‐Xin Zhu; Xi‐Yan Gao; Craig W. Herbold; Michael Wagner; De‐Feng Li; et al. (Environmental Microbiology, 2021)
Summary Heterotrophic nitrifiers are able to oxidize and remove ammonia from nitrogen‐rich wastewaters but the genetic elements of heterotrophic ammonia oxidation are poorly understood. Here, we isolated and identified a novel heterotrophic nitrifier, Alcaligenes ammonioxydans sp. nov. strain HO‐1, oxidizing ammonia to hydroxylamine and ending in the production of N 2 gas. Genome analysis revealed that strain HO‐1 encoded a complete denitrification pathway but lacks any genes coding for homologous to known ammonia monooxygenases or hydroxylamine oxidoreductases. Our results demonstrated strain HO‐1 denitrified nitrite (not nitrate) to N 2 and N 2 O at anaerobic and aerobic conditions respectively. Further experiments demonstrated that inhibition of aerobic denitrification did not stop ammonia oxidation and N 2 production. A gene cluster ( dnfT1RT2ABCD ) was cloned from strain HO‐1 and enabled E . coli accumulated hydroxylamine. Sub‐cloning showed that genetic cluster dnfAB or dnfABC already enabled E . coli cells to produce hydroxylamine and further to 15 N 2 from ( 15 NH 4 ) 2 SO 4 . Transcriptome analysis revealed these three genes dnfA , dnfB and dnfC were significantly upregulated in response to ammonia stimulation. Taken together, we concluded that strain HO‐1 has a novel dnf genetic cluster for ammonia oxidation and this dnf genetic cluster encoded a previously unknown pathway of di rect amm onia ox idation (Dirammox) to N 2 .

Recent progress of oridonin and its derivatives for cancer therapy and drug resistance - Yong-Feng Guan; Xiu-Juan Liu; Xiao-Jing Pang; Wen-Bo Liu; Guang -Xi Yu; Yin -Ru Li; Yan-Bing Zhang; Jian Song; Sai-Yang Zhang (Medicinal Chemistry Research, 2021)

The occurrence order and cross-talk of different tRNA modifications - Jing Li; Wen-Yu Zhu; Wen-Qing Yang; Cai-Tao Li; Ru-Juan Liu (Science China Life Sciences, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Energy Sources Generation and Energy Cascades along the Kuroshio East of Taiwan Island and the East China Sea - Ru Wang; Yijun Hou; Ze Liu (Journal of Marine Science and Engineering, 2021)
There are multi-spatial-scale ocean dynamic processes in the western boundary current region, so the budget of energy source and sink in the Kuroshio Current area can describe the oceanic energy cycle and transformation more accurately. The slope of the one-dimensional spectral energy density varies between −5/3 and −3 in the wavenumber range of 0.02–0.1 cpkm, indicating an inverse energy cascade in the Kuroshio of Taiwan Island and the East China Sea. According to the steady-state energy evolution, an energy source must be present. The locations of energy sources were identified using the spectral energy transfer calculated by 24 years of Ocean General Circulation Model for the Earth Simulator (OFES) data. At the sea surface, the kinetic energy (KE) sources are mainly within 23.2°–25.6° Nand 28°–29° N at less than 0.02 cpkm and within 23.2°–25° N and 26°–30° N at 0.02–0.1 cpkm. The available potential energy (APE) sources are mainly within 22°–28° N and 28.6°–30° N at less than 0.02 cpkm and within 22.6°–24.6° N, 25.4°–28° N and 29.2°–30° N at 0.02–0.1 cpkm. Beneath the sea surface, the energy sources are mainly above 400 m depth. Wind stress and density differences are primarily responsible for the KE and APE sources, respectively. Once an energy source is formed, to maintain a steady state, energy cascades (mainly inverse cascades by calculating spectral energy flux) will be engendered. By calculating the energy flux at 600 m depth, KE changes from inflow (sink) to outflow (source), and the conversion depth of source and sink is 380 m. However, outflow of the APE behaves as the source.

An Infrared Touch System for Automatic Behavior Monitoring - Qingqing Liu; Xing Yang; Ru Song; Junying Su; Moxuan Luo; Jinling Zhong; Liping Wang (Neuroscience Bulletin, 2021)
Key requirements of successful animal behavior research in the laboratory are robustness, objectivity, and high throughput, which apply to both the recording and analysis of behavior. Many automatic methods of monitoring animal behavior meet these requirements. However, they usually depend on high-performing hardware and sophisticated software, which may be expensive. Here, we describe an automatic infrared behavior-monitor (AIBM) system based on an infrared touchscreen frame. Using this, animal positions can be recorded and used for further behavioral analysis by any PC supporting touch events. This system detects animal behavior in real time and gives closed-loop feedback using relatively low computing resources and simple algorithms. The AIBM system automatically records and analyzes multiple types of animal behavior in a highly efficient, unbiased, and low-cost manner.

Purinergic smooth muscle contractions in the human prostate: estimation of relevance and characterization of different agonists - Annabel Spek; Bingsheng Li; Beata Rutz; Anna Ciotkowska; Ru Huang; Yuhan Liu; Ruixiao Wang; Frank Strittmatter; Raphaela Waidelich; Christian G. Stief; Martin Hennenberg (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
Non-adrenergic prostate smooth muscle contractions may account for the limited effectiveness of α 1 -adrenoceptor antagonists, which are the first-line option for medical treatment of voiding symptoms suggestive of benign prostatic hyperplasia. In non-human prostates, purinergic agonists induce contractions reaching similar magnitudes as α 1 -adrenergic contractions. However, evidence for the human prostate is highly limited, and pointed to much weaker purinergic contractions. Here, we examined contractions of different purinergic agonists in human prostate tissues. Tissues were obtained from radical prostatectomy. Contractions were studied in an organ bath, and expression of purinergic receptors was studied by RT-PCR. Electric field stimulation (EFS)–induced contractions amounted to 104% of KCl-induced contractions (95% CI: 84–124%). From all tested agonists, only ATP induced concentration-dependent contractions, reaching an average maximum of 18% (12–24%) of KCl. Maximum tensions following application of other agonists averaged to 7.1% of KCl for α,β-methylene-ATP (1.8–12.4%), 3.9% for β,γ-methylene-ATP (2.0–5.4%), 3.1% for 2-methylthio-ATP (− 0.1–6.3%), and 5.1% for ATPγS (1.0–9.2%). Responses were not affected by the P2X antagonist NF023 or the P2Y antagonist PPADS. mRNA expression of P2X1-4 correlated with expression of a marker for catecholaminergic nerves, although neither ATP, NF023, nor PPADS changed EFS-induced contractions. Correlation between expression of receptors and the smooth muscle marker calponin was not observed. Our findings point to a low relevance of purinergic contractions in the human prostate, compared to other contractile stimuli in the human prostate and compared to purinergic contractions in non-human prostates. Purinergic contractions in the human prostate are not sensitive to NF023 or PPADS.

OsGSTU6 Contributes to Cadmium Stress Tolerance in Rice by Involving in Intracellular ROS Homeostasis - Xiu-Qing Jing; Meng-Ru Zhou; Xiu-Min Nie; Lu Zhang; Peng-Tao Shi; Abdullah Shalmani; Hai Miao; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2021)

Prediction of oral hepatotoxic dose of natural products derived from traditional Chinese medicines based on SVM classifier and PBPK modeling - Size Li; Yiqun Yu; Xiaolan Bian; Li Yao; Min Li; Yan-Ru Lou; Jing Yuan; Hai-shu Lin; Lucy Liu; Bing Han; Xiaoqiang Xiang (Archives of Toxicology, 2021)

Double Weighted Sparse Nonnegative Tensor Factorization for Hyperspectral Unmixing - Heng-Chao Li; Shuang Liu; Xin-Ru Feng; Rui Wang; Yong-Jian Sun (International Journal of Remote Sensing, 2021)

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

Tracing consumption patterns of stimulants, opioids, and ketamine in China by wastewater-based epidemiology - Si-Yu Liu; Wen-Jing Yu; Yi-Ru Wang; Xue-Ting Shao; De-Gao Wang (Environmental Science and Pollution Research, 2021)

Re-use of wasted sludge to treat industrial pollutants - Ru Wang; Li-ping Yu; Bibi Saima Zeb; Lin-jie Yuan; Meng-yu Liu; Lin-jiang Yuan (Water, Air, & Soil Pollution, 2021)

FOXG1 Directly Suppresses Wnt5a During the Development of the Hippocampus - Yang Ni; Bin Liu; Xiaojing Wu; Junhua Liu; Ru Ba; Chunjie Zhao (Neuroscience Bulletin, 2021)

Nonadditive and Legacy Effects of Spring and Autumn Warming on Soil Respiration in an Old-Field Grassland - Shijie Ning; Jian Song; Jingyi Ru; Zhenxing Zhou; Jiajia Zhang; Xianghui Liu; Yan Hui; Yafei Ma; Shiqiang Wan (Ecosystems, 2021)

Alkaloids and phenylpropanoid from Rhizomes of Arundo donax L - Qing-Ru Liu; Juan Li; Xiao-Fang Zhao; Bo Xu; Xing-Hua Xiao; Jie Ren; Shun-Xiang Li (Natural Product Research, 2021)

TRIP13 promotes the proliferation and invasion of lung cancer cells via the Wnt signaling pathway and epithelial–mesenchymal transition - Zhi-Han Li; Lei Lei; Liang-Ru Fei; Wen-Jing Huang; Yi-Wen Zheng; Mai-Qing Yang; Zhao Wang; Chen-Chen Liu; Hong-Tao Xu (Journal of Molecular Histology, 2021)

A new cyclic peptide from the fibrous root of Pseudostellaria heterophylla - Xiao-fei Zhao; Qian Zhang; Han-tao Zhao; Yan-da Zhang; Han-ru Liu; Lu-jiang Yuan; Qian-feng Chen (Natural Product Research, 2020)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Functional connectivity changes of nucleus Accumbens Shell portion in left mesial temporal lobe epilepsy patients - Ru Yang; Xixi Zhao; Jun Liu; Xufeng Yao; Feng Hou; Yikai Xu; Qianjin Feng (Brain Imaging and Behavior, 2020)

Rapid identification of landslide, collapse and crack based on low-altitude remote sensing image of UAV - Xu-gang Lian; Zou-jun Li; Hong-yan Yuan; Ji-bo Liu; Yan-jun Zhang; Xiao-yu Liu; Yan-ru Wu (Journal of Mountain Science, 2020)

Characteristics of methane emissions in the Living Water Garden in Chengdu City from 2012 to 2017 - Ru Xue; Xiaoling Liu; Xiaoying Fu; Hongbing Luo; Ke Zhang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Xiaoting Li; Shuzhi Fu; Aiping Pu; et al. (Environmental Science and Pollution Research, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

The Intruding Wolbachia Strain from the Moth Fails to Establish Itself in the Fruit Fly Due to Immune and Exclusion Reactions - Xin-Chao Liu; Yue-Ru Li; Bei Dong; Zheng-Xi Li (Current Microbiology, 2020)

Comparative Variations of Extractive Nitrogenous Components and Quality in Fresh Muscle and Dried Product of Rabbitfish ( Siganus fuscescens ) in Taiwan - Yu-Ru Huang; Wan-Yi Huang; Hsiao-Chin Jen; Bi-Yu Liu; Ken-Meng Huang; Deng Fwu Hwang (Journal of Aquatic Food Product Technology, 2020)

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities - Tao He; Yi Liu; Rui-Feng Xiong; Xiao-Yu Li; Shou-Feng Wang; Chun-Ru Cheng (Natural Product Research, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Impaired Parahippocampal Gyrus–Orbitofrontal Cortex Circuit Associated with Visuospatial Memory Deficit as a Potential Biomarker and Interventional Approach for Alzheimer Disease - Lin Zhu; Zan Wang; Zhanhong Du; Xinyang Qi; Hao Shu; Duan Liu; Fan Su; Qing Ye; Xuemei Liu; Zheng Zhou; Yongqiang Tang; Ru Song; et al. (Neuroscience Bulletin, 2020)

Endophytic colonization by Beauveria bassiana increases the resistance of tomatoes against Bemisia tabaci - Qiu-Yang Wei; Ya-Ying Li; Chen Xu; Yi-Xia Wu; Ya-Ru Zhang; Huai Liu (Arthropod-Plant Interactions, 2020)
Beauveria bassiana , an entomopathogenic fungus, can exist asymptomatically as an endophyte in many plants. This study aimed to determine the efficiency of B. bassiana colonization of tomato plants using different inoculation methods, and how colonization of the host plant affects the key pest of tomato, the whitefly Bemisia tabaci . To confirm fungal colonization efficiency, nested PCR technique was used to detect B. bassiana sequences in Solanum lycopersicum . Distribution of the fungus within the plant parts was determined by selective medium. Tomato growth parameters were determined with plants that had been inoculated using direct spraying or irrigation of the rhizosphere. B. tabaci performance assays were carried out in a cage, and preference to treatments was determined using Y-tube olfactometer studies. Results show that B. bassiana can effectively colonize tomato, with colonization rate using leaf spraying reaching 100% within 14 days. Fungal presence was not uniformly distributed among plant parts, but was biased towards the inoculation sites. For inoculation, conidial suspension sprayed at 1 × 10 8 conidia/ml resulted in the highest number of isolated colonies in leaf tissue, 8.5 ± 2.02 colonies per 2 g of fresh tissue ( F 4,19 = 2.779, P = 0.045), and reached the lowest with root treatment. Although only small differences were observed among the growth indicators, leaf spray inoculation resulted in a significant positive influence on plant growth (PC1 55.7% contributions scores = 2.645) in further Principal component analysis. As for the feeding selectivity, B. tabaci preferred uninoculated plants. In Y-tube olfactometer assay, 80.5% of adults selected uninoculated plants. These findings add to the understanding of the interactions between B. bassiana and plants and indicate the potential of expanding the use of entomopathogenic fungi for crop protection.

Occurrence and distribution of priority pharmaceuticals in the Yellow River and the Huai River in Henan, China - Jinglan Feng; Qi Liu; Xiangli Ru; Nannan Xi; Jianhui Sun (Environmental Science and Pollution Research, 2020)

Taxonomy of the yeast genus Vanderwaltozyma and proposal of Vanderwaltozyma meishanica sp. nov., Vanderwaltozyma huisunica sp. nov., and Vanderwaltozyma molinica sp. nov. - Chin-Feng Chang; Yi-Ru Liu; Gennadi I. Naumov; Elena S. Naumova; Ching-Fu Lee (Antonie van Leeuwenhoek, 2020)

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

Allopatric divergence and hybridization within Cupressus chengiana (Cupressaceae), a threatened conifer in the northern Hengduan Mountains of western China - Jialiang Li; Richard I. Milne; Dafu Ru; Jibin Miao; Wenjing Tao; Lei Zhang; Jingjing Xu; Jianquan Liu; Kangshan Mao (Molecular Ecology, 2020)
Having a comprehensive understanding of population structure, genetic differentiation and demographic history is important for the conservation and management of threatened species. High‐throughput sequencing (HTS) provides exciting opportunities to address a wide range of factors for conservation genetics. Here, we generated HTS data and identified 266,884 high‐quality single nucleotide polymorphisms from 82 individuals of Cupressus chengiana , to assess population genomics across the species' full range, comprising the Daduhe River (DDH), Minjiang River (MJR) and Bailongjiang River (BLJ) catchments in western China. admixture , principal components analysis and phylogenetic analyses indicated that each region contains a distinct lineage, with high levels of differentiation between them (DDH, MJR and BLJ lineages). MJR was newly distinguished compared to previous surveys, and evidence including coalescent simulations supported a hybrid origin of MJR during the Quaternary. Each of these three lineages should be recognized as an evolutionarily significant unit (ESU), due to isolation, differing genetic adaptations and different demographic history. Currently, each ESU faces distinct threats, and will require different conservation strategies. Our work shows that population genomic approaches using HTS can reconstruct the complex evolutionary history of threatened species in mountainous regions, and hence inform conservation efforts, and contribute to the understanding of high biodiversity in mountains.

Genome-Wide Identification of Malectin/Malectin-Like Domain Containing Protein Family Genes in Rice and Their Expression Regulation Under Various Hormones, Abiotic Stresses, and Heavy Metal Treatments - Xiu-Qing Jing; Abdullah Shalmani; Meng-Ru Zhou; Peng-Tao Shi; Izhar Muhammad; Yi Shi; Rahat Sharif; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2020)

Collagen-binding basic fibroblast growth factor improves functional remodeling of scarred endometrium in uterine infertile women: a pilot study - Peipei Jiang; Xiaoqiu Tang; Huiyan Wang; Chenyan Dai; Jing Su; Hui Zhu; Minmin Song; Jingyu Liu; Ziqing Nan; Tong Ru; Yaling Li; Jingmei Wang; et al. (Science China Life Sciences, 2019)

Development of Human in vitro Brain-blood Barrier Model from Induced Pluripotent Stem Cell-derived Endothelial Cells to Predict the in vivo Permeability of Drugs - Yuan Li; Xueying Sun; Houfu Liu; Liang Huang; Guofeng Meng; Yu Ding; Wenji Su; Jiaqi Lu; Sophie Gong; Georg C. Terstappen; Ru Zhang; Wandong Zhang (Neuroscience Bulletin, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Cytoplasmic SIRT1 inhibits cell migration and invasion by impeding epithelial–mesenchymal transition in ovarian carcinoma - Tong Yang; Ru Zhou; Shentong Yu; Shuhong Yu; Zhuqing Cui; Peizhen Hu; Jinsong Liu; Qing Qiao; Jing Zhang (Molecular and Cellular Biochemistry, 2019)

A tree ring-based winter temperature reconstruction for the southeastern Tibetan Plateau since 1340 CE - Ru Huang; Haifeng Zhu; Eryuan Liang; Bo Liu; Jiangfeng Shi; Ruibo Zhang; Yujiang Yuan; Jussi Grießinger (Climate Dynamics, 2019)

Transformation Mechanism of a Fault and Its Associated Microstructures in Low-Porosity Rocks: A Case Study of the Tanan Depression in the Hailar-Tamtsag Basin - Ru Jia; Bo Liu; Xiaofei Fu; Lei Gong; Zhida Liu (Journal of Marine Science and Engineering, 2019)
Faults have complex internal structures, which can be divided into the fault core and the damaged zone. During the fault formation process, the damaged zone will develop a large number of fractures cross cutting the adjacent host rocks, where the size and density of fractures would decrease as a function of distance from the fault core. Statistics show that compared with the host rocks, the rock’s secondary porosity may significantly get improved until it is 5%–10% higher than the host rock’s, and the permeability could be increased from zero to six orders of magnitude higher where fractures are developed. Based on the distribution of the fault core and damaged zone, we established an idealized geologic model to analyze the influence of the fault associated microstructures on the fluid flow efficiency. The results demonstrated that the reservoir property will be effectively improved when the fractures are developed to a certain magnitude, which will provide an advantageous conduit for fluid flow. The physical properties of wells are significantly different between the reservoirs transformed by the fractures and the reservoirs that have not been affected. The reservoir unit near faults has been modified by the associated fractures improving the reservoir quality. In addition, the portions of the reservoir farther from the fault core are less influenced and retain their initial poor characteristics. In order to evaluate the enhanced reservoir properties caused by faults and associated fractures, we performed statistical analysis of valid porosity ratio of the Nantun reservoirs as a function of the distance from 49 wells to faults in the research area. The results of this study demonstrated that connected fractures enhance the properties of the reservoirs and there is a distinct range that separates oil producing wells and water producing ones. This phenomenon verifies that faults are important and must be considered carefully during the exploration and production for hydrocarbon to provide higher quality reservoirs.

Differential PCR detection of Streptococcus agalactiae and Streptococcus iniae in tilapia ( Oreochromis niloticus ) by a single primer pair - Miao Cui; Huijie Zhang; Jingjing Li; Ru Liu; Min Wu; Delin Xu; Qizhong Zhang (Journal of Fish Diseases, 2019)

Identification and characterisation of a glycine-rich RNA-binding protein as an endogenous suppressor of RNA silencing from Nicotiana glutinosa - Xu Huang; Ru Yu; Wenjing Li; Liwei Geng; Xiuli Jing; Changxiang Zhu; Hongmei Liu (Planta, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Thalamocortical dysconnectivity in premenstrual syndrome - Peng Liu; Ying Wei; Hai Liao; Yingying Fan; Ru Li; Nana Feng; Gaoxiong Duan; Demao Deng; Wei Qin (Brain Imaging and Behavior, 2019)

De novo assembly of white poplar genome and genetic diversity of white poplar population in Irtysh River basin in China - Yan-Jing Liu; Xiao-Ru Wang; Qing-Yin Zeng (Science China Life Sciences, 2019)

Andrographolide impairs alpha-naphthylisothiocyanate-induced cholestatic liver injury in vivo - Lei Wang; Fei Cao; Li-li Zhu; Peng Liu; Yu-ru Shang; Wen-hui Liu; Xin Dong; Hai-dong Bao; Peng Gong; Zhong-yu Wang (Journal of Natural Medicines, 2019)

Detecting and attributing vegetation changes in Taihang Mountain, China - Shi Hu; Fei-yu Wang; Che-sheng Zhan; Ru-xin Zhao; Xiong-guo Mo; Liang-mei-zi Liu (Journal of Mountain Science, 2019)

Geomorphic features of Quaternary glaciation in the Taniantaweng Mountain, on the southeastern Qinghai-Tibet Plateau - Wei Zhang; Le Chai; Ian S Evans; Liang Liu; Ya-peng Li; Jing-ru Qiao; Qian-yu Tang; Bo Sun (Journal of Mountain Science, 2019)

Triterpenoids, megastigmanes and hydroxycinnamic acid derivatives from Anisomeles indica - Quan-Wen Liu; Cai-Hua Chen; Xiao-Feng Wang; Kun Jiang; Shi-Jin Qu; Yi-Ru Dai; Chang-Heng Tan (Natural Product Research, 2019)

Development strategies for the sea cucumber industry in China - Xiaoshang Ru; Libin Zhang; Xiaoni Li; Shilin Liu; Hongsheng Yang (Journal of Oceanology and Limnology, 2019)

Transplantation of UC-MSCs on collagen scaffold activates follicles in dormant ovaries of POF patients with long history of infertility - Lijun Ding; Guijun Yan; Bin Wang; Lu Xu; Yan Gu; Tong Ru; Xiaoying Cui; Lei Lei; Jingyu Liu; Xiaoqiang Sheng; Bin Wang; Chunxue Zhang; et al. (Science China Life Sciences, 2018)

Preparation of attapulgite/TiO2/graphene composite and its application for the photocatalytic degradation of chlorotetracycline - Wenjie Liu; Tao Du; Qianxun Ru; Shixiang Zuo; Chao Yao (Nanotechnology for Environmental Engineering, 2018)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Chloroplast genome sequence of an endangered non-photosynthetic mycoheterotrophic species Monotropastrum sciaphilum (Andres) G. D. Wallace - Qian-Ru Zhao; Zhen-Wen Liu; Chao Shi; Hua Peng; Shu-Gang Lu (Conservation Genetics Resources, 2018)

Population genomic analysis reveals that homoploid hybrid speciation can be a lengthy process - Dafu Ru; Yongshuai Sun; Donglei Wang; Yang Chen; Tianjing Wang; Quanjun Hu; Richard J. Abbott; Jianquan Liu (Molecular Ecology, 2018)
An increasing number of species are thought to have originated by homoploid hybrid speciation ( HHS ), but in only a handful of cases are details of the process known. A previous study indicated that Picea purpurea , a conifer in the Qinghai–Tibet Plateau ( QTP ), originated through HHS from P. likiangensis and P. wilsonii . To investigate this origin in more detail, we analysed transcriptome data for 114 individuals collected from 34 populations of the three Picea species from their core distributions in the QTP . Phylogenetic, principal component and admixture analyses of nuclear SNP s showed the species to be delimited genetically and that P. purpurea was admixed with approximately 60% of its ancestry derived from P. wilsonii and 40% from P. likiangensis . Coalescent simulations revealed the best‐fitting model of origin involved formation of an intermediate hybrid lineage between P. likiangensis and P. wilsonii approximately 6 million years ago (mya), which backcrossed to P. wilsonii to form P. purpurea approximately one mya. The intermediate hybrid lineage no longer exists and is referred to as a “ghost” lineage. Our study emphasizes the power of population genomic analysis combined with coalescent analysis for reconstructing the stages involved in the origin of a homoploid hybrid species over an extended period. In contrast to other studies, we show that these stages can in some instances span a relatively long period of evolutionary time.

Hypoxia and nutrient dynamics affected by marine aquaculture in a monsoon-regulated tropical coastal lagoon - Jing Zhang; ZhuoYi Zhu; Wen Yuan Mo; Su Mei Liu; Dao Ru Wang; Guo Sen Zhang (Environmental Monitoring and Assessment, 2018)

High-degree and broad-spectrum resistance mediated by a combination of NIb siRNA and miRNA suppresses replication of necrotic and common strains of potato virus Y - Ru Yu; Caixia Chen; Weilin Cao; Hongmei Liu; Shumei Zhou; Yunzhi Song; Changxiang Zhu (Archives of Virology, 2018)

Altered topological patterns of brain functional networks in Crohn’s disease - Peng Liu; Ru Li; Chunhui Bao; Ying Wei; Yingying Fan; Yanfei Liu; Geliang Wang; Huangan Wu; Wei Qin (Brain Imaging and Behavior, 2018)

Combined prednisone and levothyroxine improve treatment of severe thrombocytopenia in hepatitis B with compensatory cirrhosis accompanied by subclinical and overt hypothyroidism - Jing Xue; Ru Feng; Haixia Fu; Qian Jiang; Hao Jiang; Jing Lu; Hui Liu; Jingwen Wang; Ting Niu; Xin Wang; Yandi Xie; Hao Wang; et al. (Science China Life Sciences, 2018)

Application of Phragmites australis to remove phenol from aqueous solutions by chemical activation in batch and fixed-bed columns - Sheng-Li Shi; Jun-Ping Lv; Qi Liu; Fang-Ru Nan; Xiao-Yan Jiao; Jia Feng; Shu-Lian Xie (Environmental Science and Pollution Research, 2018)

Cadmium phytoextraction potential of king grass (Pennisetum sinese Roxb.) and responses of rhizosphere bacterial communities to a cadmium pollution gradient - Li Hu; Ru Wang; Xianglin Liu; Bo Xu; Tuanhui Xie; Yunyun Li; Mingkuang Wang; Guo Wang; Yanhui Chen (Environmental Science and Pollution Research, 2018)

Whole-genome sequence and genome annotation of Xanthomonas citri pv. mangiferaeindicae, causal agent of bacterial black spot on Mangifera indica - Feng Liu; Xiong-chang Ou; Ru-lin Zhan (Archives of Microbiology, 2018)

Demographic expansion and genetic load of the halophyte model plant Eutrema salsugineum - Xiao‐Juan Wang; Quan‐Jun Hu; Xin‐Yi Guo; Kun Wang; Da‐Fu Ru; Dmitry A. German; Elizabeth A. Weretilnyk; Richard J. Abbott; Martin Lascoux; Jian‐quan Liu (Molecular Ecology, 2018)
The halophyte model plant Eutrema salsugineum (Brassicaceae) disjunctly occurs in temperate to subarctic Asia and North America. This vast, yet extremely discontinuous distribution constitutes an ideal system to examine long‐distance dispersal and the ensuing accumulation of deleterious mutations as expected in expanding populations of selfing plants. In this study, we resequenced individuals from 23 populations across the range of E . salsugineum . Our population genomic data indicate that E . salsugineum migrated “out of the Altai region” at least three times to colonize northern China, northeast Russia and western China. It then expanded its distribution into North America independently from northeast Russia and northern China, respectively. The species colonized northern China around 33.7 thousand years ago (kya) and underwent a considerable expansion in range size approximately 7–8 kya. The western China lineage is likely a hybrid derivative of the northern China and Altai lineages, originating approximately 25–30 kya. Deleterious alleles accumulated in a stepwise manner from (a) Altai to northern China and North America and (b) Altai to northeast Russia and North America. In summary, E . salsugineum dispersed from Asia to North America and deleterious mutations accumulated in a stepwise manner during the expansion of the species’ distribution.

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Changes of functional connectivity of the anterior cingulate cortex in women with primary dysmenorrhea - Peng Liu; Yanfei Liu; Geliang Wang; Ru Li; Ying Wei; Yingying Fan; Yang Yu; Demao Deng; Wei Qin (Brain Imaging and Behavior, 2018)

Non-structural protein 1 from avian influenza virus H9N2 is an efficient RNA silencing suppressor with characteristics that differ from those of Tomato bushy stunt virus p19 - Ru Yu; Xiuli Jing; Wenjing Li; Jie Xu; Yang Xu; Liwei Geng; Changxiang Zhu; Hongmei Liu (Virus Genes, 2018)

Scopuquinolone B, a new monoterpenoid dihydroquinolin-2(1 H )-one isolated from the coral-derived Scopulariopsis sp. fungus - Xiao-Feng Mou; Xin Liu; Ru-Fang Xu; Mei-Yan Wei; Yao-Wei Fang; Chang-Lun Shao (Natural Product Research, 2018)

Chemical Characteristics of Different Tissues of Spectacled Caiman ( Caiman crocodilus ) - Yu-Ru Huang; Yung-Hsiang Tsai; Ching-Lu Liu; Wei-Zong Syue; Yi-Cheng Su (Journal of Aquatic Food Product Technology, 2018)

Over-expression of the Arabidopsis formate dehydrogenase in chloroplasts enhances formaldehyde uptake and metabolism in transgenic tobacco leaves - Ru Wang; Zhidong Zeng; Hongxia Guo; Hao Tan; Ang Liu; Yan Zhao; Limei Chen (Planta, 2018)

Differential Inhibition of Nav1.7 and Neuropathic Pain by Hybridoma-Produced and Recombinant Monoclonal Antibodies that Target Nav1.7 - Sangsu Bang; Jiho Yoo; Xingrui Gong; Di Liu; Qingjian Han; Xin Luo; Wonseok Chang; Gang Chen; Sang-Taek Im; Yong Ho Kim; Judith A. Strong; Ma-Zhong Zhang; et al. (Neuroscience Bulletin, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Individual susceptibility to arsenic-induced diseases: the role of host genetics, nutritional status, and the gut microbiome - Liang Chi; Bei Gao; Pengcheng Tu; Chih-Wei Liu; Jingchuan Xue; Yunjia Lai; Hongyu Ru; Kun Lu (Mammalian Genome, 2018)

CAT and MDH improve the germination and alleviate the oxidative stress of cryopreserved Paeonia and Magnolia pollen - Meng Xue Jia; Xue Ru Jiang; Jin Xu; Wei Di; Yin Shi; Yan Liu (Acta Physiologiae Plantarum, 2018)

Pentapeptide-insertion scanning mutational analysis of turkey herpesvirus HVT063 reveals residues important for its RNA silencing suppression activity - Gang Jia; Wenjing Li; Meina Fan; Ru Yu; Yang Xu; Liwei Geng; Jiedao Zhang; Changxiang Zhu; Hongmei Liu (Archives of Virology, 2018)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Melatonin increases reactive aggression in humans - Jinting Liu; Ru Zhong; Wei Xiong; Haibo Liu; Christoph Eisenegger; Xiaolin Zhou (Psychopharmacology, 2017)

Clinical Significance of REM Sleep Behavior Disorders and Other Non-motor Symptoms of Parkinsonism - Hong Jin; Jin-Ru Zhang; Yun Shen; Chun-Feng Liu (Neuroscience Bulletin, 2017)

Characteristic differences in essential oil composition of six Zanthoxylum bungeanum Maxim. (Rutaceae) cultivars and their biological significance - Shu-ming Liu; Shi-jun Wang; Si-yao Song; Yong Zou; Jun-ru Wang; Bing-yin Sun (Journal of Zhejiang University-SCIENCE B, 2017)

Combining spatial and spectral information to estimate chlorophyll contents of crop leaves with a field imaging spectroscopy system - Bo Liu; Wenjing Shen; Yue-min Yue; Ru Li; Qingxi Tong; Bing Zhang (Precision Agriculture, 2017)

Inhibitory effect of StCYP707A1 gene on tuberization in transgenic potato - Lu Liu; Rui-Jie Zhang; Wen-Jiao Zhu; Xin-Ru Liu; Ke Shi; Min Chen; Qing Yang (Plant Biotechnology Reports, 2017)

ROS-induced oxidative stress is closely related to pollen deterioration following cryopreservation - Meng Xue Jia; Yin Shi; Wei Di; Xue Ru Jiang; Jin Xu; Yan Liu (In Vitro Cellular & Developmental Biology - Plant, 2017)

Improvement of aquaponic performance through micro- and macro-nutrient addition - Dongyun Ru; Jikai Liu; Zhen Hu; Yina Zou; Liping Jiang; Xiaodian Cheng; Zhenting Lv (Environmental Science and Pollution Research, 2017)

Substitution mapping of QTLs controlling seed dormancy using single segment substitution lines derived from multiple cultivated rice donors in seven cropping seasons - Yuliang Zhou; Yuehua Xie; Jinling Cai; Chunbao Liu; Haitao Zhu; Ru Jiang; Yueying Zhong; Guoliang Zhang; Bin Tan; Guifu Liu; Xuelin Fu; Ziqiang Liu; et al. (Theoretical and Applied Genetics, 2017)

Zircon U–Pb dating of eclogite from the Qiangtang terrane, north-central Tibet: a case of metamorphic zircon with magmatic geochemical features - Qing-guo Zhai; Bor-ming Jahn; Xian-hua Li; Ru-yuan Zhang; Qiu-li Li; Ya-nan Yang; Jun Wang; Tong Liu; Pei-yuan Hu; Suo-han Tang (International Journal of Earth Sciences, 2017)

Effects of xeric shrubs on soil microbial communities in a desert in northern China - Yanfei Sun; Yuqing Zhang; Wei Feng; Shugao Qin; Zhen Liu; Yuxuan Bai; Ru Yan; Keyu Fa (Plant and Soil, 2017)

Propofol attenuates H2O2-induced oxidative stress and apoptosis via the mitochondria- and ER-medicated pathways in neonatal rat cardiomyocytes - Xue-Ru Liu; Lu Cao; Tao Li; Lin-Lin Chen; Yi-Yan Yu; Wen-Jun Huang; Li Liu; Xiao-Qiu Tan (Apoptosis, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

First-Order Acoustic Wave Equation Reverse Time Migration Based on the Dual-Sensor Seismic Acquisition System - Jiachun You; Xuewei Liu; Ru-Shan Wu (Pure and Applied Geophysics, 2017)

Comparison of Conventional Washing Processing and pH Shift Processing on Gelation Characteristics of Bighead Carp ( Aristichthys nobilis ) Muscle Proteins - Tong Chang; Chenjie Wang; Hong Yang; Shanbai Xiong; Youming Liu; Ru Liu (Journal of Aquatic Food Product Technology, 2017)

Altered Resting-State Signals in Patients with Acute Stroke In or Under the Thalamus - Lijun Chen; Chuanfu Li; Jian Zhai; Anqin Wang; Qin Song; Ying Liu; Ru Ma; Long Han; Yamikani Ndasauka; Xiaoming Li; Hai Li; Xiaochu Zhang (Neuroscience Bulletin, 2016)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Dynamic quantitative proteomics characterization of TNF-α-induced necroptosis - Yang Wang; Zhi-Hao Huang; Yang-Jia Li; Gui-Wei He; Ru-Yuan Yu; Jie Yang; Wan-Ting Liu; Bin Li; Qing-Yu He (Apoptosis, 2016)

Over-expression of miR166a inhibits cotyledon formation in somatic embryos and promotes lateral root development in seedlings of Larix leptolepis - Zhe-Xin Li; Shui-Gen Li; Li-feng Zhang; Su-ying Han; Wan-Feng Li; Hai-yan Xu; Wen-hua Yang; Ya-li Liu; Yan-ru Fan; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Activation of the Ca2+-sensing receptors increases currents through inward rectifier K+ channels via activation of phosphatidylinositol 4-kinase - Chung-Hung Liu; Hsueh-Kai Chang; Sue-Ping Lee; Ru-Chi Shieh (Pflügers Archiv - European Journal of Physiology, 2016)

Salicylic acid-induced antioxidant protection against low temperature in cold-hardy winter wheat - Jing Yu; Jing Cang; Yanping Li; Ru Huang; Qiuwei Lu; Xiutian Wang; Lijie Liu; Qinghua Xu; Kejian Zhang (Acta Physiologiae Plantarum, 2016)

Peripheral Blood MicroRNA Expression Profiles in Alzheimer’s Disease: Screening, Validation, Association with Clinical Phenotype and Implications for Molecular Mechanism - Ru-Jing Ren; Yong-Fang Zhang; Eric B. Dammer; Yi Zhou; Li-ling Wang; Xiao-Hong Liu; Bei-Lei Feng; Guo-Xin Jiang; Sheng-Di Chen; Gang Wang; Qi Cheng (Molecular Neurobiology, 2016)

Trans-cinnamaldehyde protected PC12 cells against oxygen and glucose deprivation/reperfusion (OGD/R)-induced injury via anti-apoptosis and anti-oxidative stress - Xue Qi; Ru Zhou; Yue Liu; Jing Wang; Wan-Nian Zhang; Huan-Ran Tan; Yang Niu; Tao Sun; Yu-Xiang Li; Jian-Qiang Yu (Molecular and Cellular Biochemistry, 2016)

Relationship between leaf reddening, ROS and antioxidants in Buxus microphylla during overwintering - Xue-ru Jiang; Jin-gen Peng; Meng-xue Jia; Yan Liu; Ling Guo; Rong-fu Gao (Acta Physiologiae Plantarum, 2016)

Functional expression of human serum albumin-tandem thrombopoietin mimetic peptide fusion protein as a novel thrombopoietin analog in Pichia pastoris - Meizhu Wang; Dejuan Zhi; Jun Xian; Yi Ru; Suzhen Wei; Na Wang; Yiyao Liu; Haiqing Wang; Yuejuan Pei; Meijuan Song; Yang Li; Hongyu Li (Biotechnology Letters, 2016)

Pertrogenesis and tectonic implications of the late Jurassic basic rocks from the northern Shi‐Hang zone, Southeast China - Qing Zhou; Yao–hui Jiang; Shi–yong Liao; Peng Zhao; Ru–ya Jia; Zheng Liu; Guo–chang Wang; Chun–yu Ni (Island Arc, 2016)
The tectonic setting of the late mesozoic of South China is in a debate between two schools of thought: an intra‐continental rift zone along a passive continental margin or active rifting associated with subduction of the paleo‐Pacific Plate. In this study, we present new sensitive high‐resolution ion microprobe (SHRIMP) U‐Pb zircon ages, along with geochemical data of three basic dikes that cross‐cut the Dexing porphyry copper deposit. The deposit is the largest of its kind in eastern China and part of large scale mineralization associated with Mesozoic magmatic activity in the area. Our results indicate that the dikes were emplaced in the Late Jurassic with an average U‐Pb age of 153.5 ± 2.4 Ma. The intrusions have bulk ε Nd (t) of ca +0.7 and zircon ε Hf (t) value of +1.54 to +6.92. Based on relatively enriched light rare earth elements (LREE) and depleted high‐field‐strength elements (HFSE) abundances with pronounced negative Ta–Nb, Hf–Zr and Ti anomalies in multi‐element diagrams, we propose that these dikes were derived from a subduction‐modified lithospheric mantle source. The variability in Hf isotopes identifies some degree of crustal contaminations. Our data support a scenario with a back‐arc extensional setting or an intra‐arc rift environment associated with the westward subduction of the paleo‐Pacific Plate at or prior to the late Jurassic as the most likely cause for these subduction signatures.

Effect of desiccation in shade on in vitro oocyte maturation and development of the sea cucumber Apostichopus japonicus (Echinodermata: Holothuroidea) - Shilin Liu; Yi Zhou; Tao Zhang; Lina Sun; Xiaoshang Ru; Junhua Li; Hongsheng Yang (Invertebrate Reproduction & Development, 2016)

Genetic Diversity and Population Structure Patterns in Chinese Cherry (Prunus pseudocerasus Lindl) Landraces - Tao Chen; Xiao-jiao Huang; Jing Zhang; Qing Chen; Yin Liu; Hao-ru Tang; Dong-ming Pan; Xiao-rong Wang (Plant Molecular Biology Reporter, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

Differential expression of ATP-gated P2X receptors in DRG between chronic neuropathic pain and visceralgia rat models - Lin Chen; Yu-wei Liu; Kai Yue; Qin Ru; Qi Xiong; Bao-miao Ma; Xiang Tian; Chao-ying Li (Purinergic Signalling, 2016)

Sodium Channel Voltage-Gated Beta 2 Plays a Vital Role in Brain Aging Associated with Synaptic Plasticity and Expression of COX5A and FGF-2 - Yan-Bin XiYang; You-Cui Wang; Ya Zhao; Jin Ru; Bing-Tuan Lu; Yue-Ning Zhang; Nai-Chao Wang; Wei-Yan Hu; Jia Liu; Jin-Wei Yang; Zhao-Jun Wang; Chun-Guang Hao; et al. (Molecular Neurobiology, 2016)

The rural carbonaceous aerosols in coarse, fine, and ultrafine particles during haze pollution in northwestern China - Chong-Shu Zhu; Jun-Ji Cao; Chuen-Jinn Tsai; Zhen-Xing Shen; Sui-Xin Liu; Ru-Jin Huang; Ning-ning Zhang; Ping Wang (Environmental Science and Pollution Research, 2016)

Isolation and characterization of collagens from the skin of giant grouper ( Epinephelus lanceolatus ) - Cheng-Hong Hsieh; Chyuan-Yuan Shiau; Yi-Cheng Su; Yi-Han Liu; Yu-Ru Huang (Journal of Aquatic Food Product Technology, 2016)

Identification of geranylgeranyl diphosphate synthase genes from Tripterygium wilfordii - Meng Zhang; Ping Su; Yong-Jin Zhou; Xiu-Juan Wang; Yu-Jun Zhao; Yu-Jia Liu; Yu-Ru Tong; Tian-Yuan Hu; Lu-Qi Huang; Wei Gao (Plant Cell Reports, 2015)

Effects of Cu2+ and Zn2+ on growth and physiological characteristics of green algae, Cladophora - De-ju Cao; Pan-pan Xie; Juan-wei Deng; Hui-min Zhang; Ru-xiao Ma; Cheng Liu; Ren-jing Liu; Yue-gan Liang; Hao Li; Xiao-dong Shi (Environmental Science and Pollution Research, 2015)

Combined characteristics of drought on multiple time scales in Huang-Huai-Hai River basin - Ru Huang; Denghua Yan; Shaohua Liu (Arabian Journal of Geosciences, 2015)

Isolation and characterisation of Bacillus spp. antagonistic to Vibrio parahaemolyticus for use as probiotics in aquaculture - Xue-Fei Liu; Ya Li; Jian-Rong Li; Lu-Yun Cai; Xiu-Xia Li; Jin-Ru Chen; Shu-Xia Lyu (World Journal of Microbiology and Biotechnology, 2015)

Coronary Revascularization Improves QT Dispersion in Patients with Chronic Coronary Artery Total Occlusion - Feng Zhang; Xiaojian Zhang; Xin Zhang; Bo Chen; Yukun Liu; Wen-wei Yue; Ru-yi Jia (Cell Biochemistry and Biophysics, 2015)

Two new triterpenoids from Nauclea officinalis - Hai-Yang Wang; Ke Liu; Ru-Xia Wang; San-Hai Qin; Feng-Ling Wang; Jing-Yong Sun (Natural Product Research, 2015)

Augmenter of liver regeneration plays a protective role against hydrogen peroxide-induced oxidative stress in renal proximal tubule cells - Ning Xia; Ru-yu Yan; Qi Liu; Xiao-hui Liao; Hang Sun; Hui Guo; Ling Zhang (Apoptosis, 2015)

The relationship between the plant-encoded RNA-dependent RNA polymerase 1 and alternative oxidase in tomato basal defense against Tobacco mosaic virus - Yang-Wen-Ke Liao; Ya-Ru Liu; Jia-Yang Liang; Wen-Ping Wang; Jie Zhou; Xiao-Jian Xia; Yan-Hong Zhou; Jing-Quan Yu; Kai Shi (Planta, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Studies on mitogen-activated protein kinase signaling pathway in the alveolar macrophages of chronic bronchitis rats - Yan Huang; Xiao-Ming Meng; Guo-Lin Jiang; Ya-Ru Yang; Juan Liu; Xiong-Wen Lv; Jun Li (Molecular and Cellular Biochemistry, 2015)

Genetic analysis and chromosome mapping of a thermo-sensitive genic male sterile gene in wheat - Zhen-Gang Ru; Li-Ping Zhang; Tie-Zhu Hu; Hong-Yu Liu; Qing-Kai Yang; Man-Li Weng; Bin Wang; Chang-Ping Zhao (Euphytica, 2015)

The influence of genetics factor on key growth traits and quantitative genetic analysis of sea cucumber Apostichopus Japonicus (Selenka) heat-resistant and fast-growing strain - Sicong Zhang; Hongsheng Yang; Shilin Liu; Libin Zhang; Xiaoshang Ru; Dongxue Xu (Aquaculture International, 2015)

Effects of extremely low frequency alternating-current magnetic fields on the growth performance and digestive enzyme activity of tilapia Oreochromis niloticus - Ying Li; Bixiao Ru; Xingfa Liu; Wei Miao; Kai Zhang; Lili Han; Haijun Ni; Hongjuan Wu (Environmental Biology of Fishes, 2015)

Inactivation of FoxM1 transcription factor contributes to curcumin-induced inhibition of survival, angiogenesis, and chemosensitivity in acute myeloid leukemia cells - Jing-ru Zhang; Fei Lu; Ting Lu; Wen-hao Dong; Peng Li; Na Liu; Dao-xin Ma; Chun-yan Ji (Journal of Molecular Medicine, 2014)

Non-pulmonary vein foci induced before and after pulmonary vein isolation in patients undergoing ablation therapy for paroxysmal atrial fibrillation: incidence and clinical outcome - Hui Cheng; Yin-yin Dai; Ru-hong Jiang; Qiang Liu; Ya-xun Sun; Jian-wei Lin; Zu-wen Zhang; Shi-quan Chen; Jun Zhu; Xia Sheng; Chen-yang Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

Rapid development of tissue bank achieved by International Atomic Energy Agency (IAEA) Tissue Banking Programme in China - Yu-Min Zhang; Jian-Ru Wang; Nai-Li Zhang; Xiao-Ming Liu; Mo Zhou; Shao-Ying Ma; Ting Yang; Bao-Xing Li (Cell and Tissue Banking, 2014)

Umbelopsis changbaiensis sp. nov. from China and the typification of Mortierella vinacea - Ya-Ning Wang; Xiao-Yong Liu; Ru-Yong Zheng (Mycological Progress, 2014)

Enhancing Corynebacterium glutamicum robustness by over-expressing a gene, mshA, for mycothiol glycosyltransferase - Ying-Bao Liu; Can Chen; Muhammad Tausif Chaudhry; Mei-Ru Si; Lei Zhang; Yao Wang; Xi-Hui Shen (Biotechnology Letters, 2014)

(2R, 3S)-pinobanksin-3-cinnamate, a new flavonone from seeds of Alpinia galanga willd., presents in vitro neuroprotective effects - Ben Ru Xin; Jian Fang Liu; Jie Kang; Wing Ping Chan (Molecular & Cellular Toxicology, 2014)

Establishment of a Spinal Cord Injury Model in Adult Rats by an Electrocircuit-Controlled Impacting Device and its Pathological Observations - Yun Wang; Chun-feng Liu; Qi-ping Wang; Heng Gao; Han-rong Na; Ru-tong Yu (Cell Biochemistry and Biophysics, 2014)

Origin of Middle Cambrian and Late Silurian potassic granitoids from the western Kunlun orogen, northwest China: a magmatic response to the Proto-Tethys evolution - Zheng Liu; Yao-Hui Jiang; Ru-Ya Jia; Peng Zhao; Qing Zhou; Guo-Chang Wang; Chun-Yu Ni (Mineralogy and Petrology, 2014)

Origin of Early Cretaceous high-K calc-alkaline granitoids, western Tibet: implications for the evolution of the Tethys in NW China - Yao-Hui Jiang; Zheng Liu; Ru-Ya Jia; Shi-Yong Liao; Peng Zhao; Qing Zhou (International Geology Review, 2014)

New insights into the mechanisms of itch: are pain and itch controlled by distinct mechanisms? - Tong Liu; Ru-Rong Ji (Pflügers Archiv - European Journal of Physiology, 2013)

Changes in Transcriptional Factor Binding Capacity Resulting from Promoter Region Methylation Induce Aberrantly High GDNF Expression in Human Glioma - Zheng-Quan Yu; Bao-Le Zhang; Qing-Xian Ren; Jian-Cun Wang; Ru-Tong Yu; De-Wei Qu; Ze-Hao Liu; Ye Xiong; Dian-Shuai Gao (Molecular Neurobiology, 2013)

Synthesis, biological evaluation and molecular modeling studies of Schiff bases derived from 4-methylsalicylic acid as potential immunosuppressive agents - Ru Yan; Peng-Gang Liu; Zhi-Ming Zhang; Xian-Ying Fang; Xue-Wei Zhang; Jia-Li Deng; Hai-Liang Zhu (Medicinal Chemistry Research, 2013)

Classifying human operator functional state based on electrophysiological and performance measures and fuzzy clustering method - Jian-Hua Zhang; Xiao-Di Peng; Hua Liu; Jörg Raisch; Ru-Bin Wang (Cognitive Neurodynamics, 2013)

Occurrence of rust of Sophora flavescens caused by Uromyces sophorae-flavescentis in China - Ru-Jun Zhou; Jun-Fan Fu; Ning Hao; Zhen Liu; Ying Sun (Phytoparasitica, 2013)

Fine structure and primary sensory projections of sensilla located in the labial-palp pit organ of Helicoverpa armigera (Insecta) - Xin-Cheng Zhao; Qing-Bo Tang; Bente G. Berg; Yang Liu; Yan-Ru Wang; Feng-Ming Yan; Gui-Rong Wang (Cell and Tissue Research, 2013)

Edaravone Ameliorates Oxidative Damage Associated with Aβ25-35 Treatment in PC12 Cells - Gui-lian Zhang; Wang-gang Zhang; Yun Du; Li Yao; Hong Sun; Ru Zhang; Enqi Liu; Ning Bu; Hai-qin Wu; Lei Zhang; Ting-ting Li; Ying-ying Guo (Journal of Molecular Neuroscience, 2013)

Petrogenesis and tectonic implications of early Silurian high-K calc-alkaline granites and their potassic microgranular enclaves, western Kunlun orogen, NW Tibetan Plateau - Ru-Ya Jia; Yao-Hui Jiang; Zheng Liu; Peng Zhao; Qing Zhou (International Geology Review, 2013)

Physiological roles of mycothiol in detoxification and tolerance to multiple poisonous chemicals in Corynebacterium glutamicum - Ying-Bao Liu; Ming-Xiu Long; Ya-Jie Yin; Mei-Ru Si; Lei Zhang; Zhi-Qiang Lu; Yao Wang; Xi-Hui Shen (Archives of Microbiology, 2013)

Imposex effects on the veined rapa whelk (Rapana venosa) in Bohai Bay, China - Li-hui An; Yanqiang Zhang; Shuang-shuang Song; Yue Liu; Zi-cheng Li; Hao Chen; Xing-ru Zhao; Kun Lei; Junmin Gao; Bing-hui Zheng (Ecotoxicology, 2013)

Construction of multiple shRNAs expression vector that inhibits FUT1 gene expression and production of the transgenic SCNT embryos in vitro - Jian-wen Chen; Yu Zhang; Yuan-liang Zhang; Chao Wei; Xing Liu; Na-ru Zhou; Qing Jia; Yun-sheng Li; Xiao-rong Zhang; Yun-hai Zhang (Molecular Biology Reports, 2013)

Mantle origin of the Dexing porphyry copper deposit, SE China - Qing Zhou; Yao-Hui Jiang; Hui-Hua Zhang; Shi-Yong Liao; Guo-Dong Jin; Peng Zhao; Ru-Ya Jia; Zheng Liu (International Geology Review, 2013)

Deletion of RBP-J in dendritic cells compromises TLR-mediated DC activation accompanied by abnormal cytoskeleton reorganization - Yun-Ru Chen; Fan Feng; Li Wang; Shuo-Yao Qu; Zhen-Qiang Zhang; Li Liu; Hong-Yan Qin; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2013)

Increased α-tocotrienol content in seeds of transgenic rice overexpressing Arabidopsis γ-tocopherol methyltransferase - Gui-Yun Zhang; Ru-Ru Liu; Geng Xu; Peng Zhang; Yin Li; Ke-Xuan Tang; Guo-Hua Liang; Qiao-Quan Liu (Transgenic Research, 2013)

RETRACTED ARTICLE: Using remote sensing to quantify the fractional cover of vegetation and exposed bedrock within a complex landscape: applications for karst rocky desertification monitoring - Yuemin Yue; Bo Liu; Kelin Wang; Ru Li; Bing Zhang; Chunhua Zhang; Hongsong Chen (Environmental Monitoring and Assessment, 2013)

Physiological and comparative proteomic analyses in response to nitrogen application in an Amaryllidaceae plant, Lycoris aurea - Qiaomei Ru; Xin Wang; Tingwu Liu; Hailei Zheng (Acta Physiologiae Plantarum, 2013)

Effects of recombinant hIL-2-Luffin P1 immunotoxin combining with arotinoid ethylester on the proliferation and apoptosis of Hut-78 cells - Shu-lei Liu; Wei He; Ru-peng Wang; Zhi Li; Ju Wu; Yun Zhao; Xiao-hong Hu (Molecular & Cellular Toxicology, 2012)

Cloning and sequence analysis of chitin synthase gene fragments of Demodex mites - Ya-e Zhao; Zheng-hang Wang; Yang Xu; Ji-ru Xu; Wen-yan Liu; Meng Wei; Chu-ying Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Chemical composition and insecticidal activity of the essential oil of Amethystea caerulea L. - Sha Sha Chu; Quan Ru Liu; Guo Hua Jiang; Zhi Long Liu (Natural Product Research, 2012)

The prevalence of CD33 and MS4A6A variant in Chinese Han population with Alzheimer’s disease - Yu-Lei Deng; Li-Hua Liu; Ying Wang; Hui-Dong Tang; Ru-Jing Ren; Wei Xu; Jian-Fang Ma; Li-Ling Wang; Jun-Peng Zhuang; Gang Wang; Sheng-Di Chen (Human Genetics, 2012)

Five novel species of the anamorphic genus Candida in the Cyberlindnera clade isolated from natural substrates in Taiwan - Chin-Feng Chang; Yi-Ru Liu; Shan-Fu Chen; Gennadi I. Naumov; Elena S. Naumova; Ching-Fu Lee (Antonie van Leeuwenhoek, 2012)

Construction of a eukaryotic expression vector pEGFP-C1-BMP-2 and its effect on cell migration - Xiao-ying Wang; Zhong-hua Chen; Ru-yi Zhang; Sen-quan Liu; Zhu Mei; Ying-ying Yu; Xiong Zhang; Qiang Xia; Yue-min Ding (Journal of Zhejiang University-SCIENCE B, 2012)

Emerging role of Toll-like receptors in the control of pain and itch - Tong Liu; Yong-Jing Gao; Ru-Rong Ji (Neuroscience Bulletin, 2012)

Oxidative stress induces itch via activation of transient receptor potential subtype ankyrin 1 in mice - Tong Liu; Ru-Rong Ji (Neuroscience Bulletin, 2012)

An upstream regulatory element confers orientation-independent enhancement of the TSG101 promoter activity in transformed cells - Shih-Fang Hsu; Yih-Gang Goan; Hsien-Yu Tsai; Yi-Ru Lin; Rue-Tsuan Liu; Jiin-Tsuey Cheng (Molecular Biology Reports, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Studies on hemolysis of hemolysin produced by Synechocystis sp. PCC 6803 - Shuai Bi; Wei Wang; Yuanyuan Zhao; Shaoguo Ru; Yunzhang Liu (Journal of Ocean University of China, 2011)

Functional characterization of a plasma membrane Na+/H+ antiporter from alkali grass (Puccinellia tenuiflora) - Xin Wang; Ru Yang; Baichen Wang; Guifeng Liu; Chuanping Yang; Yuxiang Cheng (Molecular Biology Reports, 2011)

Effect of glucocorticoids pretreatment on steroidogenic capacity of adrenocortical cells isolated from Meishan piglets - Liu-An Li; Zhan-Wang Wu; Xiao-Jing Yang; Ying-Dong Ni; Nahid Parvizi; Ru-Qian Zhao (In Vitro Cellular & Developmental Biology - Animal, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

MpAsr encodes an intrinsically unstructured protein and enhances osmotic tolerance in transgenic Arabidopsis - Jin-Ran Dai; Bing Liu; Dong-Ru Feng; Hai-yan Liu; Yan-ming He; Kang-biao Qi; Hong-Bin Wang; Jin-Fa Wang (Plant Cell Reports, 2011)

Influence of dhaT mutation of K. pneumoniae on 1,3-propanediol fermentation - Yun-Zhen Xu; Ru-Chun Wu; Zong-Ming Zheng; De-Hua Liu (World Journal of Microbiology and Biotechnology, 2011)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Alternative splicing of the antitrypsin gene in the silkworm, Bombyx mori - Hui-fen Liu; Yi-nü Li; Ru Jia; Wei-zheng Cui; Zhi-mei Mu; Zhi-fang Zhang (Molecular Biology Reports, 2011)

MeJA-inducible expression of the heterologous JAZ2 promoter from Arabidopsis in Populus trichocarpa protoplasts - Yin Wang; Guan-Jun Liu; Xiu-Feng Yan; Zhi-Gang Wei; Zhi-Ru Xu (Journal of Plant Diseases and Protection, 2011)

Development and Characterization of Microsatellite Markers for Genetic Analysis of the Swimming Crab, Portunus trituberculatus - Qianghua Xu; Ru Liu (Biochemical Genetics, 2011)

Asialoglycoprotein receptor interacts with the preS1 domain of hepatitis B virus in vivo and in vitro - Xi Zhang; Shu-mei Lin; Tian-yan Chen; Min Liu; Feng Ye; Yun-ru Chen; Lei Shi; Ying-li He; Lie-xiu Wu; Shu-qin Zheng; Ying-ren Zhao; Shu-lin Zhang (Archives of Virology, 2011)

Molecular characterization and expression analysis of elongation factors 1A and 2 from the Pacific white shrimp, Litopenaeus vannamei - Lei Wang; Yuan Liu; Wei-Na Wang; Wei-Jun Mai; Yu Xin; Jun Zhou; Wen-Yin He; An-Li Wang; Ru-Yong Sun (Molecular Biology Reports, 2011)

Asterotremella meifongana sp. nov. and Asterotremella nantouana sp. nov., two anamorphic basidiomycetous yeasts isolated from soil and mushrooms - Yi-Ru Liu; Li-Ying Huang; Suh-Shen Young; Chin-Feng Chang; Ching-Fu Lee (Antonie van Leeuwenhoek, 2011)

Proteomic survey towards the tissue-specific proteins of mouse mitochondria - Yuan Wang; HaiDan Sun; YaWei Ru; SongYue Yin; Liang Yin; SiQi Liu (Science China Life Sciences, 2011)

Glycerol/Glucose Co-Fermentation: One More Proficient Process to Produce Propionic Acid by Propionibacterium acidipropionici - Yin Liu; Yong-Guang Zhang; Ru-Bing Zhang; Fan Zhang; Jianhang Zhu (Current Microbiology, 2011)

Evaluation of seed storage-protein gene 5′ untranslated regions in enhancing gene expression in transgenic rice seed - Wen Xian Liu; Hua Liang Liu; Zhi Jian Chai; Xiu Ping Xu; Yan Ru Song; Le Qing Qu (Theoretical and Applied Genetics, 2010)

Exploring the molecular mechanisms of OSU-03012 on vascular smooth muscle cell proliferation - Wei-Wen Kuo; Jing-Ru Weng; Chih-Yang Huang; Chang-Hai Tsai; Wei-Hung Liu; Cheng-Hao Wen; Shih-Chang Tsai; Chieh-Hsi Wu (Molecular and Cellular Biochemistry, 2010)

Genetic relationships between resistances to Fusarium head blight and crown rot in bread wheat (Triticum aestivum L.) - Hao Bing Li; Guo Qiang Xie; Jun Ma; Gui Ru Liu; Shu Min Wen; Tomohiro Ban; Sukumar Chakraborty; Chun Ji Liu (Theoretical and Applied Genetics, 2010)

A Series of Novel Rare Earth Molybdotungstosilicate Heteropolyoxometalates Binding to Bovine Serum Albumin: Spectroscopic Approach - Yan-Jun Hu; Yu Ou-Yang; Ai-Min Bai; Ru-Ming Zhao; Yi Liu (Biological Trace Element Research, 2010)

Biological Activation of Heteropoly Complex of Molybdotungstosilicate Containing Lanthanum K10H3La(SiMo6W5O39)2⋅26H2O: Spectroscopic Approach and Microcalorimetry - Yan-Jun Hu; Yu Ou-Yang; Ru-Ming Zhao; Yi Liu (Biological Trace Element Research, 2010)

Spectral indices for estimating ecological indicators of karst rocky desertification - Yuemin Yue; Bing Zhang; Kelin Wang; Bo Liu; Ru Li; Quanjun Jiao; Qingqing Yang; Mingyang Zhang (International Journal of Remote Sensing, 2010)

Analysis of the genetic diversity in Saccharum spontaneum L. accessions from Guangxi Province of China with RAPD-PCR - Ge-min Zhang; Yang-Rui Li; Wei-Zhong He; Hong He; Xi-Hui Liu; Huan-Zhong Song; Hai-Bin Liu; Ru-Cai Zhu; Wei-Kuan Fang (Sugar Tech, 2010)

Cytological and RAPD data revealed genetic relationships among nine selected populations of the wild bramble species, Rubus parvifolius and R. coreanus (Rosaceae) - Xiao-rong Wang; Yuan Liu; Bi-feng Zhong; Xiao-li Dong; Qing Chen; Wu-feng Xia; Hanwu Zhang; Hao-ru Tang (Genetic Resources and Crop Evolution, 2010)

Karyotypic, palynological, and RAPD study on 12 taxa from two subsections of section Idaeobatus in Rubus L. and taxonomic treatment of R. ellipticus, R. pinfaensis, and R. ellipticus var. obcordatus - Xiao-Rong Wang; Hao-Ru Tang; Han-Wu Zhang; Bi-Feng Zhong; Wu-Feng Xia; Yuan Liu (Plant Systematics and Evolution, 2009)

Use of simple sequence repeats for authentication of sugarcane hybrids generated from Yunnan Erianthus rockii - Yan-Fen Jing; Lian-an Tao; Xin-long Liu; Ru-dong An; Xue-kuan Chen (Sugar Tech, 2009)

Kazachstania wufongensis sp. nov., an ascosporogenous yeast isolated from soil in Taiwan - Ching-Fu Lee; Cheng-Hsu Yao; Yi-Ru Liu; Shuh-Sen Young; Ku-Shang Chang (Antonie van Leeuwenhoek, 2009)

Identification of Inonotus obliquus and Analysis of Antioxidation and Antitumor Activities of Polysaccharides - Yana Song; Jing Hui; Wei Kou; Ru Xin; Fei Jia; Ning Wang; Fengqing Hu; Huili Zhang; Hongsheng Liu (Current Microbiology, 2008)

Improved biodesulfurization of hydrodesulfurized diesel oil using Rhodococcus erythropolis and Gordonia sp. - Guo-Qiang Li; Shan-Shan Li; Shi-Wei Qu; Qing-Kun Liu; Ting Ma; Lin Zhu; Feng-Lai Liang; Ru-Lin Liu (Biotechnology Letters, 2008)

Evidence for the production of a proteinaceous hemolytic exotoxin by wild-type strain of Synechocystis sp. PCC 6803 (Cyanobacteria) - Yunzhang Liu; Wei Wang; Shaoguo Ru; Yuanyuan Zhao (Journal of Applied Phycology, 2008)

A rapid accurate culture assay for infectivity in Transmissible Encephalopathies - Ying Liu; Ru Sun; Trisha Chakrabarty; Laura Manuelidis (Journal of NeuroVirology, 2008)

Effect of Pyrogallol on the Growth and Pigment Content of Cyanobacteria-Blooming Toxic and Nontoxic Microcystis Aeruginosa - Bi-Yun Liu; Pei-Jiang Zhou; Jian-Ru Tian; Shun-Yao Jiang (Bulletin of Environmental Contamination and Toxicology, 2007)

Long-term aerobic exercise protects the heart against ischemia/reperfusion injury via PI3 kinase-dependent and Akt-mediated mechanism - Kun-Ru Zhang; Hai-Tao Liu; Hai-Feng Zhang; Quan-Jiang Zhang; Qiu-Xia Li; Qiu-Jun Yu; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2007)

Nematicidal Resorcylides from the Aquatic Fungus Caryospora callicarpa YMF1.01026 - Jinyan Dong; Yanhui Zhu; Hongchuan Song; Ru Li; Hongping He; Haiyang Liu; Rong Huang; Yongping Zhou; Le Wang; Yi Cao; Keqin Zhang (Journal of Chemical Ecology, 2007)

Effect of banning vancomycin analogue avoparcin on vancomycin‐resistant enterococci in chicken farms in Taiwan - Tsai‐Ling Lauderdale; Yih‐Ru Shiau; Hui‐Ying Wang; Jui‐Fen Lai; I‐Wen Huang; Pei‐Chen Chen; Hong‐Yi Chen; Shiow‐Suey Lai; Ya‐Fang Liu; Monto Ho (Environmental Microbiology, 2007)
Summary Avoparcin, a vancomycin analogue, was banned as a feed additive in Taiwan in 2000. A nationwide surveillance was conducted to study the prevalence of vancomycin‐resistant enterococci (VRE) on chicken farms between 2000 and 2003. Among the 1021 E. faecalis and 967 E. faecium isolates studied, resistance to tetracycline, erythromycin, high‐level aminoglycosides, ciprofloxacin and chloramphenicol either increased or remained high except vancomycin. The proportion of VRE decreased, between 2000 and 2003, from 13.7% (22/161) to 3.7% (11/299) for E. faecalis , and 3.4% (4/119) to 0% (0/300) for E. faecium . Only 8.8% (7/80) of the chicken farms surveyed harboured VRE in 2003 compared with 25% (15/60) in 2000. All VRE were resistant to tetracycline and erythromycin. All VRE possess the vanA gene but nearly all (79 of 83 isolates) were susceptible to teicoplanin, indicating VanB phenotype. Some clones were detected from different farms in various regions over the years. We conclude that the frequency of VRE in chicken farms decreased in association with a ban on avoparcin; and the continued presence of VRE may be due to the ability of some strains to persist in the farms, transfer of vancomycin resistance determinants or co‐selection by the continued use of other antibiotics.

Isolation and characterization of a novel thermophilic Bacillus strain degrading long-chain n-alkanes - Lei Wang; Yun Tang; Shuo Wang; Ru-Lin Liu; Mu-Zhi Liu; Yan Zhang; Feng-Lai Liang; Lu Feng (Extremophiles, 2006)

Roots of pioneer trees in the lower sub-tropical area of Dinghushan, Guangdong, China - Yan-ru Hao; Shao-lin Peng; Jiang-ming Mo; Xin-wei Liu; Zhuo-quan Chen; Kai Zhou; Jin-rong Wu (Journal of Zhejiang University-SCIENCE B, 2006)

TransgenicLycium barbarum L. Established as HIV capsid protein expression system - Guo-Li Du; Chang-Zheng Song; Geng-Lin Zhang; Xiao-Guang Sun; Dan-Ru Liu (Plant Molecular Biology Reporter, 2005)

An efficient protocol for plant regeneration from protoplasts of the moss Atrichum undulatum P. Beauv in vitro - Lin-Hui Li; Xian-Ping Wang; Wan-Ru Hou; Xiang-Lin Liu; Yi-Kun He (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Histidines 345 and 378 of Bacillus stearotheromophilus leucine aminopeptidase II are essential for the catalytic activity of the enzyme - Guang-Yuh Hwang; Lih-Ying Kuo; Ming-Ru Tsai; Shin-Ling Yang; Long-Liu Lin (Antonie van Leeuwenhoek, 2005)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Distribution of mercury in typical wetland plants in the Sanjiang plain - Ru-hai Liu; Qi-chao Wang; Yan Wang; Lei Zhang; Zhi-guo Shao (Chinese Geographical Science, 2003)

Estimation of atmospheric input of mercury to South Lake and Jingyue Pool - Feng-man Fang; Qi-chao Wang; Zhuang-wei Ma; Ru-hai Liu; Yu-hong Cao (Chinese Geographical Science, 2002)

Effects of Topographic Slopes on Hydrological Proecsses and Climate - Jinliang Liu; Han-Ru Cho (Advances in Atmospheric Sciences, 2001)

Differential expression of RAB5A in human lung adenocarcinoma cells with different metastasis potential - Li Yu; Feng Hui-chen; Yu Chen; Rong Zou; Song Yan; Liu Chun-xiang; Wang Wu-ru; Pu Li (Clinical & Experimental Metastasis, 1999)

Alkaline Serine Protease Is an Exotoxin of Vibrio alginolyticus in Kuruma Prawn, Penaeus japonicus - Kuo-Kau Lee; Shu-Ru Yu; Ping-Chung Liu (Current Microbiology, 1997)